Laminate for transfer and method for producing same
By forming a plated base layer containing a dispersant and conductive substance on the temporary support reacts with the resin layer to form a transfer laminate, the copper layer and the substrate have poor adhesion and high production cost in the prior art. Problem, high-adhesion and low-cost printed circuit board manufacturing are achieved.
Patent Information
- Application Number
- CN202380039023.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-07
- Filing Date
- 2023-05-11
- Publication Date
- 2024-12-20
AI Technical Summary
In the prior art, when manufacturing printed circuit boards, it is difficult to achieve sufficient adhesion between the copper layer and the polymer film or the rigid substrate without coarse substrate, and large-scale vacuum equipment is required, resulting in high production costs and finished product rates. Low, and traditional methods have problems with defects during plating and the use of environmental load substances.
The temporary support is used to form a plated base layer containing dispersant and conductive substances, and react with the functional groups of the resin layer to form a transfer laminate. The plated base layer is formed on the support through transfer technology to realize the copper layer and The adhesion of the substrate avoids the use of vacuum equipment and reduces production costs.
The high adhesion between the copper layer and the support without coarsing the substrate is achieved, simplifies the manufacturing process, reduces production costs, and improves the quality and yield of the printed circuit board.
Smart Images

Figure CN119174293A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a transfer laminate having a plated base layer and a resin layer sequentially disposed on a temporary support, and also to a method for manufacturing a printed circuit board, a high-frequency transmission printed circuit board, a rigid printed circuit board, a flexible printed circuit board, a package substrate, an electromagnetic wave shield, and a molded circuit substrate using the transfer laminate. Background Art
[0002] Due to the miniaturization and high speed of electronic equipment, the printed wiring substrate is required to be high-density and high-performance. In order to meet this requirement, a printed circuit board with a smooth surface and a sufficiently thin metal layer is required. In addition, as a substrate constituting the printed wiring substrate, a flexible copper-clad laminate (hereinafter, abbreviated as "FCCL") or a rigid copper-clad laminate (hereinafter, abbreviated as "RCCL") is known.
[0003] FCCL is mainly manufactured by the following methods: a method of laminating a heat-resistant polymer film to a copper foil using an epoxy resin adhesive; a method of applying a varnish such as polyimide on the surface of the copper foil and drying and forming a film (casting method); a method of thermally pressing the copper foil to a polyimide film having a thermoplastic resin layer (lamination method); a method of forming a metal film on the surface of a polyimide film by sputtering and then copper plating (sputtering method); a method of applying a primer layer on the surface of the polyimide film, applying a metal nanoparticle layer thereon, and copper plating the metal nanoparticle layer as a base for plating (Patent Document 1).
[0004] On the other hand, RCCL is manufactured by the following methods: a method of bonding a fully cured resin or ceramic to copper foil using an epoxy resin-based adhesive; a method of bonding a semi-cured substrate (prepreg) to copper foil by heating a glass cloth impregnated with epoxy resin; a method of applying a varnish mixed with a resin and an inorganic filler on a release film and drying it, and bonding the resin film obtained after drying to the surface of copper foil or copper wiring by thermal compression (build-up film).
[0005] However, when using copper foil in either FCCL or RCCL, the copper foil or the substrate must be roughened in order to ensure adhesion with the substrate or adhesive layer to be bonded, so there is a problem with the narrow pitch of the printed circuit board. In the high-frequency transmission required for the currently popular 5G and the expected expansion of Beyond 5G, there is a problem of transmission loss in high-frequency areas such as the millimeter wave band.
[0006] On the other hand, the sputtering method and the coating method using a metal nanoparticle layer can make the copper-plated film and the substrate closely attached at a smooth interface without roughening the substrate. Therefore, compared with the method using copper foil, it is easy to achieve narrow pitch of printed circuit boards and has the advantages of low transmission loss of high-frequency signals.
[0007] However, the sputtering method requires large vacuum equipment because it uses evaporation or sputtering to form a metal film, and there are problems such as the size of the substrate on the equipment being limited. In addition, when the sputtering method is applied to both sides of the substrate, there are the following disadvantages: the time before vacuum is twice that of the case of one side, and during the period of processing both sides one by one, defects will occur on the surface of the metal layer formed by the sputtering method, the yield rate will be reduced, and the production cost will be increased.
[0008] In addition, use the coating method of primer layer and metal nano particle layer for example when making single-sided board, need to be coated with primer layer on substrate after, be coated with metal nano particle layer, and then, when making two-sided board, need to be coated with primer layer and metal nano particle layer on the opposite side of the face that is coated first, thereby the required time of processing is lengthened.In addition, also there is the problem of quality aspect that the coating surface produces defect during coating.In addition, when being coated on two sides, the face that is coated first changes with the face that is coated last by the number of times of drying machine and thermal history is different, thereby there is the problem that the quality of the face that is coated first is different from the face that is coated later.
[0009] Here, it is necessary to make the conductive pattern such as the copper layer have sufficient adhesion with the support such as the polymer film and the rigid substrate without roughening the surface of the copper layer and the substrate, and when forming the metal layer, a cheap and simple method is used, and a manufacturing method with stable quality is provided without the need for large-scale vacuum equipment.
[0010] In addition, in the past, it has been gradually used for mobile phones, computers, mirrors, containers, various switches, shower heads, etc. as decorative plating for plastic molded products. The support for these uses is limited to acrylonitrile-butadiene-styrene copolymer (hereinafter, abbreviated as "ABS"), ABS and polycarbonate polymer alloy (hereinafter, abbreviated as "ABS-PC"). As its reason, in order to ensure the close adhesion between the substrate and the plated film, the substrate surface must be coarsened. For example, if it is ABS, the polybutadiene component can be etched and removed with strong oxidants such as hexachromic acid and permanganate, thereby achieving surface coarsening. However, since hexachromic acid and the like are environmental load substances, it is preferably not used, and an alternative method is gradually developed (for example, refer to patent document 2).
[0011] As described above, in plating for the purpose of decorating plastic molded products, the substrate is not limited to ABS or ABS-PC, and other types of plastics can also provide a plating film with excellent adhesion, and the use of environmentally hazardous substances is required to be reduced.
[0012] Prior art literature
[0013] Patent Literature
[0014] Patent Document 1: WO2019 / 013038
[0015] Patent Document 2: WO2015 / 060196 Summary of the invention
[0016] Problems to be solved by the invention
[0017] The problem to be solved by the present invention is to provide a laminate, and a rigid printed circuit board, a flexible printed circuit board and a molded product using the same, wherein the laminate is formed by a stable quality method such as a seed layer that becomes a plating base layer without roughening the surface of the support body, being simple and inexpensive, and not causing damage to the plating base layer due to contact with a coating device or contact with a conveying roller during coating, and having excellent adhesion between the support body and the metal layer (metal plating layer).
[0018] Methods for solving problems
[0019] The inventors have made great efforts to study and solve the above-mentioned problems. As a result, it is found that a plated base layer containing a dispersant and a conductive substance is formed on a temporary support, and after a resin layer is formed thereon, the functional groups of the plated base layer and the resin layer are reacted with each other to produce a transfer laminate. In addition, the transfer laminate is used to be attached to the front and back sides of the support or only to one side, and only the temporary support of the transfer laminate is peeled off, so that a plated base layer is formed on the surface of the support in a simple and inexpensive manner with high quality, thereby completing the present invention.
[0020] That is, the present invention includes the following.
[0021] [1] A transfer laminate, comprising a plated base layer (B) containing a dispersant (b1) and a conductive substance (b2), and a resin layer (C) containing a compound (c1) having a functional group [X] laminated in this order on at least one surface of a temporary support (A), characterized in that:
[0022] In the above-mentioned plating base layer (B), the signal intensity of carbon atoms measured by glow discharge emission spectrometry is larger on the resin layer (C) side than on the temporary support (A) side.
[0023] [2] The transfer laminate according to 1, wherein in the plated base layer (B), the signal intensity of the glow discharge emission spectroscopy on the temporary support (A) side is less than 2 / 3 of that on the resin layer (C) side.
[0024] [3] A transfer laminate as described in 1 or 2, wherein a chemical bond is formed by reacting a basic nitrogen atom-containing group or a phosphate ester group of the compound (b1) contained in the plated base layer (B) with a functional group [X] of the compound (c1) contained in the resin layer (C).
[0025] [4] A transfer laminate as described in any one of 1 to 3, wherein the functional group [X] is selected from one or more functional groups selected from epoxy group, carboxylic acid group, carboxylic anhydride group, ketone group, alkylolamide group, isocyanate group, vinyl group, halogenated alkyl group, acryl group, cyanamide group, urea group, acyl halide group, or one or more functional groups selected from epoxy group and amino group.
[0026] [5] The transfer laminate according to any one of 1 to 4, wherein the conductive substance (b2) is silver.
[0027] [6] The transfer laminate according to any one of 1 to 5, wherein the resin layer (C) is one or more layers.
[0028] [7] The transfer laminate according to any one of 1 to 6, wherein the surface roughness (maximum height Sz) of the temporary support (A) measured with a laser microscope is 0.001 to 20 μm.
[0029] [8] The transfer laminate according to any one of 1 to 7, wherein the temporary support (A) has a release layer on the surface thereof.
[0030] [9] The transfer laminate according to any one of 1 to 8, wherein the temporary support (A) is a film or a metal.
[0031]
[10] A laminated body characterized in that the surface of the transfer laminated body according to any one of 1 to 9 on which the resin layer (C) is formed is bonded to at least one surface of a support D.
[0032]
[11] The laminate according to item 10, wherein the support D is made of a thermosetting resin that is completely cured.
[0033]
[12] A method for producing a transfer laminate according to any one of 1 to 9, comprising:
[0034] Step 1 of forming a plating base layer (B) containing a dispersant (b1) and a conductive material (b2) on at least one surface of the temporary support (A), wherein the dispersant (b1) contains a basic nitrogen atom group or a phosphate group;
[0035] Step 2: forming a resin layer (C) containing a compound (c1) having a functional group [X] thereon, and reacting a basic nitrogen atom group or a phosphate group contained in the dispersant (b1) contained in the above-mentioned plating base layer (B) with the functional group [X] contained in the above-mentioned compound (c1) contained in the above-mentioned resin layer (C) to form a chemical bond.
[0036]
[13] A method for producing a transfer laminate according to any one of 1 to 9, characterized in that:
[0037] Step 1 of patterning and forming a plating base layer (B) containing a dispersant (b1) and a conductive substance (b2) on at least one surface of the temporary support (A), wherein the dispersant (b1) contains a basic nitrogen atom group or a phosphate group; and
[0038] Step 2 is to form the resin layer (C) on the patterned plated base layer (B), and to form a bond by reacting the basic nitrogen atom-containing group or phosphate ester group of the dispersant (b1) contained in the plated base layer (B) with the functional group [X] of the compound (c1) contained in the resin layer (C).
[0039]
[14] The method for producing a transfer laminate according to item 12 or 13, comprising the step 1' of forming a layer having a releasable property on the temporary support (A).
[0040]
[15] A method for manufacturing a conductive pattern, comprising:
[0041] Step 1 of laminating the surface of the transfer laminate obtained by the production method according to 12 or 13, on which the resin layer (C) is formed, to at least one surface of a support (D); and
[0042] Step 2 of peeling off the temporary support (A) of the laminated transfer body and forming the resin layer (C) and the plating base layer (B) on at least one surface of the support (D).
[0043]
[16] The method for producing a conductive pattern as described in 15, which includes a step of forming a metal plating layer (E) on the above-mentioned plated base layer (B).
[0044]
[17] A method for manufacturing a conductive pattern, comprising:
[0045] Step 1 of laminating the surface of the transfer laminate obtained by the production method described in 12 or 13, on which the resin layer (C) is formed, to at least one surface of a support (D);
[0046] Step 2 of forming through holes penetrating both surfaces of the temporary support (A) of the transfer laminate;
[0047] Step 3 of applying any one of palladium, conductive polymer, conductive paste, and carbon to the surface of the transfer laminate and the through-hole to make the surface of the through-hole conductive; and
[0048] Step 4 of peeling off the temporary support (A) and forming a metal plating layer (E) on the plating base layer (B) and the through-holes.
[0049]
[18] A method for manufacturing a conductive pattern, comprising:
[0050] Step 1 of laminating the surface of the transfer laminate obtained by the production method described in 12 or 13, on which the resin layer (C) is formed, to at least one surface of a support (D);
[0051] Step 2 of forming through holes penetrating both surfaces of the temporary support (A) of the transfer laminate;
[0052] Step 3 of forming a metal film on the transfer laminate and the surface of the through hole by dry plating to make the surface of the through hole conductive; and
[0053] Step 4 of peeling off the temporary support (A) and forming a metal plating layer (E) on the plating base layer (B) and the through-holes.
[0054]
[19] A method for manufacturing a conductive pattern, comprising:
[0055] Step 1 of laminating the surface of the transfer laminate obtained by the production method described in 12 or 13, on which the resin layer (C) is formed, to at least one surface of a support (D);
[0056] Step 2 of forming through holes penetrating both surfaces of the temporary support (A) of the transfer laminate;
[0057] Step 3 of peeling off the temporary support (A) and forming a metal plating layer (E) on the surface of the plating base layer (B); and
[0058] Step 4 of filling the through hole with a conductive paste to make the through hole conductive.
[0059]
[20] A method for manufacturing a conductive pattern, comprising:
[0060] Step 1 of bonding a support (D) to at least one surface of a substrate having a conductive pattern formed thereon;
[0061] Step 2: laminating the surface of the transfer laminate obtained by the production method described in 12 or 13, on which the resin layer (C) is formed, to the surface of the support (D);
[0062] Step 3 of forming non-through holes from the temporary support (A) of the transfer laminate to the conductive pattern of the inner layer;
[0063] Step 4 of applying any one of palladium, a conductive polymer, a conductive paste, and carbon to the surface of the transfer laminate and the non-through hole to make the surface of the non-through hole conductive; and
[0064] Step 5 of peeling off the temporary support (A) and forming a metal plating layer (E) on the plating base layer (B) and the non-through holes.
[0065]
[21] A method for manufacturing a conductive pattern, comprising:
[0066] Step 1 of bonding a support (D) to at least one surface of a substrate having a conductive pattern formed thereon;
[0067] Step 2: laminating the surface of the transfer laminate obtained by the production method described in 12 or 13, on which the resin layer (C) is formed, to the surface of the support (D);
[0068] Step 3 of forming non-through holes from the temporary support (A) of the transfer laminate to the conductive pattern of the inner layer;
[0069] Step 4 of forming a metal film on the transfer laminate and the surface of the non-through hole by dry plating to make the surface of the non-through hole conductive; and
[0070] Step 5 of peeling off the temporary support (A) and forming a metal plating layer (E) on the plating base layer (B) and the non-through holes.
[0071]
[22] A method for manufacturing a conductive pattern, comprising:
[0072] Step 1 of bonding a support (D) to at least one surface of a substrate having a conductive pattern formed thereon;
[0073] Step 2: laminating the surface of the transfer laminate obtained by the production method described in 12 or 13, on which the resin layer (C) is formed, to the surface of the support (D);
[0074] Step 3 of forming non-through holes from the temporary support (A) of the transfer laminate to the conductive pattern of the inner layer;
[0075] Step 4 of peeling off the temporary support (A) and forming a metal plating layer (E) on the surface of the plating base layer (B); and
[0076] Step 5 of filling the non-through hole with a conductive paste to make the non-through hole conductive.
[0077]
[23] A method for manufacturing a conductive pattern, comprising:
[0078] Step 1 of laminating the surface of the transfer laminate obtained by the production method described in 12 or 13, on which the resin layer (C) is formed, to at least one surface of a support (D);
[0079] Step 2 of forming through holes penetrating both surfaces of the temporary support (A) of the transfer laminate;
[0080] Step 3 of applying any one of palladium, conductive polymer, conductive paste, and carbon to the surface of the transfer laminate and the through-hole to make the surface of the through-hole conductive;
[0081] Step 4 of peeling off the temporary support (A) and forming a pattern resist on the surface of the plated base layer (B);
[0082] Step 5 of forming a metal plating layer (E) on the plated base layer (B) and the through-hole; and
[0083] Step 6 of peeling off the pattern resist and removing the plating base layer (B) except for the portion where the metal plating layer (E) serving as the conductive pattern is formed by using an etching solution.
[0084]
[24] A method for manufacturing a conductive pattern, comprising:
[0085] Step 1 of laminating the surface of the transfer laminate obtained by the production method described in 12 or 13, on which the resin layer (C) is formed, to at least one surface of a support (D);
[0086] Step 2 of forming through holes penetrating both surfaces of the temporary support (A) of the transfer laminate;
[0087] Step 3 of forming a metal film on the transfer laminate and the surface of the through hole by dry plating to make the surface of the through hole conductive;
[0088] Step 4 of peeling off the temporary support (A) and forming a pattern resist on the surface of the plated base layer (B);
[0089] Step 5 of forming a metal plating layer (E) on the plated base layer (B) and the through-hole; and
[0090] Step 6 of peeling off the pattern resist and removing the plating base layer (B) except for the portion where the metal plating layer (E) serving as the conductive pattern is formed by using an etching solution.
[0091]
[25] A method for manufacturing a conductive pattern, comprising:
[0092] Step 1 of laminating the surface of the transfer laminate obtained by the production method described in 12 or 13, on which the resin layer (C) is formed, to at least one surface of a support (D);
[0093] Step 2 of forming through holes penetrating both surfaces of the temporary support (A) of the transfer laminate;
[0094] Step 3 of peeling off the temporary support (A) and forming a pattern resist on the surface of the plated base layer (B);
[0095] Step 4 of forming a metal plating layer (E) on the plated base layer (B);
[0096] Step 5 of peeling off the pattern resist and removing the above-mentioned plating base layer (B) except for the portion where the metal plating layer (E) to become the conductive pattern is formed by an etching solution; and
[0097] Step 6 of filling the through hole with a conductive paste to make the through hole conductive.
[0098]
[26] A method for manufacturing a conductive pattern, comprising:
[0099] Step 1 of laminating the surface of the transfer laminate obtained by the production method described in 12 or 13, on which the resin layer (C) is formed, to at least one surface of a support (D);
[0100] Step 2 of peeling off the temporary support (A) and forming the resin (C) and the plating base layer (B) on the surface of the support (D);
[0101] Step 3 of forming a pattern resist on the surface of the plating base layer (B);
[0102] Step 4 of forming a metal plating layer (E) on the plated base layer (B);
[0103] Step 5 of peeling off the pattern resist and removing the above-mentioned plating base layer (B) except for the portion where the metal plating layer (E) to become the conductive pattern is formed by an etching solution;
[0104] Step 6 of forming through holes penetrating both surfaces of the temporary support (A) of the transfer laminate; and
[0105] Step 7 of filling the through hole with a conductive paste to make the through hole conductive.
[0106]
[27] A method for manufacturing a conductive pattern, comprising:
[0107] Step 1 of bonding a support (D) to at least one surface of a substrate having a conductive pattern formed thereon;
[0108] Step 2: laminating the surface of the transfer laminate obtained by the production method described in 12 or 13, on which the resin layer (C) is formed, to the surface of the support (D);
[0109] Step 3 of forming non-through holes from the temporary support (A) of the transfer laminate to the conductive pattern of the inner layer;
[0110] Step 4 of applying any one of palladium, a conductive polymer, a conductive paste, and carbon to the surface of the transfer laminate and the non-through hole to make the surface of the non-through hole conductive;
[0111] Step 5 of peeling off the temporary support (A) and forming a pattern resist on the surface of the plating base layer (B);
[0112] Step 6 of forming a metal plating layer (E) on the plated base layer (B) and the non-through holes; and
[0113] Step 7 of peeling off the pattern resist and removing the plating base layer (B) except for the portion where the metal plating layer (E) serving as the conductive pattern is formed by using an etching solution.
[0114]
[28] A method for manufacturing a conductive pattern, comprising:
[0115] Step 1 of bonding a support (D) to at least one surface of a substrate having a conductive pattern formed thereon;
[0116] Step 2: laminating the surface of the transfer laminate obtained by the production method described in 12 or 13, on which the resin layer (C) is formed, to the surface of the support (D);
[0117] Step 3 of forming non-through holes from the temporary support (A) of the transfer laminate to the conductive pattern of the inner layer;
[0118] Step 4 of forming a metal film on the surface of the transfer laminate and the non-through hole by dry plating to make the surface of the non-through hole conductive;
[0119] Step 5 of peeling off the temporary support (A) and forming a pattern resist on the surface of the plating base layer (B);
[0120] Step 6 of forming a metal plating layer (E) on the plated base layer (B) and the non-through holes; and
[0121] Step 7 of peeling off the pattern resist and removing the plating base layer (B) except for the portion where the metal plating layer (E) serving as the conductive pattern is formed by using an etching solution.
[0122]
[29] A method for manufacturing a conductive pattern, comprising:
[0123] Step 1 of bonding a support (D) to at least one surface of a substrate having a conductive pattern formed thereon;
[0124] Step 2: laminating the surface of the transfer laminate obtained by the production method described in 12 or 13, on which the resin layer (C) is formed, to the surface of the support (D);
[0125] Step 3 of forming non-through holes from the temporary support (A) of the transfer laminate to the conductive pattern of the inner layer;
[0126] Step 4 of peeling off the temporary support (A) and forming a pattern resist on the surface of the plating base layer (B);
[0127] Step 5 of forming a metal plating layer (E) on the plated base layer (B);
[0128] Step 6 of peeling off the pattern resist and removing the above-mentioned plating base layer (B) except for the portion where the metal plating layer (E) to become the conductive pattern is formed by an etching solution; and
[0129] Step 7 of filling the non-through hole with a conductive paste to make the non-through hole conductive.
[0130]
[30] A method for manufacturing a conductive pattern, comprising:
[0131] Step 1 of bonding a support (D) to at least one surface of a substrate having a conductive pattern formed thereon;
[0132] Step 2: laminating the surface of the transfer laminate obtained by the production method described in 12 or 13, on which the resin layer (C) is formed, to the surface of the support (D);
[0133] Step 3 of peeling off the temporary support (A) and forming the resin (C) and the plating base layer (B) on the surface of the support (D);
[0134] Step 4 of forming a pattern resist on the surface of the plated base layer (B);
[0135] Step 5 of forming a metal plating layer (E) on the plated base layer (B);
[0136] Step 6 of peeling off the pattern resist and removing the above-mentioned plating base layer (B) except for the portion where the metal plating layer (E) to become the conductive pattern is formed by an etching solution;
[0137] Step 7 of forming non-through holes from the temporary support (A) of the transfer laminate to the conductive pattern of the inner layer; and
[0138] Step 8 of filling the non-through hole with a conductive paste to make the non-through hole conductive.
[0139]
[31] The method for producing a conductive pattern as described in any one of 15 to 30, which includes a step of smoothing the surface of the above-mentioned support (D).
[0140]
[32] A method for manufacturing a printed circuit board, characterized by using the method for manufacturing a conductive pattern described in any one of 15 to 31.
[0141]
[33] A method for manufacturing a printed circuit board or an electromagnetic wave shielding film, characterized in that the method for manufacturing a conductive pattern described in any one of 15 to 31 is used, and the support (D) is selected from one or more of a rigid substrate, a film, a deposited film, ceramics, glass, a silicon wafer, and a metal.
[0142]
[34] A method for producing a molded circuit component, characterized in that the method for producing a conductive pattern described in any one of 15 to 31 is used, and the support (D) is a molded product.
[0143] Effects of the Invention
[0144] The transfer laminate of the present invention is a laminate formed by forming a plated base layer and a resin layer on a temporary support, and reacting the functional groups of the plated base layer and the resin layer with each other. In addition, a method for producing a conductive pattern is provided, by temporarily attaching the transfer laminate to one or both sides of a support, so that a resin layer and a plated base layer can be easily formed on a support in a simpler, cheaper and higher quality manner than a conventional coating method using a metal nanoparticle layer.
[0145] In addition, the method for producing the conductive pattern of the present invention can be suitably used for printed circuit boards, high-speed transmission printed circuit boards, rigid printed wiring boards, flexible printed circuit boards, package substrates, ceramic substrates, glass substrates, silicon wafer substrates, metal substrates, conductive films for touch panels, metal meshes for touch panels, organic solar cells, organic EL components, organic transistors, RFID such as contactless IC cards, electromagnetic wave shielding, LED lighting substrates, digital signage and other electronic components. In particular, it is most suitable for rigid printed circuit boards and flexible printed circuit boards.
[0146] In addition, by applying to molded products, it can be suitably used for electronic parts such as molded circuit boards (MID), connectors for connecting optical communication wiring, electrical components, electric motor peripheral components, battery components, etc.; automotive decorative parts, reflector lamps, mobile phones, computers, mirrors, containers, home appliances, various switches, faucet parts, shower heads, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0147] [ Figure 1 ] Figure 1 These are the results of measurement by glow discharge emission spectroscopy of a coating film obtained by applying a fluid containing silver as the conductive substance (b2) to a temporary support (A) and drying the fluid.
[0148] [ Figure 2 ] Figure 2 These are the results of measurement by glow discharge emission spectroscopy of a coating film obtained by applying a fluid containing silver as the conductive substance (b2) to a temporary support (A) and drying the fluid.
[0149] [ Figure 3 ] Figure 3 The diagram is a cross-sectional view showing each step related to the method for producing the transfer laminate of the present invention.
[0150] [ Figure 4 ] Figure 4 The diagram is a cross-sectional view showing each step related to the method for producing the transfer laminate of the present invention.
[0151] [ Figure 5 ] Figure 5 The diagram is a cross-sectional view showing each step related to the method for producing the transfer laminate of the present invention.
[0152] [ Figure 6 ] Figure 6 It is a cross-sectional view for each process related to the production method for smoothing the surface of the support (D).
[0153] [ Figure 7 ] Figure 7The present invention is a cross-sectional view showing the steps of a method for producing a conductive pattern, in which a transfer laminate is bonded to both surfaces of a support (D), a temporary support (A) is peeled off, and a metal plating layer (E) is formed.
[0154] [ Figure 8 ] Figure 8 The present invention is a cross-sectional view showing the steps of a method for producing a conductive pattern, in which a transfer laminate is bonded to both surfaces of a support (D), a temporary support (A) is peeled off, and a metal plating layer (E) is formed.
[0155] [ Fig. 9 ] Fig. 9 The present invention is a cross-sectional view showing the steps of a method for producing a conductive pattern, in which a transfer laminate is bonded to both surfaces of a support (D), through holes are formed and a conductive treatment is performed, and then a temporary support (A) is peeled off to form a metal plating layer (E).
[0156] [ Fig.10 ] Fig.10 The present invention is a cross-sectional view showing the steps of a method for producing a conductive pattern, in which a transfer laminate is bonded to both surfaces of a support (D), through holes are formed and a conductive treatment is performed, and then a temporary support (A) is peeled off to form a metal plating layer (E).
[0157] [ Fig.11 ] Fig.11 The present invention is a cross-sectional view showing the steps of forming a method for producing a conductive pattern, wherein a transfer laminate is bonded to both surfaces of a support (D), a through hole is formed, a metal plating layer (E) is formed, and then the through hole is filled with a conductive paste.
[0158] [ Fig.12 ] Fig.12 The present invention is a cross-sectional view of the steps in a method for manufacturing a conductive pattern, in which a support (D) is laminated on a conductive pattern, a transfer laminate is attached, non-through holes are formed and a conductive treatment is performed, and then a temporary support (A) is peeled off to form a metal plating layer (E).
[0159] [ Fig.13 ] Fig.13 The present invention is a cross-sectional view of the steps in a method for manufacturing a conductive pattern, in which a support (D) is laminated on a conductive pattern, a transfer laminate is attached, non-through holes are formed and a conductive treatment is performed, and then a temporary support (A) is peeled off to form a metal plating layer (E).
[0160] [ Fig.14 ] Fig.14The present invention is a cross-sectional view showing the steps of a method for manufacturing a conductive pattern, in which a support (D) is laminated on a conductive pattern, a transfer laminate is attached, a non-through hole is formed, a metal plating layer (E) is formed, and then the non-through hole is filled with a conductive paste.
[0161] [ Fig.15 ] Fig.15 The present invention is a cross-sectional view of the steps related to the method for manufacturing a conductive pattern, in which a transfer laminate is bonded to both surfaces of a support (D), through holes are formed and a conductive treatment is performed, the temporary support (A) is peeled off, and a metal plating layer (E) is formed by a semi-additive method.
[0162] [ Fig.16 ] Fig.16 The present invention is a cross-sectional view of the manufacturing method according to the steps, in which a transfer laminate is bonded to both surfaces of a support (D), through holes are formed and a conductive treatment is performed, the temporary support (A) is peeled off, and a conductive pattern of a metal plating layer (E) is formed by a semi-additive method.
[0163] [ Fig.17 ] Fig.17 The present invention is a cross-sectional view according to the process related to the method for manufacturing a conductive pattern, in which a transfer laminate is bonded to both surfaces of a support (D) to form a through hole, a temporary support (A) is peeled off, a metal plating layer (E) is formed by a semi-additive method, and then the through hole is filled with a conductive paste.
[0164] [ Fig.18 ] Fig.18 This is a cross-sectional view of the steps related to the method for manufacturing a conductive pattern, in which a transfer laminate is bonded to both surfaces of a support (D), a temporary support (A) is peeled off, a metal plating layer (E) is formed by a semi-additive method, and through holes are formed and then filled with a conductive paste.
[0165] [ Fig.19 ] Fig.19 The present invention is a cross-sectional view of the steps related to the method for manufacturing a conductive pattern, in which a support (D) is laminated on both sides of a conductive pattern, a transfer laminate is adhered, a non-through hole is formed and a conductive treatment is performed, and then a temporary support (A) is peeled off and a metal plating layer (E) is formed by a semi-additive method.
[0166] [ Fig. 20 ] Fig. 20 The present invention is a cross-sectional view of the manufacturing method according to the steps, in which a support (D) is laminated on both sides of a conductive pattern, a transfer laminate is adhered, non-through holes are formed and a conductive treatment is performed, and then a temporary support (A) is peeled off and a conductive pattern of a metal plating layer (E) is formed by a semi-additive method.
[0167] [ Fig.21] Fig.21 The present invention is a cross-sectional view of the manufacturing method of a conductive pattern in which a support (D) is stacked on both sides of a conductive pattern, a transfer stack is adhered, a non-through hole is formed, a temporary support (A) is peeled off, a metal plating layer (E) is formed by a semi-additive method, and then the non-through hole is filled with a conductive paste.
[0168] [ Fig. 22 ] Fig. 22 The present invention is a cross-sectional view of the steps related to the method for manufacturing a conductive pattern, in which a support (D) is laminated on both sides of a conductive pattern, a transfer laminate is adhered, a temporary support (A) is peeled off, a metal plating layer (E) is formed by a semi-additive method, and non-through holes are formed, and then the non-through holes are filled with a conductive paste. DETAILED DESCRIPTION
[0169] The present invention is a transfer laminate and a method for manufacturing the same, wherein a plated base layer (B) containing a dispersant (b1) and a conductive substance (b2), and a resin layer (C) containing a compound (c1) having a functional group [X] are sequentially stacked on at least one side of a temporary support (A), and a chemical bond is formed by reacting the functional group of the compound (b1) contained in the plated base layer (B) with the functional group [X] of the compound (c1) contained in the resin layer (C).
[0170] In addition, the present invention is a method for manufacturing a conductive pattern, characterized in that it includes: a step 1 of bonding the surface of the transfer laminate on which the resin layer (C) is formed to at least one side of a support (D); and a step 2 of peeling off the temporary support (A) of the bonded transfer laminate, and forming the resin layer (C) and the plated base layer (B) on at least one side of the support (D).
[0171] The transfer laminate of the present invention may be a laminate in which the plated base layer (B) and the resin layer (C) are sequentially stacked on at least one side of a temporary support (A), or may be a laminate in which the plated base layer (B) and the resin layer (C) are sequentially stacked on both sides of the temporary support (A).
[0172] Since the temporary support (A) needs to be peeled off eventually after the transfer laminate is bonded, it is preferable to select a temporary support (A) that can be easily peeled off from the plating base layer (B) at the interface. For example, as the polymer film, there can be mentioned: aromatic polyesters such as polyethylene terephthalate, polybutylene terephthalate (PBT), polyethylene naphthalate, and polybutylene naphthalate; fluorine-based resins such as polytetrafluoroethylene, tetrafluoroethylene perfluoroalkyl vinyl ether copolymer, tetrafluoroethylene-hexafluoropropylene copolymer, tetrafluoroethylene-ethylene copolymer, vinylidene fluoride resin, trifluorochloroethylene resin, trifluorochloroethylene-ethylene copolymer, tetrafluoroethylene-perfluorodioxole copolymer, vinyl fluoride resin, and polyvinylidene fluoride; polymethylpentene (TPX), polypropylene (PP) [including biaxially oriented polypropylene (OPP) and nonaxially oriented polypropylene (CPP)], and polyethylene (PE) [including high-density polyethylene (HDPE), low-density polyethylene (LDPE), linear low-density polyethylene
[0173] Olefin resins such as (LLDPE)]; polystyrene (PS); polyimide resins such as polyvinyl chloride (PVC), polyimide, and transparent polyimide; polyamide resins such as polyamideimide and polyamide; polycarbonate, acrylonitrile-butadiene-styrene (ABS) resin, polymer alloys of ABS and polycarbonate, acrylic resins such as poly(methyl)acrylate, polyvinyl chloride, polyvinylidene chloride, polyvinyl alcohol, polycarbonate, polyethylene, polypropylene, polyurethane, liquid crystal polymer (LCP), polyetheretherketone (PEEK), polyphenylene sulfide (PPS), polyphenylene sulfone (PPSU), epoxy resin, etc. Among them, aromatic polyester, polyethylene, olefin resin, fluorine resin, polyimide resin, LCP, polyphenylene sulfide, and polystyrene are preferably used as the above-mentioned temporary support.
[0174] In addition, as the above-mentioned temporary support (A), metals can be used, and copper, aluminum, aluminum alloys, titanium, stainless steel, beryllium bronze, phosphor bronze, nickel, nickel-chromium heat-resistant alloys, nickel alloys, tin, zinc, lead, gold, zinc, lead, tantalum, molybdenum, niobium, iron, and silver can be used. In addition, as an inorganic substrate, the above-mentioned temporary support (A) composed of silicon, ceramics, glass, etc. can be used.
[0175] The shape of the temporary support (A) is not particularly limited, and a film or sheet shape is easy to handle. The thickness of the temporary support (A) is usually preferably in the range of 1 to 5,000 μm, more preferably in the range of 1 to 300 μm, more preferably in the range of 1 to 200 μm, more preferably in the range of 1 to 100 μm, and further preferably in the range of 1 to 50 μm. Since the temporary support (A) is attached to the support (D) described later and is no longer required after the plated base layer (B) and the resin layer (C) are transferred and laminated to the support (D), it is preferably a film thin enough not to impair workability.
[0176] In order to easily transfer the plated base layer (B) and the resin layer (C) from the transfer laminate, the surface of the temporary support (A) is preferably smooth. Specifically, the surface roughness (maximum height Sz) when measured with a laser microscope is preferably in the range of 0.001 to 30 μm, preferably in the range of 0.01 to 20 μm, and more preferably in the range of 0.05 to 10 μm. In addition, the surface roughness (maximum height Sz) refers to the value measured by the evaluation method described in ISO 25178, which represents the distance from the highest point to the lowest point on the surface.
[0177] In addition, an object having a release layer formed on the surface of the above-mentioned temporary support (A) can be used. The release layer can be formed by applying a silicone release agent or a non-silicone release agent on the above-mentioned temporary support (A). As the non-silicone release agent, alkyd resin, melamine resin, acrylic resin, cellulose resin, urea resin, polyolefin, paraffin, silica composite acrylic resin, silica composite melamine resin, silica composite polyurethane resin, silica composite epoxy resin, silica composite phenol resin, silica composite polyvinyl alcohol resin, silica composite polystyrene resin, silica composite polyvinyl acetate resin, silica composite polyimide resin, silica composite polyamide-imide resin can be used. When the temporary support (A) of the transfer laminate is peeled off, the silicone resin is transferred to the surface of the plated base layer (B), and when the plated base layer (B) described later is formed into a metal plating layer, the adhesion between the plated base layer (B) and the metal plating layer (E) is impaired. Therefore, as the release layer, it is preferred to use a non-silicone release agent, preferably a polyolefin, acrylic resin, melamine resin, polyurethane resin, silica composite acrylic resin, silica composite melamine resin, silica composite polyurethane resin, silica composite epoxy resin, silica composite phenol resin, silica composite polyvinyl alcohol resin, silica composite polystyrene resin, silica composite polyvinyl acetate resin, silica composite polyimide resin, silica composite polyamide-imide resin.
[0178] The thickness of the release layer is not particularly limited as long as the release property is ensured, but is preferably a thin film to prevent the release layer from adhering to the surface of the plating base layer (B) described below. Specifically, it is preferably 0.01 to 50 μm, more preferably 0.01 to 10 μm, and even more preferably 0.01 to 1 μm.
[0179] As above-mentioned temporary support (A), preferably use metal.When using the above-mentioned plating base layer (B) of metal nanoparticle in the surface formation of the described temporary support (A) described later, if use metal, compared with the situation of using polymer film, can dry with higher temperature, reduce the surface resistance of plating base layer (B), thereby can improve the conductivity of plating base layer itself.In addition, in the operation forming conductive pattern, after the face of the resin (C) of the transfer laminate described later is attached to support (D), from the face of the above-mentioned temporary support (A) form the through hole that penetrates both sides, or when the conductive pattern from the face of the above-mentioned temporary support (A) to the inner layer forms non-through hole, form hole with drill or laser, when using polymer film as the above-mentioned temporary support (A), during the perforation processing, can produce polymeric slag, in the operation making through hole or non-through hole conductive, sometimes produce the fault of plating precipitation. On the other hand, when a metal is used, a conventional process of drilling a printed circuit board using a drill or a laser can be applied, and copper or aluminum is preferably used as the temporary support (A).
[0180] When the above-mentioned plating base layer (B) is applied to the temporary support (A) described later, in order to make the coating easy to wet, the surface of the above-mentioned temporary support (A) can also be surface-treated as required. Specifically, methods such as dry treatments such as plasma discharge treatment, ultraviolet treatment, and wet treatments using aqueous solutions such as water, acid, alkali, or organic solvents can be cited. If the above-mentioned temporary support (A) is excessively surface-treated, then the interface between the temporary support (A) described later and the plating base layer (B) becomes difficult to peel off, so it is preferably appropriately implemented to surface-treat.
[0181] Next, the plating base layer (B) will be described.
[0182] The above-mentioned plating base layer (B) is a layer containing a dispersant (b1) and a conductive substance (b2). If the plating base layer (B) is formed on a temporary support (A) by the following method, the above-mentioned dispersant (b1) can be localized at the interface between the plating support layer (B) and the air, and at the interface between the plating base layer (B) and the temporary support (A).
[0183] The interface between the plated base layer (B) and the air is the surface on which the resin layer (C) described below is formed. By localizing the above-mentioned dispersant (b1) in large quantities at the air interface, the functional group possessed by the above-mentioned dispersant (b1) and the functional group [X] possessed by the compound (c1) contained in the resin layer (C) can easily form a chemical bond, thereby improving the adhesion between the plated base layer (B) and the resin layer (C). On the other hand, since the interface between the plated base layer (B) and the temporary support (A) is the surface on which the metal plated layer (E) is formed after the transfer laminate described below is transferred to the support (D), when there is a large amount of localized dispersant (b1), the adhesion between the plated base layer (B) and the metal plated layer (E) is reduced.
[0184] Here, as a result of diligent research, it was found that: for the presence state of carbon atoms originating from the dispersant (b1) measured by glow discharge emission spectroscopy when a plating base layer (B) is formed on a temporary support (A), there are optimal amounts of carbon atoms at the interface between the plating base layer (B) and the air (on the side of the final resin layer (C)) and at the interface between the plating base layer (B) and the temporary support (A) (on the side of the final metal plating layer (E)).
[0185] Glow discharge emission spectrometry is a method of measuring the element distribution in the depth direction of the coating base layer (B) by high-frequency sputtering of the coating base layer (B) in an argon glow discharge region and continuously splitting the luminous lines of the sputtered atoms. As a glow discharge emission spectrometry, a high-frequency glow discharge luminescent surface analyzer (GDS) GD-Profiler 2 manufactured by Horiba Manufacturing Co., Ltd. can be used. As measurement conditions, argon gas, gas pressure 1000Pa, power 20W, and anode diameter 4mm are set. In addition, the signal intensity obtained by the measurement of glow discharge emission spectrometry becomes the luminous intensity of each element obtained simultaneously from an independent detection machine. In order to quantify each element, a calibration curve corresponding to the number of elements must be prepared. However, if one element is focused on, the element distribution in the depth direction relative to the coating base layer (B) can be obtained based on the signal intensity.
[0186] Figure 1 and Figure 2 These are the results of glow discharge emission spectroscopy when silver was used as the conductive material (b2).
[0187] Figure 1It is a graph of the signal intensity of each element using the sputtering time on the horizontal axis and the vertical axis. Relative to the distribution of silver atoms, carbon atoms are present at the interface between air and the coating base layer (B) (ultimately the resin layer (C) side) about 0.5 seconds after the start of sputtering, and it can be seen that there are more carbon atoms. Thereafter, as the sputtering time passes, the carbon atoms decrease. At this time, it is shown that there are relatively few carbon atoms inside the coating base layer (B). If sputtering is further performed, there is an interface between the coating base layer (B) and the temporary support (A) about 16 seconds after the start of sputtering (ultimately the metal coating layer (E) side), and it can be seen that there are more carbon atoms. Therefore, it can be seen that since the carbon atoms derived from the dispersant (b1) are more present at the interface between the air and the coating base layer (B), the functional group possessed by the dispersant (b1) and the functional group [X] possessed by the compound (c1) contained in the resin layer (C) described below reacts easily to form a chemical bond.
[0188] Figure 2 is to Figure 1 Different plating base layers (B) are formed on the temporary support (A). With respect to the distribution of silver atoms, carbon atoms are more present at the interface between the air and the plating base layer (B) (ultimately on the resin layer (C) side) around 1 second after the start of sputtering. Thereafter, even after the sputtering time, the signal intensity of the carbon atoms does not change. The sputtering time at which the signal intensity of the silver atoms decreases is about 21 seconds, which is the interface between the plating base layer (B) and the temporary support (A) (ultimately on the metal plating layer (E) side), and no increase in carbon atoms is observed.
[0189] The above-mentioned plated base layer (B) may be a layer disposed on the entire surface of the above-mentioned temporary support (A), or may be a layer disposed on a portion of the surface of the above-mentioned temporary support (A). The conductive pattern obtained by the above-mentioned plated base layer (B) may be a pattern in which the above-mentioned plated base layer (B) is formed on the entire surface of the above-mentioned temporary support (A), or may be a pattern in which the above-mentioned plated base layer (B) is formed on a portion of the surface. As the above-mentioned plated base layer (B) existing on a portion of the surface of the above-mentioned temporary support (A), specifically, there can be cited: a conductive pattern formed on the surface of the above-mentioned temporary support (A) using a pattern resist, or a conductive pattern in which the plated base layer (B) is formed only on the required portion using a printing method, and after the plated base layer (B) is formed on the entire surface of the above-mentioned temporary support (A), a laser is used to remove (trim) the unnecessary portion, and only the required portion is left, thereby obtaining a conductive pattern, etc.
[0190] The above-mentioned plating base layer (B) contains the conductive material (b2) in an amount of 80% to 99.9% by mass, and contains the above-mentioned dispersant (b1) in an amount of 0.1% to 20% by mass, more preferably in an amount of 0.1% to 10% by mass, based on the entire above-mentioned plating base layer (B).
[0191] As the dispersant (b1) contained in the above-mentioned plating base layer (B), a compound having a basic nitrogen atom group or a phosphate group is used, which reacts with the functional group [X] of the compound (c1) contained in the resin layer (C) described below to form a chemical bond. The above-mentioned basic nitrogen atom group or the above-mentioned phosphate group may react with the above-mentioned functional group [X] partially to form a chemical bond, or may react with the above-mentioned functional group [X] completely to form a chemical bond.
[0192] Examples of the basic nitrogen atom-containing group include an imino group, a primary amino group and a secondary amino group.
[0193] When a compound having a plurality of basic nitrogen atom groups in the molecule is used as the above-mentioned dispersant (b1), in terms of improving the adhesion between the above-mentioned plated base layer (B) and the above-mentioned resin layer (C), it is preferred that one of the above-mentioned basic nitrogen atom groups participates in the bonding with the functional group [X] of the compound (c1) contained in the resin layer (C) described below when forming the above-mentioned plated base layer (B), while the other one contributes to the interaction with the conductive substance (b2) such as silver in the plated base layer (B).
[0194] As for the ability to improve the adhesion of the above-mentioned plating base layer (B) and the following metal plating layer (E) by making the above-mentioned plating base layer (B) porous, the above-mentioned dispersant (b1) having a basic nitrogen group is preferably a polymer dispersant. As the polymer dispersant, polyalkyleneimine such as polyethyleneimine and polypropyleneimine, and a compound formed by adding polyoxyalkylene to the above-mentioned polyalkyleneimine are preferably used. By using a polymer dispersant in the above-mentioned dispersant, the dispersant in the above-mentioned plating base layer (B) can be removed and made porous compared to a low molecular weight dispersant, and its void size can be increased, and voids of nanometer to submicron size can be formed. The metal constituting the following metal plating layer (E) is easily filled into the void, and the filled metal becomes an anchor, which can greatly improve the adhesion of the above-mentioned plating base layer (B) and the following metal plating layer (E).
[0195] When a compound having a phosphate group in the molecule is used as the above-mentioned dispersant (b1), it is preferred to use an acrylic resin that is easy to introduce the phosphate group. When the phosphate group is introduced into the acrylic resin, a monomer having the phosphate group is used as the raw material of the acrylic resin. As a monomer having a phosphate group, for example, 2-((meth)acryloyloxy)ethyl phosphate, 2-((meth)acryloyloxy)propyl phosphate, diphenyl (2-acryloyloxyethyl) phosphate, diphenyl (2-methacryloyloxyethyl) phosphate, phenyl (2-acryloyloxyethyl) phosphate, etc. can be cited.
[0196] In addition, it is preferred to use a functional group [Y] other than the phosphate group in the dispersant (b1) because it can improve the adhesion between the plating base layer (B) and the resin layer (C). For example, the functional group [Y] may include a carboxyl group, an isocyanate group, a blocked isocyanate group, an epoxy group, a hydroxyl group, Oxazoline group, N-methylol group, N-alkoxymethyl group, amino group, alkoxysilyl group, etc. In addition, the said dispersing material (b1) may have two or more types of these functional groups.
[0197] From the viewpoint of further improving the adhesion with the resin layer (C), the content of the functional group [Y] in the dispersing material (b1) is preferably in the range of 0.001 to 5 mmol / g, more preferably in the range of 0.01 to 3 mmol / g, and even more preferably in the range of 0.01 to 2 mmol / g.
[0198] As the conductive material (b2) constituting the above-mentioned plated base layer (B), transition metals or their compounds may be mentioned, among which ionic transition metals are preferred. As the ionic transition metal, copper, silver, gold, nickel, palladium, platinum, cobalt, etc. may be mentioned. Among these, silver or copper is preferred from the perspective of easily forming the following metal plating layer (E), and silver is more preferred from the perspective of reducing the surface resistance of the plated base layer. In addition, magnetic metals such as nickel and cobalt reduce the transmission characteristics required for high-frequency transmission, so silver and copper are preferably used, and silver is more preferred.
[0199] The shape of the conductive material (b2) used to form the above-mentioned plated base layer (B) is preferably particulate or fibrous. In addition, when the conductive material (b2) is a particle, its size is preferably nanometer size. Specifically, from the perspective of making a denser coating and further reducing the resistance value, the average particle size is preferably in the range of 1 to 100 nm, and more preferably in the range of 1 to 50 nm. The average particle size can be measured using "Nanotrac UPA-150" manufactured by Microtrac.
[0200] On the other hand, when the conductive material (b2) is in the form of fibers, the diameter of the fibers is preferably within the range of 5 to 100 nm, more preferably within the range of 5 to 50 nm, in order to obtain a denser coating and further reduce the resistance value. In addition, the length of the fibers is preferably within the range of 0.1 to 100 μm, more preferably within the range of 0.1 to 30 μm.
[0201] The plating base layer (B) can be formed by preparing a fluid containing the dispersant (b1) and the conductive substance (b2) and applying the fluid. The content of the conductive substance (b2) in the fluid is preferably in the range of 1 to 90% by mass, more preferably in the range of 1 to 60% by mass, and further preferably in the range of 1 to 10% by mass.
[0202] As components that may be mixed in the fluid, there may be mentioned a dispersant or solvent for dispersing the conductive material (b2) in a solvent, or, as required, the following surfactants, leveling agents, viscosity modifiers, film-forming aids, defoaming agents, preservatives, and the like.
[0203] In order to disperse the conductive material (b2) in the solvent, a dispersant may be used in combination. Examples of the dispersant include: dodecanethiol, 1-octanethiol, triphenylphosphine, dodecylamine, polyethylene glycol, polyvinyl pyrrolidone, polyethyleneimine, polyvinyl pyrrolidone; fatty acids such as myristic acid, octanoic acid, and stearic acid; polycyclic hydrocarbon compounds having carboxyl groups such as bile acid, glycyrrhizic acid, and rosin acid; polyurethane resins, acrylic resins, and compounds containing phosphoric acid groups in the polyurethane resins or acrylic resins.
[0204] The amount of the dispersant used to disperse the conductive substance (b2) is preferably in the range of 0.01 to 50 parts by mass, more preferably in the range of 0.01 to 10 parts by mass, based on 100 parts by mass of the conductive substance (b2).
[0205] In addition, in order to further improve the adhesion between the above-mentioned plated base layer (B) and the following metal plated layer (E), when the dispersant is removed by sintering to form a porous above-mentioned plated base layer (B), the range is preferably 0.1 to 10 parts by mass, and more preferably 0.1 to 5 parts by mass, relative to 100 parts by mass of the above-mentioned metal particles (c).
[0206] As the solvent used for the above-mentioned fluid, an aqueous medium or an organic solvent can be used. As the above-mentioned aqueous medium, for example, distilled water, ion exchange water, pure water, ultrapure water, etc. can be mentioned. In addition, as the above-mentioned organic solvent, alcohol compounds, ether compounds, ester compounds, ketone compounds, etc. can be mentioned.
[0207] Examples of the alcohol compound include methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, sec-butanol, tert-butanol, heptanol, hexanol, octanol, nonanol, decanol, undecanol, dodecanol, tridecanol, tetradecanol, pentadecyl alcohol, stearyl alcohol, allyl alcohol, cyclohexanol, terpineol, terpineol, dihydroterpineol, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monoethyl ether, diethylene glycol monomethyl ether, diethylene glycol monobutyl ether, tetraethylene glycol monobutyl ether, propylene glycol monomethyl ether, dipropylene glycol monomethyl ether, tripropylene glycol monomethyl ether, propylene glycol monopropyl ether, dipropylene glycol monopropyl ether, propylene glycol monobutyl ether, dipropylene glycol monobutyl ether and tripropylene glycol monobutyl ether.
[0208] Furthermore, in addition to the solvent, ethylene glycol, diethylene glycol, 1,3-butanediol, isoprene glycol, glycerin, and the like may be used in the above-mentioned fluid as necessary.
[0209] As the surfactant, a common surfactant can be used, and examples thereof include di-2-ethylhexyl sulfosuccinate, dodecylbenzenesulfonate, alkyl diphenyl ether disulfonate, alkyl naphthalenesulfonate, and hexametaphosphate.
[0210] As the leveling agent, a common leveling agent can be used, and examples thereof include silicone-based compounds, acetylene glycol-based compounds, and fluorine-based compounds.
[0211] As the viscosity modifier, a common thickener can be used, for example, acrylic polymers or synthetic rubber latex which can be thickened by adjusting to alkalinity, polyurethane resins which can be thickened by aggregating molecules, hydroxyethyl cellulose, carboxymethyl cellulose, methyl cellulose, polyvinyl alcohol, hydrogenated castor oil, amide wax, polyethylene oxide, metal soaps, dibenzylidene sorbitol, etc.
[0212] As the film-forming aid, a common film-forming aid can be used, for example, anionic surfactants (such as dioctyl sodium sulfosuccinate), hydrophobic nonionic surfactants (such as sorbitan monooleate), polyether-modified siloxane, silicone oil, etc.
[0213] As the defoaming agent, a common defoaming agent can be used, and examples thereof include silicone defoaming agents, nonionic surfactants, polyethers, higher alcohols, and polymer surfactants.
[0214] As the preservative, a common preservative may be used, and examples thereof include isothiazolin-based preservatives, triazine-based preservatives, imidazole-based preservatives, pyridine-based preservatives, azole-based preservatives, and pyridinethione-based preservatives.
[0215] The viscosity of the fluid (measured at 25°C using a Brookfield viscometer) is preferably in the range of 0.1 to 500,000 mPa·s, more preferably in the range of 0.2 to 10,000 mPa·s. When the fluid is applied (printed) by the following inkjet printing method, letterpress reverse printing, or the like, the viscosity is preferably in the range of 5 to 20 mPa·s.
[0216] As a method for manufacturing the transfer laminate of the present invention, the following method can be cited: first, a fluid containing a dispersant (b1) and a conductive substance (b2) is coated on a temporary support (A), and the organic solvent contained in the fluid is removed by drying to form a plated base layer (B), and then a fluid containing a compound (c1) having a functional group [X] is coated to form a resin layer (C), and then the basic nitrogen atom-containing group or phosphate group contained in the dispersant (b1) contained in the above-mentioned plated base layer (B) is reacted with the functional group [X] contained in the above-mentioned compound (c1) contained in the above-mentioned resin layer (C) to form a bond.
[0217] Examples of a method for coating or printing the fluid on the temporary support (A) include inkjet printing, reverse printing, screen printing, plate printing, gravure printing, flexible printing, pad printing, spin coating, spray coating, rod coating, extrusion coating, slit coating, roll coating, dip coating, rotary coating, capillary coating, small-diameter gravure coating, and blade roll method.
[0218] The drying temperature after coating or printing the above-mentioned fluid containing the above-mentioned dispersant (b1) and the conductive material (b2) is preferably in the range of 50°C to 400°C, more preferably in the range of 80°C to 340°C, preferably in the range of 120°C to 320°C, preferably in the range of 150°C to 300°C, and further preferably in the range of 180°C to 280°C.
[0219] The above-mentioned drying may or may not be carried out with air supply. In addition, the drying may be carried out in the air, in an environment of replacement with an inert gas such as nitrogen or argon, or under air flow, or in a vacuum. When the plating base layer (B) is a layer of metal nanoparticles dispersed with a dispersant, by drying in the air, the layer of metal nanoparticles can be oxidized to improve the adhesion with the metal plating layer (E) described below. In addition, by drying in the air, the dispersant or surfactant, leveling agent, viscosity modifier, film-forming aid, defoaming agent, preservative, etc. present on the surface of the plating base layer (B) can be oxidized and decomposed, which can reduce the compounds that hinder the adhesion, thereby improving the plating base layer.
[0220] (B) Adhesion with the metal plating layer (E).
[0221] The mass per unit area of the plating base layer (B) is preferably 1 to 30,000 mg / m 2 The range is preferably 1 to 5,000 mg / m 2 When electroless plating is performed on the plating base layer (B), the plating base layer (B) is used as a catalyst, so the film thickness of the plating base layer can be thin, specifically, preferably 1 to 5000 mg / m 2 , preferably 10 to 1000 mg / m 2 , preferably 10 to 500 mg / m 2 , more preferably 50 to 500 mg / m 2 On the other hand, when electrolytic plating is performed on the plating base layer (B), the plating base layer (B) has conductivity and can be low in resistance, so the film thickness can be thicker, preferably 100 to 30,000 mg / m 2 , preferably 100 to 10000 mg / m 2 , preferably 300 to 5000 mg / m 2 In order to improve the adhesion between the metal plating layer (E) and the plating base layer (B) and to make the expensive plating base layer (B) thinner and reduce the cost, the preferred concentration is 500 to 2000 mg / m 2 .
[0222] In order to form electrolytic plating uniformly, the surface resistance of the above-mentioned plating base layer (B) when electrolytic plating is performed on the above-mentioned plating base layer (B) is preferably low resistance. The surface resistance is preferably in the range of 0.1 to 10000Ω / □, more preferably in the range of 0.15 to 1000Ω / □, more preferably in the range of 0.15 to 500Ω / □, more preferably in the range of 0.2 to 100Ω / □, more preferably in the range of 0.2 to 10Ω / □, and further preferably in the range of 0.2 to 5Ω / □.
[0223] Next, the resin layer (C) will be described.
[0224] The resin layer (C) is a layer provided to increase the ratio of the transferable area (transfer rate) when the transfer laminate is bonded to the support (D) to transfer the plated base layer (B) and to improve the adhesion between the plated base layer (B) and the support (D).
[0225] The resin layer (C) is formed by applying a composition (c1-1) containing a compound (c1) having a functional group [X] on the surface of the plated base layer (B) and drying the coating film (c). The functional group [X] of the compound (c1) present in the coating film (c) reacts with the basic nitrogen atom-containing group or phosphate group of the dispersant (b1) contained in the plated base layer (B) to form a chemical bond. The reaction proceeds to form a chemical bond at room temperature, but the reaction can be further accelerated by heating to form a chemical bond.
[0226] As a result, the adhesion at the interface between the plated base layer (B) and the resin layer (C) is improved, and when the transfer laminate is attached to the support (D) and the temporary support (A) of the transfer laminate is peeled off, the plated base layer (B) and the resin layer (C) are not easily peeled off. In addition, in the structure in which the resin layer (C) and the plated base layer (B) are stacked on the support (D), a conductive pattern with excellent adhesion that will not peel off over time can be obtained.
[0227] The coating film (c) which can be referred to as a precursor of the resin layer (C) is a film formed by coating a composition containing a compound (c1) having a functional group [X] on the surface of a support and drying the composition. The compound (c1) contained in the coating film (c) has a functional group [X] that reacts with a basic nitrogen atom-containing group or a phosphate ester group of the dispersant (b1) contained in the plating base layer (B).
[0228] As the functional group [X] that reacts with the basic nitrogen atom-containing group, ketone group, epoxy group, carboxylic acid group, carboxylic anhydride group, alkyl alcohol amide, isocyanate group, vinyl group, halogenated alkyl group, acryloyl group, cyanamide group, urea group (urea bond), acyl halide group, etc., one or more functional groups selected from these can be used. The ketone group refers to a carbonyl group derived from ketone. From the viewpoint of preventing the reaction at room temperature, the isocyanate group can also be sealed with a blocking agent.
[0229] Among them, as the functional group [X], from the viewpoint of preventing the formation of by-products such as halogen, acid, amine, etc. when reacting with the basic nitrogen atom-containing group of the above-mentioned compound (b1), it is preferred to use one or more selected from the group consisting of an epoxy group, a ketone group, a carboxylic acid group, a carboxylic anhydride group, an alkyl alcohol amide and an isocyanate group.
[0230] As the functional group [X] that reacts with the phosphate group, an epoxy group, an amino group, etc. can be mentioned, and one or more functional groups selected from these can be used. In addition, when the functional group [Y] is contained, as the functional group that reacts with the functional group [Y], for example, a carboxyl group, an isocyanate group, a blocked isocyanate group, an epoxy group, a hydroxyl group, The above-mentioned functional groups may be oxazoline, N-methylol, N-alkoxymethyl, amino, alkoxysilyl, etc. In addition, the above-mentioned resin (a1) may have two or more of these functional groups. Furthermore, the above-mentioned carboxyl group may also be derived from an acid anhydride. In addition, the above-mentioned amino group may be any one of primary to tertiary amino groups.
[0231] The functional group [X] is preferably present in an amount of 50 mmol / kg to 10,000 mmol / kg, more preferably 100 mmol / kg to 8,000 mmol / kg, relative to the entire resin layer (C). In order to further improve adhesion, 100 mmol / kg to 5,000 mmol / kg is more preferred.
[0232] As the above-mentioned resin layer (C), for example, polyurethane resin, acrylic resin, core-shell composite resin using polyurethane resin as shell and acrylic resin as core, epoxy resin, phenoxy resin, imide resin, amide resin, melamine resin, phenolic resin, urea-formaldehyde resin, blocked isocyanate polyvinyl alcohol, polyvinyl pyrrolidone etc. obtained by reacting end-capping agents such as phenol with polyisocyanate etc. can be cited. In addition, the core-shell composite resin using polyurethane resin as shell and acrylic resin as core is obtained by, for example, polymerizing acrylic monomer in the presence of polyurethane resin. In addition, these resins can be used in one kind, or two or more kinds can be used in combination.
[0233] Among the resins forming the above-mentioned resin layer (C), a resin containing aminotriazine-modified novolac resin is preferably used. The phenolic hydroxyl group (functional group [X]) of the aminotriazine novolac resin forms an ionic bond with the basic nitrogen atom-containing group contained in the plating base layer (B) by an acid-base reaction, thereby improving the adhesion of the interface between the plating base layer (B) and the resin layer (C).
[0234] The aminotriazine modified novolac resin is a novolac resin in which an aminotriazine structure and a phenol structure are bonded via a methylene group. The aminotriazine modified novolac resin is obtained, for example, by reacting an aminotriazine compound such as melamine, benzoguanamine, methylguanamine, phenolic compounds such as phenol, cresol, butylphenol, bisphenol A, phenylphenol, naphthol, resorcinol, and formaldehyde in the presence of a weakly alkaline catalyst such as an alkylamine or in the absence of a catalyst at near neutrality by co-condensation reaction, or by reacting an alkyl etherified product of an aminotriazine compound such as methylated melamine with the phenolic compound.
[0235] The aminotriazine-modified novolac resin is preferably a resin having substantially no methylol group. In addition, the aminotriazine-modified novolac resin may also contain molecules having an aminotriazine structure generated as a by-product when the aminotriazine-modified novolac resin is produced and bonded to methylene groups only, molecules having a phenol structure and bonded to methylene groups only, etc. Furthermore, a certain amount of unreacted raw materials may also be contained.
[0236] Examples of the phenol structure include phenol residues, cresol residues, butylphenol residues, bisphenol A residues, phenylphenol residues, naphthol residues, and resorcinol residues. In addition, the residue here refers to a structure remaining after at least one hydrogen atom bonded to a carbon of an aromatic ring is detached. For example, in the case of phenol, it refers to a hydroxyphenyl group.
[0237] Examples of the triazine structure include structures derived from aminotriazine compounds such as melamine, benzoguanamine and methylguanamine.
[0238] The phenol structure and the triazine structure may be used in one kind or in combination of two or more kinds. In addition, in order to further improve the adhesion, the phenol structure is preferably a phenol residue, and the triazine structure is preferably a structure derived from melamine.
[0239] The hydroxyl value of the aminotriazine-modified novolac resin is preferably 50 to 200 mg KOH / g, more preferably 80 to 180 mg KOH / g, and even more preferably 100 to 150 mg KOH / g in order to further improve adhesion.
[0240] The aminotriazine-modified novolac resin may be used alone or in combination of two or more.
[0241] When an aminotriazine-modified novolac resin is used as the compound having an aminotriazine, it is preferred to use an epoxy resin in combination.
[0242] Examples of the epoxy resin include bisphenol A epoxy resin, bisphenol F epoxy resin, biphenyl epoxy resin, cresol novolac epoxy resin, phenol novolac epoxy resin, bisphenol A novolac epoxy resin, alcohol ether epoxy resin, tetrabromobisphenol A epoxy resin, naphthalene epoxy resin, phosphorus-containing epoxy compounds having a structure derived from 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivatives, epoxy resins having a structure derived from dicyclopentadiene derivatives, epoxides of fats and oils such as epoxidized soybean oil, etc. These epoxy resins may be used alone or in combination of two or more.
[0243] Among the above epoxy resins, bisphenol A epoxy resin, bisphenol F epoxy resin, biphenyl epoxy resin, cresol novolac epoxy resin, phenol novolac epoxy resin, bisphenol A novolac epoxy resin are preferred because they can further improve adhesion, and bisphenol A epoxy resin is particularly preferred. Since the epoxy group (functional group [X]) of the epoxy resin reacts with the basic nitrogen atom-containing group contained in the plating base layer (B) to form a covalent bond, the adhesion of the interface between the plating base layer (B) and the resin layer (C) is improved.
[0244] In order to further improve the adhesion, the epoxy equivalent of the epoxy resin is preferably in the range of 100 to 300 g / equivalent, more preferably in the range of 120 to 250 g / equivalent, and even more preferably in the range of 150 to 200 g / equivalent.
[0245] When the resin layer (C) is made into a layer containing an aminotriazine-modified novolac resin and an epoxy resin, the molar ratio [(x) / (y)] of the phenolic hydroxyl group in the aminotriazine-modified novolac resin to the epoxy group in the epoxy resin is preferably in the range of 0.1 to 5, more preferably in the range of 0.2 to 3, and even more preferably in the range of 0.3 to 2, in order to further improve the adhesion.
[0246] In order to promote the reaction of the aminotriazine modified phenolic novolac resin and the epoxy resin, a curing accelerator may also be used. As the curing accelerator, for example, an amine compound having a primary, secondary or tertiary amino group may be cited. In addition, as the amine compound, any of aliphatic, alicyclic, and aromatic may be used. In addition, as the curing accelerator, thiols, acid anhydrides, acid boron fluorides, boric acid esters, organic acid hydrazides, Lewis acids, organometallic compounds, onium salts, cationic compounds, etc. may also be used.
[0247] In addition, it is preferred to use a compound containing a phenoxy resin. The resin layer (C) has the function of improving the adhesion between the support (D) and the plated base layer (B) as described below. In the present invention, the phenoxy resin preferably uses a resin with a weight average molecular weight in the range of 10,000 to 100,000. By using a high molecular weight phenoxy resin for the resin layer (C), the elongation of the polymer is increased, and then the elastic modulus is increased, so that the surface of the resin layer (C) is thermally pressed onto the support (A) using a transfer laminate, and the transfer rate of the above-mentioned plated base layer (B) after the temporary support (A) is peeled off is improved. In addition, the adhesion between the support (D) and the metal plating layer (E) can be improved. Furthermore, by using a high molecular weight phenoxy resin, the decomposition of the polymer caused by heat in the long-term heat resistance test can be suppressed, so that even after the long-term heat resistance test, the adhesion of the metal plating layer (E) can be maintained.
[0248] Phenoxy resin is a polyhydroxy polyether obtained by reacting a dihydric phenol compound with epichlorohydrin or reacting a divalent epoxy compound with a dihydric phenol compound. As the dihydric phenol compound, bisphenols can be cited. As phenoxy resin, for example, phenoxy resins with bisphenol A structure (skeleton), phenoxy resins with bisphenol F structure, phenoxy resins with bisphenol S structure, phenoxy resins with bisphenol M structure, phenoxy resins with bisphenol P structure, phenoxy resins with bisphenol Z structure, etc. can be cited. In addition, phenoxy resins with skeleton structures such as novolac structure, anthracene structure, fluorene structure, dicyclopentadiene structure, norbornene structure, naphthalene structure, biphenyl structure, adamantane structure, etc. can be cited. These phenoxy resins can be used alone, or two or more can be mixed and used. Among these, preferably the resin with bisphenol structure, more preferably bisphenol A skeleton, bisphenol F skeleton, bisphenol S skeleton. In addition, the end of the phenoxy resin can also be any functional group such as phenolic hydroxyl group, epoxy group.
[0249] In the present invention, the weight average molecular weight of the phenoxy resin used is preferably in the range of 10,000 to 100,000. If the molecular weight is 10,000 or more, the coating adhesion after the long-term heat resistance test is improved. In addition, if the molecular weight is 100,000 or less, the solubility in organic solvents is improved, and the viscosity of the coating liquid when forming the resin layer (C) is appropriate, so the operability is good. The preferred weight average molecular weight of the phenoxy resin is 20,000 to 80,000, and more preferably 22,000 to 50,000. In addition, the weight average molecular weight of the phenoxy resin can be adjusted by the molar ratio of the epoxy resin to the phenolic resin or the reaction time in the above reaction. In addition, in this specification, the weight average molecular weight adopts the value obtained by measuring with the following gel permeation chromatography (GPC) and converted to standard polystyrene. The GPC measurement was performed using a high-efficiency GPC device (HLC-8420GPC, manufactured by Tosoh Corporation) as a measurement device, and a column was used by connecting TSKgelG5000HxL / G4000HxL / G3000HxL / G2000HxL (manufactured by Tosoh Corporation) in series, tetrahydrofuran was used as an eluent, and the measurement was performed using an RI detector. In addition, phenoxy resin generally refers to a high molecular weight epoxy resin, but in this specification, "epoxy resin" refers to an epoxy resin having a weight average molecular weight of less than 10,000, which is different from the above-mentioned phenoxy resin.
[0250] As the phenoxy resin, commercially available epoxy resins can be used, for example, 1256, 1255HX30 (both phenoxy resins containing a bisphenol A skeleton), 4250, 4275 (bisphenol A / bisphenol F mixed type), YL6794, YL7213, YL7290, YL7482, YL7553, YX8100 (phenoxy resins containing a bisphenol S skeleton), X6954 (phenoxy resins containing a bisphenol acetophenone skeleton) manufactured by Mitsubishi Chemical Corporation. Resin), YX7200 (phenoxy resin containing cyclohexane skeleton), YP-70 (bisphenol F type phenoxy resin) manufactured by Nippon Steel Chemical & Materials Co., Ltd., ZX356-2 (phenoxy resin containing bisphenol A and bisphenol F skeletons), YPB-40PXM40 (phenoxy resin containing bromine), ERF-001M30 (phenoxy resin containing phosphorus), FX-280, FX-293, FX-310 (phenoxy resin containing fluorene skeleton), PKHA, PKHB, PKHB+, PKHC, PKHH, PKHJ, PKFE, etc. manufactured by Gabriel Phenoxies.
[0251] In the present invention, it is preferred that the resin layer (C) contains an epoxy resin in combination with the phenoxy resin. By using a phenoxy resin and an epoxy resin in combination, the adhesion of the plating layer in normal conditions and after a long-term heat resistance test is further improved.
[0252] Examples of the epoxy resin include bisphenol A epoxy resin, bisphenol F epoxy resin, biphenyl epoxy resin, cresol novolac epoxy resin, phenol novolac epoxy resin, bisphenol A novolac epoxy resin, alcohol ether epoxy resin, tetrabromobisphenol A epoxy resin, naphthalene epoxy resin, phosphorus-containing epoxy compounds having a structure derived from 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide derivatives, epoxy resins having a structure derived from dicyclopentadiene derivatives, epoxides of fats and oils such as epoxidized soybean oil, etc. These epoxy resins may be used alone or in combination of two or more.
[0253] As the epoxy resin used in combination with the phenoxy resin, from the viewpoint of further improving the adhesion of the metal plating layer (E) described below, preferably, an aromatic epoxy resin such as bisphenol A epoxy resin, bisphenol F epoxy resin, biphenyl epoxy resin, cresol novolac epoxy resin, phenol novolac epoxy resin, bisphenol A novolac epoxy resin is preferred; liquid epoxy resins are more preferred, and bisphenol A epoxy resin is particularly preferred.
[0254] The epoxy equivalent of the epoxy resin is preferably 100 to 5,000 g / equivalent, more preferably 120 to 2,000 g / equivalent, and even more preferably 120 to 250 g / equivalent in order to further improve the adhesion.
[0255] When the resin layer further contains an epoxy resin in addition to the phenoxy resin, the blending ratio of the phenoxy resin to the epoxy resin is preferably 90:10 to 10:90, more preferably 85:15 to 15:80, based on mass.
[0256] In addition, in the present invention, when a phenoxy resin is used for the resin layer (C), the epoxy group at the end of the phenoxy resin reacts with the basic nitrogen atom group contained in the plating base layer (B), so that the adhesion of the interface between the plating base layer (B) and the resin layer (C) is improved. In addition, the phenoxy resin may be used in combination with other resins.
[0257] The resin layer (C) formed by the above-mentioned heating step may also have a
[0258] The functional group [X] in (b1) partially remains after the reaction of the basic nitrogen atom-containing group or the phosphate ester group.
[0259] As described above, the resin layer (C) needs to be heated to react the basic nitrogen atom-containing group or phosphate group contained in the plated base layer (B) with the functional group [X] contained in the resin layer (C), and the dried resin layer (C) may be completely cured or semi-cured. The conductive pattern is formed on the support (D) by laminating the surface of the resin layer (C) of the following transfer laminate to the support (D) and peeling off the temporary support (A) of the transfer laminate. Therefore, in order to ensure the adhesion with the support (D), the resin layer (C) is preferably semi-cured.
[0260] The resin layer (C) may be arranged on a part or all of the plated base layer (B) present on the surface of the temporary support layer (A), or may be arranged on one side or both sides of the temporary support (A). For example, when a conductive pattern is to be formed on the surface of the following support (D), a resin layer (C) may be used on the entire surface of the temporary support (A), and only the plated base layer (B) may be provided in the required portion of the resin layer (C). In addition, a conductive pattern may be provided in which the resin layer (C) is provided only in the portion where the plated base layer (B) is provided on the surface of the temporary support (A).
[0261] The resin layer (C) may be one layer or two or more layers. When two or more resin layers (C) are formed, for example, the layer close to the plated base layer can improve the adhesion with the plated base layer (B), and on the other hand, the resin layer (C) finally close to the support (D) can improve the adhesion with the support (D). In addition, the first resin layer (C) close to the plated base layer (B) becomes a layer close to the plated base layer (B) or the metal plated layer (E) described below, and when forming a conductive pattern, it becomes a portion close to the copper wiring, so in order to improve the insulation reliability, the resin composition of the resin layer (C) can be selected and formed.
[0262] In addition, the coating of the resin layer (C) is applied to the surface of the plating base layer (B) formed on the surface of the temporary support (A), and therefore, in order to obtain a viscosity that is easy to apply, it is preferably mixed with an organic solvent. Examples of the organic solvent include toluene, ethyl acetate, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, isopropyl alcohol, diacetone alcohol, ethylene glycol, toluene, and the like. One of these solvents may be used, or two or more of them may be used in combination.
[0263] The amount of the organic solvent used is preferably appropriately adjusted depending on the coating method used when coating the plating base layer (B) and the film thickness required for the resin layer (C).
[0264] Furthermore, known additives such as a film-forming aid, a leveling agent, a tackifier, a water-repellent, a defoaming agent, and an antioxidant may be appropriately added to the coating material of the resin layer (C) as needed.
[0265] The resin layer (C) can be formed by coating a part or all of the plating base layer (B) formed on the surface of the temporary support (A) with the resin layer (C) and removing the organic solvent contained in the coating of the resin layer (C).
[0266] Examples of a method for applying the coating material for the resin layer (C) include inkjet printing, reverse printing, screen printing, plate printing, gravure printing, flexographic printing, pad printing, spin coating, spray coating, rod coating, extrusion coating, slit coating, roll coating, dip coating, rotary coating, capillary coating, small-diameter gravure coating, and doctor roll method.
[0267] After the coating of the resin layer (C) is applied to the surface of the plating base layer (B) formed on the surface of the temporary support (A), the method of removing the organic solvent contained in the coating layer is, for example, usually a method of drying it using a dryer to volatilize the organic solvent. The drying temperature needs to be set to a temperature in the following range: the organic solvent used can be volatilized without causing adverse effects such as thermal deformation on the support (A), and the functional group [X] contained in the resin layer (C) reacts with the basic nitrogen atom-containing group or the phosphate group contained in the plating base layer (B) as described above.
[0268] The drying temperature of the resin layer (C) is preferably in the range of 50°C to 400°C, more preferably in the range of 80°C to 340°C, preferably in the range of 120°C to 280°C, and further preferably in the range of 150°C to 200°C.
[0269] The film thickness of the above-mentioned resin layer (C) varies depending on the application, and is preferably in a range that further improves the adhesion between the above-mentioned resin layer (C) and the following support (D). The film thickness of the above-mentioned resin layer (C) is preferably in the range of 10nm to 30μm, more preferably in the range of 50nm to 1μm, more preferably in the range of 100nm to 800nm, and further preferably in the range of 200nm to 500nm.
[0270] In the laminate after the surface of the resin layer (C) of the following transfer laminate is attached to the support (D) and the temporary support (A) is peeled off, the surface of the above-mentioned resin layer (C) can also be pre-treated by a dry treatment method such as a corona discharge treatment method, a plasma discharge treatment method, an ultraviolet treatment method, or a wet treatment method using water or an acidic or alkaline agent, an organic solvent, etc., in order to further improve the adhesion between the above-mentioned resin layer (C) and the support (D).
[0271] Next, the support (D) will be described.
[0272] The support (D) becomes a substrate for forming a conductive pattern, and therefore needs to be changed according to the application of a printed wiring board, a flexible printed wiring board, a rigid printed wiring board, a package substrate, a ceramic substrate, a glass substrate, a silicon wafer substrate, a metal substrate, an electromagnetic wave shielding film, or a molded circuit substrate.
[0273] Examples of the material of the support (D) include polyimide resins, modified polyimide resins (MPI), polyamideimide resins, polyamide resins, polyethylene terephthalate resins, polybutylene terephthalate resins, polyethylene naphthalate resins, polycarbonate resins, acrylonitrile-butadiene-styrene (ABS) resins, polyarylate resins, polyacetal resins, acrylic resins such as poly(methyl)acrylate, polyvinylidene fluoride resins, polytetrafluoroethylene resins, polyvinyl chloride resins, polyvinylidene chloride resins, vinyl chloride resins obtained by graft copolymerization of acrylic resins, polyvinyl alcohol resins, polyethylene resins, polypropylene resins, and the like. Olefin resin, polyurethane resin, cycloolefin resin, polystyrene, liquid crystal polymer (LCP), polyetheretherketone (PEEK) resin, polyphenylene sulfide (PPS), polyphenylene sulfone (PPSU), polyphenylene ether (PPE), bismaleimide-triazine resin (BT resin), fluororesin composite polyimide resin (a film having a fluororesin layer formed on the surface of a polyimide resin), thermoplastic polyimide resin composite polyimide resin (a film having a thermoplastic polyimide resin layer formed on the surface of a polyimide resin), cellulose nanofiber, silicon, silicon carbide, gallium nitride, sapphire, ceramics, glass, diamond-like carbon (DLC), alumina, etc.
[0274] In addition, as the support (D), a resin substrate containing a thermosetting resin and an inorganic filler can also be preferably used. Examples of the thermosetting resin include epoxy resins, phenolic resins, unsaturated imide resins, cyanate resins, isocyanate resins, benzoic acid resins, and the like. Oxazine resin, oxetane resin, amino resin, unsaturated polyester resin, allyl resin, dicyclopentadiene resin, silicone resin, triazine resin, melamine resin, liquid crystal polymer (LCP), polyetheretherketone (PEEK) resin, polyphenylene sulfide (PPS), polyphenylene sulfone (PPSU), polyphenylene ether (PPE), etc. On the other hand, as the above-mentioned inorganic filler, for example, silica, alumina, talc, mica, aluminum hydroxide, magnesium hydroxide, calcium carbonate, aluminum borate, borosilicate glass, etc. can be cited. These thermosetting resins and inorganic fillers can be used in one kind respectively, or in combination of two or more kinds.
[0275] In addition, the inorganic filler may be in the form of powder, flake, fiber, or the like.
[0276] As the form of the above-mentioned support (D), any one of a planar flexible material, a rigid material, and a rigid-flexible material can be used. More specifically, for the above-mentioned support (D), commercially available materials formed into a film, a sheet, or a plate can be used, and a material formed into a planar shape by a solution, a melt, or a dispersion of the above-mentioned resin can also be used. In addition, the above-mentioned support (D) can be a substrate of a material having the above-mentioned resin formed on a conductive material such as a metal, or a substrate of a material having the above-mentioned resin formed by stacking on a printed circuit board having a circuit pattern. As a stacking method, if the above-mentioned support (D) is a semi-cured support such as a prepreg, it can be attached to the printed circuit board having a circuit pattern by heat and pressure, and if it is a fully cured support (D), it can be stacked using an adhesive sheet such as a bonding sheet.
[0277] In the case of a flexible circuit board, polyimide resin, modified polyimide resin (MPI), transparent polyimide, polytetrafluoroethylene resin, cycloolefin resin, polystyrene, liquid crystal polymer (LCP), polyphenylene sulfide (PPS), polyamide, fluororesin composite polyimide resin (a film having a fluororesin layer formed on the surface of a polyimide resin, a multilayer film in which a polyimide resin and a fluororesin are alternately stacked), thermoplastic polyimide resin composite polyimide resin (a film having a thermoplastic polyimide resin layer formed on the surface of a polyimide resin), etc. can be used.
[0278] When the support (D) is in the form of a film or a sheet, the thickness is not particularly limited, but is generally about 1 to 5,000 μm, more preferably 1 to 500 μm, and even more preferably 1 to 200 μm in consideration of flexibility and bendability.
[0279] In the case of rigid circuit boards, composite substrates of glass fiber and epoxy resin (glass epoxy resin, FR-4, FR-5), composite substrates of paper and epoxy resin (FR-3), composite substrates of glass non-woven fabric and epoxy resin (CEM-3), composite substrates of paper, glass non-woven fabric and epoxy resin (CEM-1), composite substrates of paper and phenolic resin (paper phenolic resin, FR-1, FR-2), composite substrates of glass fiber and PPE resin (such as MEGTRON6 made by Panasonic) can be used. , bismaleimide-triazine resin (BT resin), a composite substrate of silica and epoxy resin (for example, a deposition film manufactured by Ajinomoto Co., Ltd.), polyimide, liquid crystal polymer, polyetheretherketone, polyphenylene sulfide, polystyrene, polycarbonate, polyester resin, polypropylene, polyethylene, acrylic resin, polyurethane resin, cycloolefin polymer, glass, silicon, silicon carbide, gallium nitride, gallium oxide, sapphire, ceramics, alumina ceramics, alumina, glass, diamond-like carbon, aluminum, stainless steel, copper, silver, gold, iron, nickel, etc.
[0280] Examples of the support (D) include synthetic fibers such as polyester fibers, polyamide fibers and polyaramid fibers, inorganic fibers such as carbon fibers, and natural fibers such as cellulose nanofibers.
[0281] In a printed circuit board that requires high-frequency transmission, the surface of the support (D) is preferably smooth. In communications performed by the fifth generation mobile communication system (5G) or millimeter waves, in order to achieve high-speed communication, the frequency of the alternating current becomes higher. The higher the frequency, the more the skin effect of the surface layer of the copper wiring will be generated. Therefore, if the surface roughness of the copper wiring through which the current flows is larger, it will become a resistor and cause the transmission loss to increase. Therefore, the surface of the support (D) is preferably smooth, and the surface roughness (maximum height Sz) when measured by a laser microscope is preferably in the range of 0.001 to 30 μm, preferably in the range of 0.01 to 20 μm, and more preferably in the range of 0.05 to 10 μm. In addition, the surface roughness (maximum height Sz) refers to the value measured by the evaluation method described in ISO 25178, which represents the distance from the highest point to the lowest point on the surface.
[0282] As a method for smoothing the support (D), there are methods for physically smoothing the surface of the support (D) and methods for smoothing it by chemical treatment. As a method for physically smoothing it, examples include rolling processing, cutting processing, grinding processing, grinding with abrasive grains, electrical discharge processing, laser processing, water jet processing, etc., in which the support (D) is passed between smooth rollers to make the surface smooth. In addition, as a method for smoothing it by chemical treatment, examples include electrolytic grinding, etching grinding, etc.
[0283] In addition, when the support (D) is an uncured or semi-cured thermosetting resin or thermoplastic resin, a smoothing treatment can be performed by the following method: a smooth copper foil or aluminum foil or other metal foil, a smooth polyimide film or a fluororesin film or other heat-resistant film is used as a smoothing treatment substrate, and the smooth surface is bonded to the surface of the support (D) by thermal compression bonding, and then peeled off to transfer the smooth surface to the surface of the support (D). In particular, when the support (D) is a rigid substrate substrate containing a thermosetting resin such as an epoxy resin or a polyphenylene ether resin and glass fiber or an inorganic filler, the smooth surface of the copper foil can be thermally compressed to the substrate by applying pressure, and then the copper foil is etched with cupric chloride or ferric chloride to remove the copper foil and smooth the surface of the substrate. The surface roughness of the above-mentioned smoothing treatment substrate affects the surface roughness of the support (D) to be finally made smooth. Therefore, the surface roughness of the smoothing treated substrate is preferably smooth, and the surface roughness (maximum height Sz) when measured by a laser microscope is preferably in the range of 0.001 to 30 μm, preferably in the range of 0.01 to 20 μm, and more preferably in the range of 0.05 to 10 μm. In addition, the surface roughness (maximum height Sz) refers to the value measured by the evaluation method described in ISO 25178, which represents the distance from the highest point to the lowest point on the surface.
[0284] The surface of the support (D) is formed by laminating the surface of the resin layer (C) of the following transfer laminate to the support (D), and after peeling off the temporary support (A) of the transfer laminate, a laminate having a resin layer (C) and a plated base layer (B) is formed on the surface of the above-mentioned support (D). In order to further improve the adhesion between the resin layer (C) and the support (D), the above-mentioned support (D) may be provided with fine concavoconvexities to a degree that does not damage the smoothness, or surface treatment may be performed to introduce functional groups such as hydroxyl, carbonyl, and carboxyl groups. For example, dry treatment such as plasma discharge treatment such as corona discharge treatment, ultraviolet treatment, and wet treatment using aqueous solutions such as water, acid, and alkali or organic solvents may be mentioned.
[0285] Next, a method for transferring the transfer laminate to the support (D) will be described.
[0286] As the transfer method, a method of laminating the surface of the resin layer (C) of the transfer laminate to the support (D) using heat and pressure can be used. There are no particular limitations, and examples thereof include heat lamination, solventless lamination, extrusion lamination, wet lamination, hot roll transfer, in-mold transfer, pressurization, vacuum pressurization, and water pressure transfer.
[0287] When the support (D) is a flexible material and a roll film, it is preferred to use a heat lamination method, a solvent-free lamination method, an extrusion lamination method, or a wet lamination method. From the perspective of being particularly easy to handle, a heat lamination method is more preferred. On the other hand, when the support (D) is a rigid material, it is often necessary to perform heat compression bonding piece by piece, so it is preferred to use a pressurization method or a vacuum pressurization method.
[0288] Regarding the thermal compression bonding conditions, the heating conditions are preferably in the range of 50° C. to 400° C., more preferably in the range of 80° C. to 350° C., more preferably in the range of 80° C. to 280° C., more preferably in the range of 100° C. to 200° C., and more preferably in the range of 120 to 180° C. As the pressure conditions, the range of 0.05 MPa to 35 MPa is preferred, the range of 0.3 MPa to 20 MPa is more preferred, and the range of 0.3 MPa to 20 MPa is more preferred.
[0289] As for the processing time of heat pressing, in the case of heat lamination, since heat pressing is performed by the linear pressure of the roller while conveying, the processing is performed within 1 second. On the other hand, in the case of pressurization or vacuum pressurization, the processing time is preferably in the range of 1 second to 120 minutes, preferably in the range of 30 seconds to 60 minutes, more preferably in the range of 30 seconds to 15 minutes, and from the viewpoint of productivity, it is preferably processed in the range of 1 minute to 5 minutes.
[0290] In addition, when hot pressing is performed, air will enter between the transfer laminate and the support (D), or the gas generated from the support (D) or the transfer laminate will gather between the transfer laminate and the support (D), resulting in a reduction in the transfer rate, so it is preferred to use vacuum pressurization to perform hot pressing under vacuum. As vacuum conditions, as absolute pressure, it is preferably 100 hPa or less, more preferably 50 hPa or less, and more preferably 13 hPa or less. The heating conditions or pressure conditions are preferably treated under the same conditions as above.
[0291] Next, a method of bonding the surface of the resin layer (C) of the transfer laminate to the support (D) and peeling the temporary support (A) will be described.
[0292] The method of peeling the temporary support (A) is not particularly limited. When the adhesion between the support (D) and the resin layer (C) is low during the above-mentioned thermocompression bonding (temporary bonding state), there is a situation where the resin layer (C) and the plated base layer (B) will not be fully transferred to the support (D), and a part of it will remain on the side of the transfer laminate, so the peeling direction and speed of the temporary support (A) during peeling become very important. Specifically, relative to the support (D), it is preferably peeled in the direction of 90 to 180 degrees, preferably peeled in the range of 120 to 180 degrees, and preferably peeled in the direction of 150 to 180 degrees. When peeling, it is preferred that the support (D) side is not peeled off, but the temporary support (A) side is peeled off at the above angle. The peeling speed is preferably in the range of 0.01m / minute to 20m / minute, more preferably in the range of 0.05 to 10m / minute, and more preferably in the range of 0.5 to 5m / minute.
[0293] Next, the post-treatment of the laminate after bonding the surface of the resin layer (C) of the transfer laminate to the support (D) and then peeling off the temporary support (A) of the transfer laminate will be described.
[0294] As described above, in order to achieve low resistance of the plated base layer or completely cure the semi-cured resin layer (C), the functional group [X] of the compound (c1) contained in the resin layer (C) reacts with the basic nitrogen atom-containing group or phosphate group of the above-mentioned dispersant (b1) contained in the plated base layer (B) to form a bond. In addition, heat treatment may be performed to further improve the adhesion between the support (D) and the resin layer (C). As heat treatment conditions, it is preferably in the range of 80°C to 400°C, more preferably in the range of 100°C to 350°C, more preferably in the range of 120°C to 325°C, and more preferably in the range of 150°C to 300°C. As heat treatment time, it is preferably in the range of 1 second to 168 hours, more preferably in the range of 30 seconds to 72 hours, and from the viewpoint of productivity, it is more preferably in the range of 1 minute to 30 minutes.
[0295] In the subsequent process, in order to form the following metal plating layer (E) or pattern resist on the surface of the plating base layer (B), it is preferred to implement a cleaning process that cleans the components that reduce these adhesions. As a component that reduces adhesion, for example, when the temporary support (A) is a resin film, there is an oligomer component that is present in the film and overflows to the surface of the film, when the temporary support (A) is formed with a release layer, there is a part of the component of the release agent that will migrate to the component of the plating base layer (B), and when the temporary support (A) is a metal, there is a film of a metal oxide on the temporary support. As the above-mentioned cleaning process, organic matter present on the surface of the plating base layer (B) can be exemplified by oxidative decomposition by heating, plasma discharge treatment such as corona discharge treatment, dry treatment such as ultraviolet treatment, wet treatment using aqueous solutions such as water, acid, alkali, water containing ozone (ozone nanobubbles) or organic solvents, etc.
[0296] The metal plating layer (E) constituting the laminate of the present invention is provided for the purpose of forming a highly reliable wiring pattern that does not break for a long time and can maintain good electrical conductivity when the laminate is used in a printed wiring board or the like.
[0297] In addition, when the above-mentioned metal plating layer (E) is formed on the entire surface of the above-mentioned plated base layer (B) on the above-mentioned support (D), the metal plating layer (E) is also formed on the entire surface of the above-mentioned support (D). On the other hand, when the plated base layer (B) exists in a part of the above-mentioned support (D), the metal plating layer (E) is formed only on the part of the plated base layer (B).
[0298] The metal plating layer (E) is a layer formed on the plating base layer (B). As a method for forming the metal plating layer (E), a dry plating method or a wet plating method can be used. As a dry plating method, a metal evaporation method or a metal sputtering method can be cited. In addition, the wet plating method can exemplify an electrolytic plating method, an electroless plating method, etc. In order to easily form the metal plating layer (E), a wet plating method is preferably used. In addition, two or more of these plating methods can also be combined. For example, electrolytic plating can also be performed after electroless plating to form the metal plating layer (E). When the plating base layer (B) is conductive, in order to reduce the plating cost when forming a conductive pattern, it is preferred to directly electrolytically plate the plating base layer (B).
[0299] The electroless plating method is, for example, a method of bringing an electroless plating solution into contact with the metal constituting the plating base layer (B) to precipitate a metal such as copper contained in the electroless plating solution to form an electroless plating layer (film) composed of a metal film.
[0300] Examples of the electroless plating solution include an electroless plating solution containing a metal such as copper, silver, gold, nickel, chromium, cobalt, or tin, a reducing agent, and a solvent such as an aqueous medium or an organic solvent.
[0301] Examples of the reducing agent include dimethylaminoborane, hypophosphorous acid, sodium hypophosphite, dimethylamine borane, hydrazine, formaldehyde, sodium borohydride, and phenol.
[0302] In addition, as the above-mentioned electroless plating solution, an electroless plating solution containing the following complexing agents can be used as needed: monocarboxylic acids such as acetic acid and formic acid; dicarboxylic acid compounds such as malonic acid, succinic acid, adipic acid, maleic acid, and trans-butenedioic acid; hydroxycarboxylic acid compounds such as malic acid, lactic acid, glycolic acid, gluconic acid, and citric acid; amino acid compounds such as glycine, alanine, imidoacetic acid, arginine, aspartic acid, and glutamic acid; organic acids such as aminopolycarboxylic acid compounds such as imidoacetic acid, triacetamide, ethylenediaminediacetic acid, ethylenediaminetetraacetic acid, and diethylenetriaminepentaacetic acid, or soluble salts of these organic acids (sodium salts, potassium salts, ammonium salts, etc.), amine compounds such as ethylenediamine, diethylenetriamine, and triethylenetetraamine, etc.
[0303] The electrolytic plating method is, for example, a method in which electricity is applied while an electrolytic plating solution is in contact with the metal constituting the above-mentioned plating base layer (B) or the surface of the electroless plating layer (film) formed by the above-mentioned electroless treatment, thereby causing metals such as copper contained in the electrolytic plating solution to precipitate onto the surface of the conductive material (b2) constituting the above-mentioned plating base layer (B) provided at the cathode or the electroless plating layer (film) formed by the above-mentioned electroless treatment, thereby forming an electrolytic plating layer (metal film).
[0304] Examples of the electrolytic plating solution include those containing sulfides of metals such as copper, nickel, chromium, cobalt, and tin, sulfuric acid, and an aqueous medium. Specifically, examples include those containing copper sulfate, sulfuric acid, and an aqueous medium.
[0305] The electroless plating solution and the electrolytic plating solution are preferably used within a range of 20 to 98°C.
[0306] The thickness of the metal plating layer (E) is preferably in the range of 0.01 μm to 100 μm, more preferably in the range of 0.5 μm to 50 μm. The thickness of the metal plating layer (E) can be adjusted by controlling the treatment time, current density, and the amount of plating additive used in the plating treatment step when forming the metal plating layer (E).
[0307] Examples of a method for patterning the metal plating layer (E) include a subtractive method, a photolithography-etching method such as a semi-additive method, and a method of plating on the printed pattern of the metal particle layer (C).
[0308] The subtractive method is a method in which a resist having a shape corresponding to a desired pattern shape is formed on the metal plating layer (E) constituting the laminate of the present invention which is manufactured in advance, and the metal plating layer (E) and the plated base layer (B) which remain after the etching agent is removed by subsequent development treatment are dissolved and removed by a chemical solution, thereby forming a desired pattern. As the chemical solution, a chemical solution containing cupric chloride, ferric chloride, etc. can be used.
[0309] The semi-additive method is a method in which the surface of the resin layer (C) of the transfer laminate is attached to the support (D), and the temporary support (A) of the transfer laminate is peeled off, and in a laminate having the resin layer (C) and the plated base layer (B) formed on the surface of the support (D), the surface of the plated base layer (B) is treated as necessary, and a plated resist layer having a shape corresponding to a desired pattern is formed on the surface, and then, after the metal plating layer (E) is formed by electroless plating, electrolytic plating or a combination thereof, the plated resist layer and the plated base layer (B) in contact therewith are dissolved in a chemical solution or the like to be removed, thereby forming a desired pattern. When the plated base layer (B) is silver, it is preferably etched with a chemical that selectively etches silver as described below.
[0310] In addition, in the above-mentioned semi-additive method, when it is necessary to make the front and back sides of the support (D) conductive or when it is necessary to make the surface of the support (D) conductive with the inner copper layer, the surface of the resin layer (C) of the transfer laminate can be attached to the support (D), and the temporary support (A) is not peeled off, but the temporary support (A) is given the following function of protecting the surface of the plated base layer. Specifically, the method is as follows: after laminating the transfer laminate to the support (D), a through hole or a non-through hole is opened from the surface of the temporary support (A) using a drill or a laser, and then at least one selected from the group of palladium, a conductive polymer, carbon, and a conductive paste is given to the surface (wall) of the through hole or the non-through hole, and the through hole or the non-through hole is subjected to a conductive treatment, and then the temporary support (A) of the transfer laminate is peeled off, and after the surface of the plating base layer (B) is treated as needed, a plating resist layer having a shape corresponding to the desired pattern is formed on its surface, and then, after the above-mentioned metal plating layer (E) is formed by an electrolytic plating method, the above-mentioned plating resist layer and the above-mentioned plating base layer (B) in contact therewith are dissolved in a liquid medicine or the like to be removed, thereby forming the desired pattern. In the case where the plating base layer (B) is silver, it is preferably etched with a chemical that selectively etches the following silver.
[0311] In addition, the through hole or the non-through hole is subjected to a conductive treatment by a dry plating method, so that the front and back sides can be connected. Specifically, in the semi-additive method, when it is necessary to connect the front and back sides of the support (D) or when it is necessary to connect the surface of the support (D) and the inner copper layer, the surface of the resin layer (C) of the transfer laminate can be attached to the support (D), and the temporary support (A) is not peeled off, but the temporary support (A) has the following function of protecting the surface of the plated base layer. Specifically, the method is as follows: after laminating the transfer laminate to the support (D), a through hole or a non-through hole is opened from the surface of the temporary support (A) using a drill or a laser, and then the surface (wall) of the through hole or the non-through hole is subjected to a conductive treatment using a dry plating method, the temporary support (A) of the transfer laminate is peeled off, and after the surface of the plating base layer (B) is treated as needed, a plating resist layer having a shape corresponding to the desired pattern is formed on the surface, and then the above-mentioned metal plating layer (E) is formed by an electrolytic plating method, and the above-mentioned plating resist layer and the above-mentioned plating base layer (B) in contact therewith are dissolved in a liquid medicine or the like to be removed, thereby forming the desired pattern. In addition, when the plating base layer (B) is silver, it is preferably etched with a chemical that selectively etches the following silver.
[0312] In addition, the conductive paste can be filled in the through hole or the non-through hole to make the front and back conductive. Specifically, it is the following method: after the transfer stack is attached to the support (D), a through hole or a non-through hole is opened from the surface of the temporary support (A) using a drill or a laser, the temporary support (A) of the transfer stack is peeled off, and after the surface treatment of the plated base layer (B) is performed as needed, a plated resist layer of a shape corresponding to the desired pattern is formed on its surface, and then, the metal plating layer (E) is formed by electrolytic plating. Thereafter, the plated resist layer and the plated base layer (B) in contact therewith are dissolved in a liquid medicine or the like to be removed, thereby forming the desired pattern. Then, using a screen printing method or the like, the through holes and the non-through holes are filled with a conductive paste and heated, so that the front and back are conductive.
[0313] By directly laminating the temporary support (A) on the plated base layer (B), in the following step of forming a through hole penetrating both sides in the method for manufacturing a printed circuit board of the present invention, organic or inorganic contaminants (smear) generated can be prevented from adhering to the surface of the plated base layer (B). In addition, in the step of making the inner wall surface of the formed through hole conductive, any one of palladium, conductive polymer, carbon, and conductive paste can be prevented from adhering to the conductive plated base layer (B), thereby protecting the plated base layer (B).
[0314] As a method for forming the above-mentioned through holes or non-through holes using the above-mentioned semi-additive method, a well-known and commonly used method can be appropriately selected, for example, drilling processing, laser processing, a processing method combining laser processing with chemical etching of an insulating substrate using an oxidant, an alkaline agent, an acidic agent, etc., and the like can be cited.
[0315] The hole size (diameter) of the hole formed by the drilling process is preferably in the range of 0.01 to 1 mm, more preferably in the range of 0.02 to 0.5 mm, and further preferably in the range of 0.03 to 0.1 mm.
[0316] Organic or inorganic dirt (smear) generated during the hole processing may cause poor plating precipitation in the metal plating process of forming the metal plating layer (E) or reduce the plating adhesion, which damages the plating appearance, so it is preferred to remove the dirt (smear removal). As a method for removing smear, for example, dry treatment such as plasma treatment and reverse sputtering treatment, cleaning treatment with an aqueous solution of an oxidant such as potassium permanganate, cleaning treatment with an aqueous solution of an alkali or acid, and wet treatment such as cleaning treatment with an organic solvent can be cited.
[0317] Next, there is a step of applying any one of palladium, conductive polymer, conductive paste, and carbon to the surface of the through hole or the non-through hole to make the surface of the through hole or the non-through hole conductive.
[0318] The method of making the through-hole surface conductive can be performed by referring to the method described in "Direct Plating" in, for example, Toyonaga Minoru, Circuit Technology, vol. 8, No. 1 (1993) pp. 47-59.
[0319] As a method for making the surface of the through hole conductive, any of the four methods described in the above literature, (1) palladium-tin colloid system, (2) tin-free palladium system, (3) conductive polymer system, and (4) graphite system, can be used. Alternatively, the surface of the through hole can be conductively treated with a conductive paste.
[0320] As a method for making the surface of the through hole conductive using palladium-tin colloid, the method is implemented as follows: after cleaning and conditioning the surface of the laminated body with the through hole, tin-palladium colloid is adsorbed on the surface, and accelerated treatment is performed to remove the tin. Alternatively, a method of further converting palladium into palladium sulfide to improve conductivity can also be used.
[0321] In addition, as a method for making the surface of the through hole conductive by using a conductive polymer, a method of oxidatively polymerizing a monomer of a pyrrole derivative can be used. After conditioning the surface of the laminate having the through hole, it is treated with an aqueous permanganate solution to form MnO2 on the surface of the through hole formed on the support (D). If the substrate surface is immersed in an aqueous monomer solution in which a high-boiling alcohol is dissolved, and then immersed in a dilute sulfuric acid aqueous solution, the surface coated with MnO2 is polymerized to form a conductive polymer, thereby making it conductive.
[0322] Furthermore, as a method of making the surface of the through hole conductive by using graphite, the surface of the laminate having through holes is treated with a solution of suspended carbon black to adsorb carbon on the entire surface of the substrate. By conditioning the surface of the laminate having through holes, the surface of the substrate is positively charged, and then carbon black having a negative charge is adsorbed on the surface to ensure conductivity.
[0323] Furthermore, as a method of making the surface of the through hole conductive with a conductive paste, a method of imparting conductivity to the wall of the through hole formed on the surface of the laminated body is used to form a seed layer for the subsequent electrolytic plating process.
[0324] As a method for making the through hole surface conductive, any method using the above-mentioned palladium, conductive polymer, carbon, and conductive paste can be used, and commercially available known and commonly used processes can be used. For example, in the tin-palladium process, a method known as the CRIMSON process can be used, and in the graphite system, for example, a process known as the black hole process or the shadow process can be used. Among these methods, from the viewpoint of material and process cost, a method using carbon for conductive use is preferably used.
[0325] Furthermore, as a method for making the surface of the through hole and the non-through hole conductive, there is a method for treating the surface of the above-mentioned laminate formed with a through hole with a dry plating method. For example, a method of using a vacuum evaporation method, an ion plating method, or a sputtering method to form a film on the surface of the through hole and make it conductive can also be used appropriately. When the dry plating method is used for conductivity, the metal species used for conductivity is not limited, as long as the surface of the through hole can be made conductive and the two-sided connection of the electrolytic copper plating by the subsequent process is not hindered, and various metals and metal oxides can be used. For example, one of the metals such as titanium, nickel, copper, silver, gold, platinum, etc. can be used or a plurality of them can be used in combination. When a plurality of them are combined, a plurality of metals can be made into films simultaneously, or they can be made into films one by one. Among these metal species, copper or silver is preferably used from the viewpoint of conductivity.
[0326] Then, the temporary support (A) is peeled off to expose the plated base layer (B). This step is a step of exposing the plated base layer (B) which becomes a plated seed layer for forming a metal plated layer (E) in a subsequent step, and has the purpose of removing the palladium, conductive polymer, conductive paste, carbon, sputtered metal or metal oxide used to make the through hole conductive from the surface other than the through hole.
[0327] The temporary support layer (A) can be peeled off by mechanical peeling, and various commercially available peeling devices can also be used. In addition, when an alkali-soluble resin is used as the temporary support (A), it can be peeled off by immersing it in an alkaline solution. As the alkaline solution and peeling conditions for peeling, the stripping solution used for the following pattern resist can be appropriately used.
[0328] Next, after the temporary support (A) is peeled off, a pattern resist having a circuit pattern is formed on the exposed plating base layer (B).
[0329] In the process of forming the pattern resist, in order to improve the adhesion with the resist layer, the surface of the plated base layer (B) may be subjected to a surface treatment such as cleaning with an acidic or alkaline cleaning solution, corona treatment, plasma treatment, UV treatment, gas phase ozone treatment, liquid phase ozone treatment, or treatment with a surface treatment agent before the resist is formed. These surface treatments may be performed by one method or by combining two or more methods.
[0330] As the treatment with the surface treatment agent, for example, a method of treating with a rust inhibitor composed of a triazole compound, a silane coupling agent and an organic acid as described in Japanese Unexamined Patent Publication No. 7-258870, a method of treating with an organic acid, a benzotriazole rust inhibitor and a silane coupling agent as described in Japanese Unexamined Patent Publication No. 2000-286546, a method of treating with a substance having a structure in which a nitrogen-containing heterocyclic ring such as triazole or thiadiazole and a silyl group such as a trimethoxysilyl group or a triethoxysilyl group are bonded via an organic group having a thioether (sulfide) bond as described in Japanese Unexamined Patent Publication No. 2002-363189, a method of treating with a substance having a structure in which a nitrogen-containing heterocyclic ring such as triazole or thiadiazole and a silyl group such as a trimethoxysilyl group or a triethoxysilyl group are bonded via an organic group having a thioether (sulfide) bond as described in WO2013 / 186941, A method for treating with a silane compound having an amino group and an amino group, a method for treating with an imidazole silane compound obtained by reacting a formyl imidazole compound with an aminopropyl silane compound as described in Japanese Patent Application Publication No. 2015-214743, a method for treating with an azole silane compound as described in Japanese Patent Application Publication No. 2016-134454, a method for treating with an aromatic compound having an amino group and an aromatic ring in one molecule, a polyacid having two or more carboxyl groups, and a halide ion as described in Japanese Patent Application Publication No. 2017-203073, a method for treating with a surface treatment agent containing a triazole silane compound as described in Japanese Patent Application Publication No. 2018-16865, etc.
[0331] Then, in order to form a metal pattern on the surface, the photosensitive resist of the resist layer is exposed to the pattern with active light through a photomask or using a direct exposure machine. The exposure amount can be appropriately set as needed. The latent image formed on the photosensitive resist by exposure is removed using a developer to form a pattern resist.
[0332] As the developer, a dilute alkaline aqueous solution of 0.3 to 2% by mass of sodium carbonate, potassium carbonate, etc. may be cited. In order to promote the surfactant, defoaming agent or development, a small amount of organic solvent or the like may be added to the dilute alkaline aqueous solution. In addition, the exposed substrate may be immersed in the developer, or the developer may be sprayed onto the resist by a jet or the like, thereby developing the pattern resist remaining after the pattern forming portion is removed.
[0333] When forming a pattern resist, a descum treatment using plasma or a commercially available resist residue remover may be used to remove resist residues such as flanges generated at the interface between the cured resist and the substrate or resist deposits remaining on the substrate surface.
[0334] As the photosensitive resist used in the present invention, commercially available resist inks, liquid resists, and dry film resists can be used, and they can be appropriately selected according to the resolution of the target pattern, the type of exposure machine used, the type of chemical solution used in the plating treatment in the subsequent process, the pH, etc.
[0335] As commercially available resist inks, for example, "plating resist MA-830" and "etching resist X-87" manufactured by Taiyo Ink Manufacturing Co., Ltd.; etching resists and plating resists of NAZDAR; "etching resist PLAS FINE PER" series and "plating resist PLAS FINE PPR" series manufactured by Huying Chemical Co., Ltd., etc. In addition, as electrodeposition resists, for example, "Eagle series" and "Paper series" of Dow Chemical Company, etc. can be mentioned. Furthermore, as commercially available dry films, for example, "PHOTEK" series manufactured by Hitachi Chemical Co., Ltd.; "ALPHO" series manufactured by Nikko Materials Co., Ltd.; "Sunfort" series manufactured by Asahi Kasei Co., Ltd., "Riston" series manufactured by Dupont, etc. can be mentioned.
[0336] In order to efficiently manufacture printed circuit boards, it is relatively simple to use a dry film resist, and in particular, when forming fine circuits, a dry film for a semi-additive method can be used. Commercially available dry films for this purpose include, for example, "ALFO LDF500" and "NIT2700" manufactured by Nikko Materials Co., Ltd., "Sunphooto UFG-258" manufactured by Asahi Kasei Co., Ltd., "RD Series (RD-2015, 1225)" and "RY Series (RY-5319, 5325)" manufactured by Hitachi Chemical Co., Ltd., and "PlateMaster Series (PM200, 300)" manufactured by Dupont.
[0337] Then, a metal plating layer (E) is formed on the above-mentioned plating base layer (B) formed with the plating resist. The above-mentioned metal plating layer can be exemplified by wet plating methods such as electrolytic plating and electroless plating. In addition, two or more of these plating methods can also be combined. If the photosensitive resist is immersed in an alkaline aqueous solution, it will cause peeling, so it is preferred to form the metal plating layer (E) by electrolytic plating.
[0338] The plated base layer (B) is used as a cathode electrode for electrolytic copper plating. The plated base layer (B) exposed by development is treated by electrolytic copper plating as described above, thereby connecting the through holes of the stacked body with copper plating and forming a conductive pattern at the same time.
[0339] Before forming the conductive pattern by the electrolytic copper plating method, the surface of the plated base layer (B) may be subjected to a surface treatment as required. As the surface treatment, cleaning treatment by an acidic or alkaline cleaning solution, corona treatment, plasma treatment, UV treatment, gas phase ozone treatment, liquid phase ozone treatment, treatment by a surface treatment agent, etc. may be cited without damaging the surface of the plated base layer (B) or the formed resist pattern. These surface treatments may be performed by one method or by using two or more methods in combination.
[0340] In addition, when forming a conductive pattern after the copper plating, annealing may be performed after plating to relieve stress of the plated film or improve adhesion. Annealing may be performed before or after the etching step described below, or before or after etching.
[0341] The annealing temperature can be appropriately selected in the temperature range of 40 to 300° C. according to the heat resistance of the substrate used or the purpose of use, preferably in the range of 40 to 250° C., and more preferably in the range of 40 to 200° C. in order to suppress the oxidation degradation of the plated film. In addition, the annealing time is preferably 10 minutes to 10 days in the temperature range of 40 to 200° C., and the annealing time at a temperature exceeding 200° C. is preferably about 5 minutes to 10 hours. In addition, when the plated film is annealed, a rust inhibitor can also be appropriately applied to the surface of the plated film.
[0342] Then, the pattern resist is stripped. After the conductive pattern is formed by the above-mentioned plating, the pattern resist formed using the above-mentioned photosensitive resist is stripped, and the above-mentioned plating base layer (B) of the non-pattern forming part is removed by an etching solution. The stripping of the pattern resist can be carried out under the recommended conditions described in the catalog, specification sheet, etc. of the photosensitive resist used. In addition, as the resist stripping solution used when stripping the pattern resist, a commercially available resist stripping solution or a 1.5-3% by mass aqueous solution of sodium hydroxide or potassium hydroxide set to 45-60°C can be used. The stripping of the resist can be carried out by immersing the substrate on which the pattern is formed in the stripping solution, or by spraying the stripping solution with a spray or the like.
[0343] In addition, the etching solution used when removing the plating base layer (B) of the non-pattern forming portion preferably selectively etches only the above-mentioned plating base layer (B) and does not etch the copper forming the above-mentioned metal plating layer (E). When silver is used for the plating base layer (B), such an etching solution may be a mixture of carboxylic acid and hydrogen peroxide.
[0344] As the above-mentioned carboxylic acid, for example, acetic acid, citric acid, formic acid, propionic acid, butyric acid, valeric acid, caproic acid, heptanoic acid, octanoic acid, nonanoic acid, capric acid, lauric acid, myristic acid, palmitic acid, heptadecanoic acid, stearic acid, oleic acid, linoleic acid, linolenic acid, arachidic acid, eicosapentaenoic acid, docosahexaenoic acid, oxalic acid, malonic acid, succinic acid, benzoic acid, salicylic acid, phthalic acid, isophthalic acid, terephthalic acid, gallic acid, mellitic acid, cinnamic acid, pyruvic acid, lactic acid, malic acid, citric acid, trans-butenedioic acid, maleic acid, aconitic acid, glutaric acid, adipic acid, amino acids, etc. can be mentioned. These carboxylic acids can be used alone or in combination of two or more. Among these carboxylic acids, acetic acid or citric acid is preferably mainly used in terms of ease of manufacture and handling as an etching solution.
[0345] When a mixture of carboxylic acid and hydrogen peroxide is used as an etching solution, hydrogen peroxide reacts with carboxylic acid to generate peroxycarboxylic acid. The generated peroxycarboxylic acid is presumed to suppress the dissolution of copper constituting the conductive pattern while preferentially dissolving silver constituting the above-mentioned plating base layer (B).
[0346] The mixing ratio of the mixture of the carboxylic acid and hydrogen peroxide is preferably in the range of 2 to 100 mol, more preferably 2 to 50 mol, per 1 mol of the carboxylic acid in order to suppress dissolution of the copper conductive pattern.
[0347] The mixture of the carboxylic acid and hydrogen peroxide is preferably an aqueous solution diluted with water. In addition, from the perspective of being able to suppress the influence of the temperature rise of the etching solution, the content ratio of the mixture of the carboxylic acid and hydrogen peroxide in the aqueous solution is preferably in the range of 2 to 65% by mass, and more preferably in the range of 2 to 30% by mass.
[0348] As the water used for the dilution, it is preferable to use water from which ionic substances and impurities have been removed, such as ion-exchanged water, pure water, and ultrapure water.
[0349] A protective agent for protecting the copper conductive pattern and suppressing dissolution may be further added to the etching solution. As the protective agent, an azole compound is preferably used.
[0350] Examples of the azole compound include imidazole, pyrazole, triazole, tetrazole, oxazole, thiazole, selenazole, oxadiazole, thiadiazole, oxatriazole and thiatriazole.
[0351] Specific examples of the azole compounds include 2-methylbenzimidazole, aminotriazole, 1,2,3-benzotriazole, 4-aminobenzotriazole, 1-bisaminomethylbenzotriazole, aminotetrazole, phenyltetrazole, 2-phenylthiazole, benzothiazole, etc. These azole compounds may be used alone or in combination of two or more.
[0352] The concentration of the azole compound in the etching solution is preferably in the range of 0.001 to 2 mass %, and more preferably in the range of 0.01 to 0.2 mass %.
[0353] In addition, it is preferred to add polyalkylene glycol as a protective agent to the etching solution in order to suppress dissolution of the copper conductive pattern.
[0354] Examples of the polyalkylene glycol include water-soluble polymers such as polyethylene glycol, polypropylene glycol, and polyoxyethylene-polyoxypropylene block copolymers. Of these, polyethylene glycol is preferred. The number average molecular weight of the polyalkylene glycol is preferably in the range of 200 to 20,000.
[0355] The concentration of the polyalkylene glycol in the etching solution is preferably in the range of 0.001 to 2% by mass, and more preferably in the range of 0.01 to 1% by mass.
[0356] In order to suppress pH fluctuation, the etching solution may contain an additive such as a sodium salt, a potassium salt, or an ammonium salt of an organic acid, if necessary.
[0357] The removal of the plated base layer (B) in the non-patterned portion can be performed by forming the conductive pattern and then immersing the substrate after peeling off the pattern resist formed using the photosensitive resist in the etching solution, or spraying the etching solution onto the substrate using a spray or the like.
[0358] When using an etching device to remove the plated base layer (B) of the non-pattern forming part, for example, all the components of the above-mentioned etching solution can be prepared in a manner to have a prescribed composition and then supplied to the etching device, or the components of the above-mentioned etching solution can be separately supplied to the etching device and the above-mentioned components can be mixed in the device to prepare it in a manner to have a prescribed composition.
[0359] The etching solution is preferably used in a temperature range of 10 to 35° C., and in particular, when an etching solution containing hydrogen peroxide is used, it is preferably used in a temperature range of 30° C. or lower in order to suppress the decomposition of hydrogen peroxide.
[0360] After the above-mentioned plating base layer (B) is removed by the above-mentioned etching solution, in order to prevent the silver component dissolved in the etching solution from adhering to and remaining on the printed circuit board, a cleaning operation may be further performed in addition to water washing. For the cleaning operation, it is preferred to use a cleaning solution that dissolves silver oxide, silver sulfide, and silver chloride but hardly dissolves silver. Specifically, it is preferred to use an aqueous solution containing thiosulfate or tris (3-hydroxyalkyl) phosphine or an aqueous solution containing mercaptocarboxylic acid or a salt thereof as the cleaning solution.
[0361] Examples of the thiosulfate salt include ammonium thiosulfate, sodium thiosulfate, potassium thiosulfate, etc. Examples of the tris(3-hydroxyalkyl)phosphine include tris(3-hydroxymethyl)phosphine, tris(3-hydroxyethyl)phosphine, tris(3-hydroxypropyl)phosphine, etc. These thiosulfates or tris(3-hydroxyalkyl)phosphine may be used alone or in combination of two or more.
[0362] When using an aqueous solution containing thiosulfate, the concentration can be appropriately set according to the process time, the characteristics of the cleaning device used, etc., and is preferably in the range of 0.1 to 40% by mass. From the perspective of cleaning efficiency or the stability of the solution during continuous use, it is more preferably in the range of 1 to 30% by mass.
[0363] The concentration of the aqueous solution containing tris(3-hydroxyalkyl)phosphine when used may be appropriately set according to the process time, the characteristics of the cleaning apparatus used, etc., and is preferably in the range of 0.1 to 50% by mass. From the viewpoint of cleaning efficiency or the stability of the solution during continuous use, it is more preferably in the range of 1 to 40% by mass.
[0364] Examples of the mercaptocarboxylic acid include thioglycolic acid, 2-mercaptopropionic acid, 3-mercaptopropionic acid, thiomalic acid, cysteine, N-acetylcysteine, etc. Examples of the salt of the mercaptocarboxylic acid include alkali metal salts, ammonium salts, amine salts, and the like.
[0365] When an aqueous solution of mercaptocarboxylic acid or a salt thereof is used, the concentration is preferably in the range of 0.1 to 20% by mass, and more preferably in the range of 0.5 to 15% by mass from the viewpoint of cleaning efficiency and process cost in large-scale treatment.
[0366] As a method for performing the above-mentioned cleaning operation, for example, there can be mentioned: a method of immersing the printed circuit board obtained by etching away the plated base layer (B) of the non-pattern forming part in the above-mentioned cleaning solution; a method of spraying the cleaning solution onto the above-mentioned printed circuit board by spraying, etc. Regarding the temperature of the cleaning solution, it can be used at room temperature (25°C), and in order to stably perform the cleaning treatment without being affected by the external temperature, it can also be used at a temperature of, for example, 30°C.
[0367] In addition, the step of removing the plating base layer (B) in the non-pattern forming portion by an etching solution and the cleaning operation may be repeated as necessary.
[0368] As described above, after the plated base layer (B) of the non-patterned portion is removed by the etching solution, the printed circuit board of the present invention may be further cleaned as needed to further improve the insulation of the non-patterned portion. For example, the cleaning operation may be performed using an alkaline permanganate solution prepared by dissolving potassium permanganate or sodium permanganate in an aqueous solution of potassium hydroxide or sodium hydroxide.
[0369] The cleaning using the alkaline permanganate solution may be exemplified by: a method of immersing the printed circuit board obtained by the above method in an alkaline permanganate solution set at 20 to 60° C.; a method of spraying the alkaline permanganate solution onto the printed circuit board by spraying, etc. In order to improve the wettability of the alkaline permanganate solution to the surface of the substrate and improve the cleaning efficiency, the printed circuit board may be contacted with a water-soluble organic solvent having an alcoholic hydroxyl group before cleaning. As the organic solvent, methanol, ethanol, n-propanol, isopropanol, etc. may be exemplified. One of these organic solvents may be used, or two or more of them may be used in combination.
[0370] The concentration of the alkaline permanganic acid solution can be appropriately selected as required, preferably a solution of 0.1 to 10 mass parts of potassium permanganate or sodium permanganate dissolved in 100 mass parts of 0.1 to 10 mass % potassium hydroxide or sodium hydroxide aqueous solution, and more preferably a solution of 1 to 6 mass parts of potassium permanganate or sodium permanganate dissolved in 100 mass parts of 1 to 6 mass % potassium hydroxide or sodium hydroxide aqueous solution with regard to the viewpoint of cleaning efficiency.
[0371] When the alkaline permanganate solution is used for cleaning, it is preferred that after the alkaline permanganate solution is used for cleaning, the cleaned printed circuit board is treated with a solution having a neutralizing and reducing effect. As the solution having a neutralizing and reducing effect, for example, an aqueous solution containing 0.5 to 15% by mass of dilute sulfuric acid or an organic acid may be mentioned. In addition, as the organic acid, for example, formic acid, acetic acid, oxalic acid, citric acid, ascorbic acid, methionine, etc. may be mentioned.
[0372] The cleaning with the alkaline permanganate solution may be performed after the cleaning performed to prevent the silver component dissolved in the etching solution from adhering to and remaining on the printed circuit board, or the cleaning with the alkaline permanganate solution may be performed instead of the cleaning to prevent the silver component dissolved in the etching solution from adhering to and remaining on the printed circuit board.
[0373] In addition, the printed wiring board obtained using the printed wiring board laminate of the present invention may be subjected to nickel / gold plating, nickel / palladium / gold plating, or palladium / gold plating as necessary as a final surface treatment for laminating a cover film on the circuit pattern, forming a solder resist layer, and the circuit pattern.
[0374] Next, drawings related to a method for producing a transfer laminate and a method for producing a conductive pattern will be described.
[0375] Figure 3 The present invention relates to a method for producing a transfer laminate. A plated base layer (B) is formed on the entire surface of a temporary support (A), and then a resin layer (C) is formed to obtain a transfer laminate.
[0376] Figure 4 The invention relates to a method for producing a transfer laminate. A plated base layer (B) is formed on the surface of a temporary support (A), a conductive pattern is formed by etching using a pattern resist, and after removing the pattern resist, a resin (C) is formed on the entire surface of the temporary support (A), thereby obtaining a transfer laminate.
[0377] Figure 5 The present invention relates to a method for producing a transfer laminate. After forming a pattern of a plated base layer (B) on the surface of a temporary support (A) by printing, a resin layer (C) is formed on the entire surface of the temporary support (A) to obtain a transfer laminate.
[0378] Figure 6 This is a step of smoothing the surface of the support (D). This step is not necessarily necessary when the surface of the support (D) is sufficiently smooth. For a support (D) with large surface irregularities, a smooth surface of a smoothing substrate such as a metal foil or a heat-resistant film is bonded to the support (D) using hot pressing or vacuum pressing, and then the bonded metal foil or heat-resistant film is physically or chemically peeled off to obtain a smooth support (D).
[0379] Figure 7 is used Figure 3 A method for manufacturing a conductive pattern of a transfer laminate obtained in . A transfer laminate having a plated base layer (B) and a resin layer (C) formed on the entire surface of a temporary support (A), wherein the surface having the resin layer (C) formed thereon is bonded to both surfaces of a support (D), and the temporary support (A) of the bonded transfer laminate is peeled off, and after the resin layer (C) and the plated base layer (B) are formed on both surfaces of the support (D), a conductive pattern of a metal plated layer (E) is formed. In Figure 7 In the process, the transfer laminate is laminated to both surfaces of the support (D), or the transfer laminate may be laminated to only one surface.
[0380] Figure 8 It is used Figure 4 or Figure 5A method for producing a conductive pattern of a transfer laminate obtained in . A transfer laminate having a resin layer (C) is formed on the entire surface of a temporary support (A) after forming a pattern of a plated base layer (B) on a portion of the surface of a temporary support (A) by using a pattern resist or a printing method, and the surface on which the resin layer (C) is formed is bonded to a support (D). Subsequently, the temporary support (A) of the bonded transfer laminate is peeled off, and after the resin layer (C) and the plated base layer (B) are formed on both surfaces of the support (D), a conductive pattern of a metal plated layer (E) is formed. In Figure 8 In the process, the transfer laminate is laminated to both surfaces of the support (D), or the transfer laminate may be laminated to only one surface.
[0381] Fig. 9 Is using Figure 3 In the case of the transfer laminate obtained in the method, the front and back surfaces of the support (D) are electrically connected through the through holes.
[0382] After laminating the smooth surface of a smooth metal foil or a heat-resistant film to at least one side of a support (D) having projections and depressions by using hot pressing or the like, removing the laminating metal foil or heat-resistant film to smoothen the support (D), laminating the surface of a transfer laminate having a plated base layer (B) and a resin layer (C) formed on the entire surface of a temporary support (A) on which the resin layer (C) is formed to the smoothed surface of the support (D), and then forming a through hole penetrating both surfaces from the temporary support (A) of the transfer laminate, and then imparting any one of palladium, a conductive polymer, a conductive paste, and carbon to the surface of the transfer laminate and the through hole to make the surface of the through hole conductive, and then peeling off the temporary support (A) to form a conductive pattern of a metal plating layer (E) on the plated base layer (B) and the through hole. Fig. 9 In the case of a smoothing treatment of the support (D), this treatment is not necessarily necessary when the surface is sufficiently smooth. Figure 3 The example of the transfer laminate obtained in the embodiment of the present invention is as follows, but it is also possible to use a laminate such as Figure 4 or Figure 5 Thus, a laminate having a pattern of a plated base layer (B) is formed on the transfer laminate. Furthermore, although the transfer laminate is bonded to both sides of the support (D), the transfer laminate may be bonded to only one side, and other conductive patterns such as copper foil may be bonded to the other side.
[0383] Fig.10 is used Figure 3 In the case of the transfer laminate obtained in the method, the front and back surfaces of the support (D) are electrically connected through the through holes.
[0384] After laminating the smooth surface of a smooth metal foil or a heat-resistant film to at least one side of a support (D) having projections and depressions by using hot pressing or the like, removing the laminating metal foil or heat-resistant film to smoothen the support (D), laminating the surface of a transfer laminate having a plated base layer (B) and a resin layer (C) formed on the entire surface of a temporary support (A) on which the resin layer (C) is formed to the smoothed surface of the support (D), and then forming through holes penetrating both surfaces from the temporary support (A) of the transfer laminate, forming a metal film on the surface of the transfer laminate and the through hole by using a dry plating method such as an evaporation method or a sputtering method to make the surface of the through hole conductive, and then peeling off the temporary support (A) to form a conductive pattern of a metal plating layer (E) on the plated base layer (B) and the through hole. Fig.10 In the embodiment, the support (D) is subjected to a smoothing treatment, but this is not necessarily necessary when the surface is sufficiently smooth. Figure 3 The example of the transfer laminate obtained in the embodiment of the present invention is as follows, but it is also possible to use a laminate such as Figure 4 or Figure 5 Thus, the transfer laminate has a pattern of the plated base layer (B) formed on it. Furthermore, although the transfer laminate is bonded to both sides of the support (D), the transfer laminate can also be bonded to only one side, and other conductive patterns such as copper foil can be bonded to the other side.
[0385] Fig.11 is used Figure 3 In the case of the transfer laminate obtained in the method, the front and back surfaces of the support (D) are electrically connected through the through holes.
[0386] After laminating the smooth surface of a smooth metal foil or a heat-resistant film to at least one side of a support (D) having projections and depressions by using hot pressing or the like, the laminating metal foil or heat-resistant film is removed to smooth the support (D), and then, a transfer laminate having a plated base layer (B) and a resin layer (C) formed on the entire surface of a temporary support (A) is laminated on the surface having the resin layer (C) to the smoothed surface of the support (D), and then, through holes penetrating both surfaces are formed from the temporary support (A) of the transfer laminate, and then, the temporary support (A) is peeled off, and a metal plating layer (E) is formed on the surface of the plated base layer (B), and then, a conductive paste is filled in the through holes to make the through holes conductive. A method for manufacturing a conductive pattern. Fig.11 In the embodiment, the support (D) is subjected to a smoothing treatment, but this is not necessarily necessary when the surface is sufficiently smooth. Figure 3 The example of the transfer laminate obtained in the embodiment of the present invention is as follows, but it is also possible to use a laminate such as Figure 4 or Figure 5Thus, a laminate having a pattern of the plated base layer (B) is formed on the transfer laminate. Furthermore, although the transfer laminate is bonded to both sides of the support (D), the transfer laminate may be bonded to only one side, and other conductive patterns such as copper foil may be bonded to the other side.
[0387] Fig.12 is used Figure 3 In the case of a transfer laminate obtained in the process, a support (D) is adhered to a substrate having a conductive pattern, and the surface of the support (D) is smoothed, and a conductive pattern is manufactured in which the surface of the support (D) is electrically connected to the conductive pattern of the inner layer through non-through holes.
[0388] A support (D) and a smooth metal foil or a heat-resistant film are sequentially stacked on at least one side of a substrate having a conductive pattern formed thereon, and after being bonded together by hot pressing, the metal foil or the heat-resistant film is removed to smooth the support (D), and then, on the surface of the support (D), a transfer laminate having a plated base layer (B) and a resin layer (C) formed on the entire surface of a temporary support (A) is bonded to the smoothed surface of the support (D), and non-through holes are formed from the temporary support (A) of the transfer laminate to the conductive pattern of the inner layer, and any one of palladium, a conductive polymer, a conductive paste, and carbon is applied to the surface of the transfer laminate and the non-through hole to make the surface of the non-through hole conductive, and the temporary support (A) is peeled off, and a conductive pattern having a metal plating layer (E) formed on the plated base layer (B) and the non-through hole is produced. Fig.12 The support (D) is smoothed, but this is not necessarily necessary when the surface is sufficiently smooth. Fig.12 is used Figure 3 The example of the transfer laminate obtained in the embodiment of the present invention is as follows, but it is also possible to use a laminate such as Figure 4 or Figure 5 A laminate having a pattern of a plated base layer (B) formed on the transfer laminate. Fig.12 The support (D) is bonded to both surfaces of the substrate having the conductive pattern formed thereon, and the transfer laminate is further bonded thereto. However, the support (D) and the transfer laminate may be bonded to only one surface, and the support (D) and another conductive pattern such as copper foil may be bonded to the other surface.
[0389] Fig.13 is used Figure 3 In the case of a transfer laminate obtained in the process, a support (D) is adhered to a substrate having a conductive pattern, and the surface of the support (D) is smoothed, and a conductive pattern is manufactured in which the surface of the support (D) is electrically connected to the conductive pattern of the inner layer through non-through holes.
[0390] A support (D) and a smooth metal foil or a heat-resistant film are sequentially stacked on at least one side of a substrate having a conductive pattern formed thereon, and after being bonded together by hot pressing, the metal foil or the heat-resistant film is removed to smooth the support (D), and then, on the surface of the support (D), a transfer laminate having a plated base layer (B) and a resin layer (C) formed on the entire surface of a temporary support (A) is bonded to the smoothed surface of the support (D), and non-through holes are formed from the temporary support (A) of the transfer laminate to the conductive pattern of the inner layer, a metal film is formed on the surface of the transfer laminate and the non-through holes by a dry plating method such as an evaporation method or a sputtering method to make the surface of the non-through holes conductive, and after the temporary support (A) is peeled off, a conductive pattern of a metal plating layer (E) is formed on the plated base layer (B) and the non-through holes. Fig.13 The support (D) is smoothed, but this is not necessarily necessary when the surface is sufficiently smooth. Fig.13 Although using Figure 3 The example of the transfer laminate obtained in the embodiment of the present invention is as follows, but it is also possible to use a laminate such as Figure 4 or Figure 5 A laminate having a pattern of a plated base layer (B) formed on a transfer laminate. Fig.13 The support (D) is bonded to both surfaces of the substrate having the conductive pattern formed thereon, and the transfer laminate is further bonded thereto. However, the support (D) and the transfer laminate may be bonded to only one surface, and the support (D) and another conductive pattern such as copper foil may be bonded to the other surface.
[0391] Fig.14 is used Figure 3 In the case of a transfer laminate obtained in the process, a support (D) is adhered to a substrate having a conductive pattern, and the surface of the support (D) is smoothed, and a conductive pattern is manufactured in which the surface of the support (D) is electrically connected to the conductive pattern of the inner layer through non-through holes.
[0392] A support (D) and a smooth metal foil or a heat-resistant film are sequentially stacked on at least one side of a substrate having a conductive pattern formed thereon, and after being bonded together by hot pressing, the metal foil or the heat-resistant film is removed to smooth the support (D), and then, on the surface of the support (D), a transfer laminate having a plated base layer (B) and a resin layer (C) formed on the entire surface of a temporary support (A) is bonded to the smoothed surface of the support (D), and then, non-through holes are formed from the temporary support (A) of the transfer laminate to the conductive pattern of the inner layer, the temporary support (A) is peeled off, and a metal plating layer (E) is formed on the surface of the plated base layer (B), and then, a conductive paste is filled in the non-through holes to make the non-through holes conductive. A method for manufacturing a conductive pattern. Fig.14 The support (D) is smoothed, but this is not necessarily necessary when the surface is sufficiently smooth. Fig.14 Although using Figure 3 The example of the transfer laminate obtained in the embodiment of the present invention is as follows, but it is also possible to use a laminate such as Figure 4 or Figure 5 A laminate having a pattern of a plated base layer (B) is formed on such a transfer laminate. Fig.14 The support (D) is bonded to both surfaces of the substrate having the conductive pattern formed thereon, and the transfer laminate is further bonded thereto. However, the support (D) and the transfer laminate may be bonded to only one surface, and the support (D) and another conductive pattern such as copper foil may be bonded to the other surface.
[0393] Fig.15 is used Figure 3 In the case of the transfer laminate obtained in , the front and back surfaces of the support (D) are electrically connected via through holes, and a method for producing a conductive pattern by a semi-additive process.
[0394] After the smooth surface of a smooth metal foil or a heat-resistant film is bonded to at least one side of a support (D) having projections and depressions by using hot pressing or the like, the bonded metal foil or heat-resistant film is removed to smoothen the support (D), and then a transfer laminate having a plated base layer (B) and a resin layer (C) formed on the entire surface of a temporary support (A) is bonded to the smoothed surface of the support (D), and then a through hole penetrating both surfaces is formed from the temporary support (A) of the transfer laminate, and a through hole is formed on the temporary support (A) of the transfer laminate. A method for producing a conductive pattern by imparting any one of palladium, conductive polymer, conductive paste, and carbon to the surface of a transfer stack and a through hole to make the surface of the through hole conductive, then peeling off the temporary support (A), forming a pattern resist on the surface of a plated base layer (B), then forming a metal plated layer (E) on the plated base layer (B) and the through hole, then peeling off the pattern resist, and removing the plated base layer (B) except for the portion where the metal plated layer (E) forming the conductive pattern is formed by an etching solution. Fig.15 The support (D) is smoothed, but this is not necessarily necessary when the surface is sufficiently smooth. Fig.15 Although the transfer laminate is laminated to both surfaces of the support (D), the transfer laminate may be laminated to only one surface, and another conductive pattern such as copper foil may be laminated to the other surface.
[0395] Fig.16 is using Figure 3 In the case of the transfer laminate obtained in , the front and back surfaces of the support (D) are electrically connected via through holes, and a method for producing a conductive pattern by a semi-additive process.
[0396] After the smooth surface of a smooth metal foil or a heat-resistant film is laminated to at least one side of a support (D) having projections and depressions by using a hot press or the like, the laminated metal foil or the heat-resistant film is removed to smooth the support (D), and then a transfer laminate having a plated base layer (B) and a resin layer (C) formed on the entire surface of a temporary support (A) is laminated on the surface having the resin layer (C) formed thereon to the smoothed surface of the support (D), and through holes penetrating both surfaces are formed from the temporary support (A) of the transfer laminate, so that A method for manufacturing a conductive pattern by forming a metal film on the surface of the transfer stack and the through hole by dry plating to make the surface of the through hole conductive, then peeling off the temporary support (A) and forming a pattern resist on the surface of the plated base layer (B), then forming a metal plating layer (E) on the plated base layer (B) and the through hole, then peeling off the pattern resist and removing the plated base layer (B) except for the portion where the metal plating layer (E) forming the conductive pattern is formed by an etching solution. In addition, Fig.16Although the support (D) is smoothed in the embodiment, this is not necessarily required if the surface is sufficiently smooth. Fig.16 Although the transfer laminate is laminated to both surfaces of the support (D), the transfer laminate may be laminated to only one surface, and another conductive pattern such as copper foil may be laminated to the other surface.
[0397] Fig.17 is using Figure 3 In the case of the transfer laminate obtained in , the front and back surfaces of the support (D) are electrically connected via through holes, and a method for producing a conductive pattern by a semi-additive process.
[0398] After the smooth surface of a smooth metal foil or a heat-resistant film is laminated to at least one surface of a support (D) having projections and depressions by using a hot press or the like, the laminated metal foil or the heat-resistant film is removed to smoothen the support (D), and then, a transfer laminate having a plated base layer (B) and a resin layer (C) formed on the entire surface of a temporary support (A) is laminated on the surface having the resin layer (C) formed thereon to the smoothed surface of the support (D), and a transfer laminate is removed from the temporary support (A) of the transfer laminate. A method for manufacturing a conductive pattern by forming a through hole that penetrates both sides, then peeling off the temporary support (A) and forming a pattern resist on the surface of the plated base layer (B), then forming a metal plated layer (E) on the plated base layer (B), then peeling off the pattern resist and removing the plated base layer (B) except for the portion where the metal plated layer (E) that becomes the conductive pattern is formed by an etching solution, then filling the through hole with a conductive paste to make the through hole conductive. Fig.17 The support (D) is smoothed, but this is not necessarily necessary when the surface is sufficiently smooth. Fig.17 Although the transfer laminate is laminated to both surfaces of the support (D), the transfer laminate may be laminated to only one surface, and another conductive pattern such as copper foil may be laminated to the other surface.
[0399] Fig.18 is using Figure 3 In the case of the transfer laminate obtained in , the front and back surfaces of the support (D) are electrically connected via through holes, and a method for producing a conductive pattern by a semi-additive process.
[0400] After the smooth surface of a smooth metal foil or a heat-resistant film is laminated to at least one surface of a support (D) having projections and depressions by using a hot press or the like, the laminated metal foil or the heat-resistant film is removed to smooth the support (D), and then a transfer laminate having a plated base layer (B) and a resin layer (C) formed on the entire surface of a temporary support (A) is laminated on the surface having the resin layer (C) formed thereon to the smoothed surface of the support (D), and then the temporary support (A) is peeled off to form the resin layer (C) on the surface of the support (D). and the above-mentioned plated base layer (B), then, forming a pattern resist on the surface of the plated base layer (B), then, forming a metal plated layer (E) on the above-mentioned plated base layer (B), then, peeling off the pattern resist, and removing the above-mentioned plated base layer (B) except for the formation portion of the metal plated layer (E) which becomes a conductive pattern by an etching liquid, then, forming a through hole penetrating both sides from the surface of the above-mentioned metal plated layer (E), then, filling the above-mentioned through hole with a conductive paste to make the through hole conductive. In the method for manufacturing a conductive pattern Fig.18 Although the support (D) is smoothed in the embodiment, this is not necessarily required if the surface is sufficiently smooth. Fig.18 Although the transfer laminate is laminated to both surfaces of the support (D), the transfer laminate may be laminated to only one surface, and another conductive pattern such as copper foil may be laminated to the other surface.
[0401] Fig.19 is using Figure 3 In the case of a transfer laminate obtained in the process, a support (D) is adhered to a substrate having a conductive pattern, and the surface of the support (D) is smoothed, and the surface of the support (D) is electrically connected to the conductive pattern of the inner layer through non-through holes, thereby providing a method for manufacturing a conductive pattern by a semi-additive process.
[0402] A support (D) and a smooth metal foil or a heat-resistant film are sequentially stacked on at least one side of a substrate having a conductive pattern formed thereon, and after the support (D) is smoothed by removing the metal foil or the heat-resistant film, a transfer laminate having a plated base layer (B) and a resin layer (C) formed on the entire surface of a temporary support (A) is laminated on the surface of the support (D) on the surface of the transfer laminate having the resin layer (C) formed thereon, and then the transfer laminate is laminated from the temporary support (A) to the conductive pattern of the inner layer. A method for producing a conductive pattern in which a non-through hole is formed, and then any one of palladium, conductive polymer, carbon, and conductive paste is applied to the surface of the transfer stack and the non-through hole to make the surface of the non-through hole conductive, and then the temporary support (A) is peeled off and a pattern resist is formed on the surface of the plated base layer (B), and then a metal plating layer (E) is formed on the plated base layer (B) and the non-through hole, and then the pattern resist is peeled off and the plated base layer (B) except for the portion where the metal plating layer (E) that becomes the conductive pattern is removed by an etching solution. Fig.19 The support (D) is smoothed, but this is not necessarily necessary when the surface is sufficiently smooth. Fig.19 The support (D) is bonded to both surfaces of the substrate having the conductive pattern formed thereon, and the transfer laminate is further bonded thereto. However, the support (D) and the transfer laminate may be bonded to only one surface, and the support (D) and another conductive pattern such as copper foil may be bonded to the other surface.
[0403] Fig. 20 is using Figure 3 In the case of a transfer laminate obtained in the process, a support (D) is adhered to a substrate having a conductive pattern, and the surface of the support (D) is smoothed, and the surface of the support (D) is electrically connected to the conductive pattern of the inner layer through non-through holes, thereby providing a method for manufacturing a conductive pattern by a semi-additive process.
[0404] A support (D) and a smooth metal foil or a heat-resistant film are sequentially stacked on at least one side of a substrate having a conductive pattern formed thereon, and after being bonded together by thermocompression bonding, the metal foil or the heat-resistant film is removed to smoothen the surface of the support (D). Then, on the surface of the support (D), a transfer laminate having a plated base layer (B) and a resin layer (C) formed on the entire surface of a temporary support (A) is bonded to the smoothed surface of the support (D). Then, the conductive pattern from the temporary support (A) to the inner layer of the transfer laminate is A method for manufacturing a conductive pattern in which a non-through hole is formed, and then a metal film is formed on the surface of the transfer stack and the non-through hole using a dry plating method such as a vapor deposition method or a sputtering method to make the surface of the non-through hole conductive, and then the temporary support (A) is peeled off, and a pattern resist is formed on the surface of the plated base layer (B), and then a metal plating layer (E) is formed on the plated base layer (B) and the non-through hole, and then the pattern resist is peeled off and the plated base layer (B) except for the formation portion of the metal plating layer (E) that becomes the conductive pattern is removed by an etching solution. Fig. 20 The support (D) is smoothed, but this is not necessarily necessary when the surface is sufficiently smooth. Fig. 20 The support (D) is bonded to both surfaces of the substrate having the conductive pattern formed thereon, and the transfer laminate is further bonded thereto. However, the support (D) and the transfer laminate may be bonded to only one surface, and the support (D) and another conductive pattern such as copper foil may be bonded to the other surface.
[0405] Fig.21 is using Figure 3 In the case of a transfer laminate obtained in the process, a support (D) is adhered to a substrate having a conductive pattern, and the surface of the support (D) is smoothed, and the surface of the support (D) is electrically connected to the conductive pattern of the inner layer through non-through holes, thereby providing a method for manufacturing a conductive pattern by a semi-additive process.
[0406] A support (D) and a smooth metal foil or a heat-resistant film are sequentially stacked on at least one side of a substrate having a conductive pattern formed thereon, and after the support (D) is smoothed by removing the metal foil or the heat-resistant film, a transfer laminate having a plated base layer (B) and a resin layer (C) formed on the entire surface of a temporary support (A) is laminated on the surface of the support (D) so that the surface having the resin layer (C) is formed thereon, and then, a transfer laminate having a plated base layer (B) and a resin layer (C) formed thereon is laminated on the surface of the support (D) after smoothing, and then, a transfer laminate having a plated base layer (B) and a resin layer (C) is laminated on the surface of the temporary support (A) to form a transfer layer. (A) A method for manufacturing a conductive pattern comprising forming a non-through hole until the conductive pattern of the inner layer is formed, then peeling off the temporary support (A) and forming a pattern resist on the surface of the plated base layer (B), then forming a metal plated layer (E) on the plated base layer (B), then peeling off the pattern resist and removing the plated base layer (B) except for the portion where the metal plated layer (E) forming the conductive pattern is formed by an etching solution, then filling the non-through hole with a conductive paste to make the non-through hole conductive. Fig.21 The support (D) is smoothed, but this is not necessarily necessary when the surface is sufficiently smooth. Fig.21 The support (D) is bonded to both surfaces of the substrate having the conductive pattern formed thereon, and the transfer laminate is further bonded thereto. However, the support (D) and the transfer laminate may be bonded to only one surface, and the support (D) and another conductive pattern such as copper foil may be bonded to the other surface.
[0407] Fig. 22 is using Figure 3 In the case of a transfer laminate obtained in the process, a support (D) is adhered to a substrate having a conductive pattern, and the surface of the support (D) is smoothed, and the surface of the support (D) is electrically connected to the conductive pattern of the inner layer through non-through holes, thereby providing a method for manufacturing a conductive pattern by a semi-additive process.
[0408] A support (D) and a smooth metal foil or a heat-resistant film are sequentially laminated on at least one side of a substrate having a conductive pattern formed thereon, and after the laminate is laminated by thermocompression bonding, the metal foil or the heat-resistant film is removed to smooth the support (D), and then, on the surface of the support (D), a transfer laminate having a plated base layer (B) and a resin layer (C) formed on the entire surface of a temporary support (A) is laminated on the surface of the support (D) so that the surface having the resin layer (C) is formed thereon, and then, the temporary support (A) is peeled off, and a transfer laminate having a plated base layer (B) and a resin layer (C) is formed on the surface of the support (D). The resin (C) and the plated base layer (B) are then formed with a pattern resist on the surface of the plated base layer (B), and then a metal plated layer (E) is formed on the plated base layer (B). Then, the pattern resist is peeled off, and the plated base layer (B) except for the formation portion of the metal plated layer (E) which becomes a conductive pattern is removed by an etching solution, and then a non-through hole is formed from the metal plated layer (E) to the conductive pattern of the inner layer, and then a conductive paste is filled in the non-through hole to make the non-through hole conductive. In the method for manufacturing a conductive pattern. Fig. 22 The support (D) is smoothed, but this is not necessarily necessary when the surface is sufficiently smooth. Fig. 22 The support (D) is bonded to both surfaces of the substrate having the conductive pattern formed thereon, and the transfer laminate is further bonded thereto. However, the support (D) and the transfer laminate may be bonded to only one surface, and the support (D) and another conductive pattern such as copper foil may be bonded to the other surface.
[0409] By using the stack of the transfer stack of the present invention and the method for manufacturing a conductive pattern using the transfer stack, a seed layer that is stable in quality and serves as a plating base can be formed without causing damage to the plating base layer due to contact with a coating device or a conveying roller during coating, and a substrate that has excellent adhesion between a support and a metal layer (metal plating layer), and has a circuit pattern with a smooth surface having high adhesion, good design reproducibility, and good rectangular cross-sectional shape on various smooth substrates. Therefore, by using the semi-additive method stack of the present invention, high-density, high-performance printed circuit board substrates and printed circuit boards of various shapes and sizes can be provided at low cost, and the industrial utilization in the field of printed circuit boards is high. In addition, by the laminated body of the transfer laminated body of the present invention or the manufacture method of the conductive pattern of the transfer laminated body, it can be suitably used as a printed circuit board for high-speed transmission, a rigid printed circuit board, a flexible printed circuit board, a conductive film for touch panel, a metal mesh for touch panel, an organic solar cell, an organic EL assembly, an organic transistor, a contactless IC card and other RFID, electromagnetic wave shielding, LED lighting substrates, digital signage, packaging substrates, ceramic substrates, glass substrates, silicon wafer substrates, metal substrates and other electronic components. In addition, it can be suitably used as decorative plating, molded circuit components (MID) of molded products. Especially the most suitable high-speed rigid printed circuit board and high-speed flexible printed circuit board applications requiring high-frequency transmission.
[0410] Example
[0411] Hereinafter, the present invention will be described in detail by way of examples. In addition, the present invention is not limited in any way by the following examples.
[0412] [Preparation Example 1: Preparation of coating liquid (1) for forming plating base layer (B)]
[0413] Under a nitrogen atmosphere, a chloroform solution (30 ml) containing 9.6 parts by mass of p-toluenesulfonyl chloride was added dropwise over 30 minutes to a mixture containing 20 parts by mass of methoxypolyethylene glycol (number average molecular weight 2,000), 8.0 parts by mass of pyridine and 20 ml of chloroform while stirring under ice cooling. The mixture was stirred at a bathtub temperature of 40° C. for 4 hours, and 50 ml of chloroform was added to mix.
[0414] The obtained product was then washed with 100 ml of a 5% by mass hydrochloric acid aqueous solution, then washed with 100 ml of a saturated sodium bicarbonate aqueous solution, and then washed with 100 ml of a saturated saline aqueous solution, dried over anhydrous magnesium sulfate, filtered, and concentrated under reduced pressure. After washing with hexane several times, the product was filtered and dried under reduced pressure at 80° C. to obtain methoxypolyethylene glycol having a p-toluenesulfonyloxy group.
[0415] 5.39 parts by mass of methoxypolyethylene glycol having a p-toluenesulfonyloxy group, 20 parts by mass of polyethyleneimine (manufactured by Aldrich, molecular weight 25,000), 0.07 parts by mass of potassium carbonate, and 100 ml of N,N-dimethylacetamide were mixed and stirred at 100° C. for 6 hours under a nitrogen atmosphere.
[0416] Then, 300 ml of a mixed solution of ethyl acetate and hexane (volume ratio of ethyl acetate / hexane = 1 / 2) was added, and after vigorous stirring at room temperature, the solid product was filtered out. The solid was washed with 100 ml of a mixed solution of ethyl acetate and hexane (volume ratio of ethyl acetate / hexane = 1 / 2), and then dried under reduced pressure to obtain a compound in which polyethylene glycol was bonded to polyethyleneimine.
[0417] 138.8 parts by mass of an aqueous solution containing 0.592 parts by mass of the obtained compound of polyethylene glycol bonded to polyethylene imine was mixed with 10 parts by mass of silver oxide, and stirred for 30 minutes at 25° C. Then, 46 parts by mass of dimethylethanolamine was slowly added while stirring, and stirred for 30 minutes at 25° C. Then, 15.2 parts by mass of a 10% by mass ascorbic acid aqueous solution was slowly added while stirring, and stirring was continued for 20 hours to obtain a silver dispersion.
[0418] After adding 200 ml of a mixed solvent of isopropanol and 200 ml of hexane to the obtained silver dispersion and stirring for 2 minutes, centrifugal concentration was performed at 3000 rpm for 5 minutes. After removing the supernatant, a mixed solvent of 50 ml of isopropanol and 50 ml of hexane was added to the precipitate and stirred for 2 minutes, and then centrifugal concentration was performed at 2000 rpm for 10 minutes. After removing the supernatant, 20 parts by mass of water were further added to the precipitate and stirred for 2 minutes, and the organic solvent was removed under reduced pressure. After further adding 10 parts by mass of water and stirring and dispersing, the dispersion was placed in a refrigerator at -40°C for one day and one night for freezing, and treated with a freeze dryer (FDU-2200 manufactured by Tokyo Rika Instruments Co., Ltd.) for 24 hours, thereby obtaining silver particles having a gray-green metallic luster and composed of flaky blocks containing a dispersant having a basic nitrogen atom group.
[0419] The obtained powder of silver particles containing a dispersant having a basic nitrogen atom group was dispersed in a mixed solvent of 45 parts by mass of ethanol and 55 parts by mass of ion exchange water to prepare a 5% by mass coating solution (1) for forming a plating base layer (B). The proportion of the dispersant in the obtained silver particles was calculated from the ash content after heating at 500° C. for 1 hour in an electric furnace, and it was confirmed that it was 5% by mass relative to 100% by mass of the silver solid content.
[0420] [Preparation Example 2: Preparation of coating liquid (2) for forming plating base layer (B)]
[0421] 32 parts by mass of methyl ethyl ketone and 32 parts by mass of ethanol were added to a reaction container equipped with a stirrer, a reflux condenser, a nitrogen inlet tube, a thermometer, and a dropping funnel, and the temperature was raised to 80° C. under a nitrogen flow. Subsequently, a mixture of 20 parts by mass of 2-(methacryloyloxy)ethyl phosphate, 70 parts by mass of methoxypolyethylene glycol methacrylate (molecular weight 1,000), 10 parts by mass of glycidyl methacrylate, 4.1 parts by mass of mercaptopropylcarboxylate, and 80 parts by mass of methyl ethyl ketone, a polymerization initiator ("V-65" manufactured by Wako Pure Chemical Industries, Ltd., 0.5 parts by mass of 2,2'-azobis(2,4-dimethylvaleronitrile)), and 5 parts by mass of methyl ethyl ketone were added dropwise from different dropping funnels over 2 hours while stirring under a nitrogen atmosphere.
[0422] Then, 0.3 parts by mass of a polymerization initiator ("PERBUTYL O", tert-butyl peroxy-2-ethylhexanoate, manufactured by NOF Corporation) was added twice every 4 hours, and the mixture was stirred at 80°C for 12 hours. Deionized water was added to the obtained resin solution for phase inversion emulsification, and after desolventizing under reduced pressure, deionized water was added to adjust the concentration to obtain a 76.8% by mass aqueous solution of a non-volatile acrylic resin having a phosphate group and an epoxy group. The weight average molecular weight of the acrylic resin was 4,200, and the acid value was 96.2 mgKOH / g.
[0423] Next, 5.56 g (53 mmol) of an 85% by mass aqueous solution of N,N-diethylhydroxylamine, 138 mg of a 76.8% by mass aqueous dispersion of an acrylic resin having a phosphate group and an epoxy group, and 15 g of deionized water were mixed to prepare a reducing agent solution.
[0424] On the other hand, 200 mg of a 76.8% aqueous dispersion of an acrylic resin having a phosphate group and an epoxy group was dissolved in 5 g of water, and a solution of 6.00 g (35.3 mmol) of silver nitrate dissolved in 10 g of water was added and stirred. The reducing agent solution obtained above was added dropwise to the mixture at 25°C for 2 hours. After the addition was completed, the reaction was terminated by stirring for 3 hours. Thereafter, the obtained solution was filtered with a membrane filter (pore diameter 0.45 μm). Subsequently, ion exchange water was added to adjust the non-volatile component to 5% by mass, and a coating solution (2) for forming a plating base layer (B) was obtained. For the obtained silver particles, the proportion of the dispersant was calculated from the ash content after heating at 500°C for 1 hour in an electric furnace, and the result confirmed that it was 8% by mass relative to 100% by mass of the silver solid content.
[0425] [Preparation Example 3: Preparation of coating liquid (1) for forming resin layer (C)]
[0426] 60 parts by mass of phenoxy resin 4250 (bisphenol A / bisphenol F mixed type manufactured by Mitsubishi Chemical Corporation, molecular weight 60,000, solid content 100% by mass), 33 parts by mass of aminotriazine novolac resin ("Phenolite LA-7052" manufactured by DIC Corporation, solid content 60% by mass), 17 parts by mass of epoxy resin ("EPICLON EXA-830CRP" manufactured by DIC Corporation; bisphenol F type epoxy resin, epoxy group equivalent 162 g / equivalent), 3 parts by mass of trimellitic anhydride, and 0.5 parts by mass of "TBZ" manufactured by Shikoku Chemicals Co., Ltd. as a curing catalyst were mixed, diluted with cyclohexanone so that the non-volatile component became 2% by mass, and uniformly mixed to obtain a coating liquid (1) for forming a resin layer (C).
[0427] [Preparation Example 4: Preparation of coating liquid (2) for forming resin layer (C)]
[0428] In a nitrogen-substituted container equipped with a thermometer, a nitrogen inlet pipe, and a stirrer, 100 parts by mass of a polyester polyol (a polyester polyol obtained by reacting 1,4-cyclohexanedimethanol, neopentyl glycol, and adipic acid), 17.6 parts by mass of 2,2-dimethylolpropionic acid, 21.7 parts by mass of 1,4-cyclohexanedimethanol, and 106.2 parts by mass of dicyclohexylmethane-4,4'-diisocyanate were reacted in a mixed solvent of 178 parts by mass of methyl ethyl ketone to obtain a polyurethane prepolymer solution having an isocyanate group at the terminal.
[0429] Next, 13.3 parts by mass of triethylamine was added to the polyurethane prepolymer solution to neutralize the carboxyl groups of the polyurethane prepolymer, and 380 parts by mass of water was added and stirred sufficiently to obtain an aqueous dispersion of the polyurethane prepolymer.
[0430] 8.8 parts by mass of a 25% by mass aqueous solution of ethylenediamine was added to the aqueous dispersion of the polyurethane prepolymer obtained above and stirred to extend the polyurethane prepolymer chain. The polyurethane prepolymer was then aged and desolventized to obtain an aqueous dispersion of a polyurethane resin (30% by mass of nonvolatile components). The weight average molecular weight of the polyurethane resin was 53,000.
[0431] Next, 140 parts by mass of deionized water and 100 parts by mass of the aqueous dispersion of the polyurethane resin obtained above were added to a reaction vessel equipped with a stirrer, a reflux condenser, a nitrogen inlet tube, a thermometer, a dropping funnel for dropping a monomer mixture, and a dropping funnel for dropping a polymerization catalyst, and the temperature was raised to 80° C. while blowing nitrogen. Thereafter, a monomer mixture composed of 60 parts by mass of methyl methacrylate, 30 parts by mass of n-butyl acrylate, and 10 parts by mass of N-n-butoxymethyl acrylamide and 20 parts by mass of a 0.5% by mass ammonium persulfate aqueous solution were added dropwise from different dropping funnels over 120 minutes while the temperature in the reaction vessel was kept at 80° C. while stirring.
[0432] After the completion of the dropwise addition, the mixture was stirred at the same temperature for 60 minutes, and then the temperature in the reaction container was cooled to 40°C, diluted with deionized water so that the non-volatile component became 2% by mass, and filtered using a 200-mesh filter cloth to obtain a core-shell type composite resin, i.e., a coating liquid (2) for forming a resin layer (C), in which the polyurethane resin is made into a shell layer and an ethylene-based resin made of methyl methacrylate or the like as a raw material is made into a core layer.
[0433] <Preparation Example 5: Preparation of Transfer Laminated Body (1)>
[0434] The coating solution (1) for forming the plated base layer (B) obtained in Preparation Example 1 was applied to the surface of a release film ("TN-200", a release PET film manufactured by Toyobo Co., Ltd.; thickness 38 μm) on which a release layer was formed using a desktop small-sized coating machine ("K Printing Proofer" manufactured by RK Print Coat Instruments), and dried at 150°C for 5 minutes to coat a silver layer corresponding to the plated base layer (B) in such a manner that the thickness after drying becomes 0.1 μm. The plated base layer (B) on the release film was analyzed using a glow discharge luminescence analyzer, and the result showed that the signal intensity of carbon atoms present at the interface between air and the plated base layer (B) was 0.89, and the signal intensity of carbon atoms present at the interface between the plated base layer (B) and the release film was 0.43.
[0435] Thereafter, the coating liquid (1) for forming the resin layer (C) obtained in Preparation Example 3 was applied using a desktop small-sized coating machine ("KPrinting Proofer" manufactured by RK Print Coat Instruments) and dried at 180°C for 3 minutes, thereby coating a layer corresponding to the above-mentioned resin layer (C) in a manner to have a thickness of 0.3 μm after drying, thereby forming a plated base layer (B) and a resin layer (C) on the surface of the release film corresponding to the above-mentioned temporary support (A), and obtaining a transfer laminate (1). A cutter was used to cut 100 squares of 1 mm on the surface formed with the resin layer (C), and a checkerboard peeling test was performed using an adhesive tape. As a result, all 100 squares were peeled off at the interface between the release film and the plated base layer (B), thus confirming that the basic nitrogen atom-containing group of the dispersant (b1) contained in the plated base layer (B) reacted with the epoxy group of the epoxy resin contained in the resin layer (C) and the carboxylic acid derived from trimellitic acid to form a chemical bond.
[0436] <Preparation Example 6: Preparation of Transfer Laminated Body (2)>
[0437] The coating solution (1) for forming the plating base layer (B) obtained in Preparation Example 1 was applied to the glossy surface (non-roughened surface) of a copper foil ("F2-WS" copper foil manufactured by Furukawa Electric Co., Ltd.; thickness 18 μm) using a small desktop coater ("K Printing Proofer" manufactured by RK Print Coat Instruments), and dried at 200°C for 5 minutes to coat a silver layer corresponding to the plating base layer (B) so that the thickness after drying becomes 0.1 μm. The plating base layer (B) on the copper foil was analyzed using a glow discharge luminescence analyzer. The result showed that the signal intensity of carbon atoms present at the interface between air and the plating base layer (B) was 0.85, and the signal intensity of carbon atoms present at the interface between the plating base layer (B) and the copper foil was 0.3.
[0438] Thereafter, the coating liquid (1) for forming the resin layer (C) obtained in Preparation Example 3 was applied using a small desktop coater ("K Printing Proofer" manufactured by RK Print Coat Instruments) and dried at 180°C for 3 minutes to coat a layer corresponding to the above-mentioned resin layer (C) in such a manner that the thickness after drying becomes 0.3 μm. Furthermore, the coating liquid (2) for forming the resin layer (C) obtained in Preparation Example 4 was applied using a small desktop coater ("K Printing Proofer" manufactured by RK Print Coat Instruments) and dried at 120°C for 5 minutes to coat a layer corresponding to the above-mentioned resin layer (C) in such a manner that the thickness after drying becomes 0.2 μm, thereby forming a plating base layer (B) and a resin layer (C) on the surface of the copper foil corresponding to the above-mentioned temporary support (A), thereby obtaining a transfer laminate (2). A cutter was used to cut 100 squares of 1 mm on the surface on which the resin layer (C) was formed, and a checkerboard peeling test was performed using an adhesive tape. The result showed that all 100 squares peeled off at the interface between the copper foil and the plated base layer (B). Therefore, it was confirmed that the basic nitrogen atom-containing group contained in the dispersant (b1) contained in the plated base layer (B) reacted with the epoxy group of the epoxy resin contained in the resin layer (C) or the carboxylic acid derived from trimellitic anhydride to form a chemical bond.
[0439] <Preparation Example 7: Preparation of Transfer Laminated Body (3)>
[0440] On the surface of a release film ("TN-200" manufactured by Toyobo Co., Ltd., release PET film; thickness 38 μm) on which a release layer was formed, the coating liquid (2) for forming the plated base layer (B) obtained in Preparation Example 2 was formed into a grid pattern with a line width of 5 mm and a line spacing of 5 mm using an inkjet printer ("Inkjet Tester EB100" manufactured by Konica Minolta Co., Ltd., evaluation print head KM512L, discharge volume 42 pL), and dried at 150° C. for 5 minutes, thereby printing a silver layer corresponding to the plated base layer (B) so that the thickness after drying becomes 0.1 μm. The plated base layer (B) on the copper foil was analyzed using a glow discharge luminescence analyzer, and the result showed that the signal intensity of carbon atoms present at the interface between air and the plated base layer (B) was 0.5, and the signal intensity of carbon atoms present at the interface between the plated base layer (B) and the release film was 0.1.
[0441] Thereafter, the coating liquid (1) for forming the resin layer (C) obtained in Preparation Example 3 was applied using a small desktop coating machine ("KPrinting Proofer" manufactured by RK Print Coat Instruments) and dried at 180°C for 3 minutes, thereby coating a layer corresponding to the above-mentioned resin layer (C) in a manner to have a thickness of 0.3 μm after drying, thereby forming a plated base layer (B) and a resin layer (C) on the surface of the release film corresponding to the above-mentioned support (A), and obtaining a transfer laminate (3). A cutter was used to cut 100 squares of 1 mm square on the surface formed with the resin layer (C), and a checkerboard peeling test was performed using an adhesive tape. As a result, all 100 squares were peeled off at the interface between the release film and the plated base layer (B), thereby confirming that the phosphate group of the dispersant (b1) contained in the plated base layer (B) reacted with the amino group derived from the aminotriazine novolac resin contained in the resin layer (C) to form a chemical bond.
[0442] <Preparation Example 8: Preparation of Deposited Film>
[0443] 3 parts by mass of a bisphenol epoxy resin ("ZX059" manufactured by Nippon Steel Chemical Co., Ltd., a mixture of bisphenol A type:bisphenol F type = 1:1, epoxy equivalent of about 169), 3 parts by mass of a naphthalene epoxy resin ("HP-4032D" manufactured by DIC Corporation, epoxy equivalent of about 144), 12 parts by mass of a crystalline bifunctional epoxy resin ("YX4000HK" manufactured by Mitsubishi Chemical Corporation, epoxy equivalent of about 185), 9 parts by mass of a dicyclopentadiene epoxy resin ("HP7200H" manufactured by DIC Corporation, epoxy equivalent of about 275), and 10 parts by mass of a phenoxy resin ("YX7200B35" manufactured by Mitsubishi Chemical Corporation, a MEK solution having a solid content of 35% by mass) were dissolved in 30 parts by mass of solvent naphtha while stirring and heating. After cooling to room temperature, 40 parts by mass of an active ester compound ("HPC-8000-65T" manufactured by DIC Corporation, a toluene solution containing 65% by mass of nonvolatile components with an active group equivalent of about 223), 3 parts by mass of a curing accelerator (4-dimethylaminopyridine, a MEK solution containing 5% by mass of solid content), and spherical silica (average particle size 0.25 μm, "SO-C1" manufactured by Admatechs Corporation, carbon content per unit surface area 0.36 mg / m2) surface-treated with a phenylaminosilane coupling agent ("KBM573" manufactured by Shin-Etsu Chemical Co., Ltd.) were mixed therein. 2) 140 parts by mass, and uniformly dispersed by a high-speed rotary mixer to prepare a resin varnish. Then, the resin varnish was uniformly applied on a release surface of a release PET film (thickness 38 μm) so that the thickness of the resin composition layer after drying became 30 μm, and dried at 80 to 120° C. (average 100° C.) for 4 minutes to prepare a deposition film.
[0444] <Preparation Example 9: Preparation of Silver Etching Solution (1)>
[0445] 2.6 parts by mass of acetic acid was added to 47.4 parts by mass of water, and 50 parts by mass of 35% by mass hydrogen peroxide water was further added to prepare a silver etching solution (1). The molar ratio of hydrogen peroxide to carboxylic acid (hydrogen peroxide / carboxylic acid) in the silver etching solution (1) was 13.6, and the content ratio of the mixture of hydrogen peroxide and carboxylic acid in the silver etching solution (1) was 22.4% by mass.
[0446] (Example 1)
[0447] The polyimide film (Kapton 150EN-A manufactured by DuPont Toray Co., Ltd.) was subjected to corona treatment on both sides ("Corona Surface Modification Evaluation Device TEC-4AX" manufactured by Kasuga Electric Co., Ltd., electrode-substrate distance 0.5 mm, 100 W). Thereafter, the surface of the transfer laminate (1) obtained in Preparation Example 5 on which the resin layer (C) was formed was attached to both sides of the polyimide film, and thermally pressed using a laminator ("Small Desktop Test Laminator" manufactured by TESTER SANGYO Co., Ltd.) with a roller material of metal-metal, a roller temperature of 160°C, an air input pressure of 0.4 MPa, and a roller speed of 1 m / min. Subsequently, only the release film of the transfer laminate (1) thermally pressed to both sides of the polyimide film was peeled off, thereby forming the resin layer (C) and the plated base layer (B) on both sides of the polyimide film. The surface resistance of the plated base layer (B) was 20Ω / □ on both the front and back surfaces. Thereafter, drying was performed at 250° C. for 5 minutes, so that the surface resistance of the plated base layer (B) was 1Ω / □ on both the front and back surfaces.
[0448] Thereafter, the plated base layer (B) obtained above was set as the cathode side, the phosphorus-containing copper was set as the anode side, and an electrolytic plating solution containing copper sulfate was used at a current density of 2 A / dm 2 Electrolytic plating was performed for 27 minutes to form a copper plating layer (film thickness 12 μm) corresponding to the metal plating layer (E) on the plated base layer (B). As the electrolytic plating solution, 70 g / L of copper sulfate, 200 g / L of sulfuric acid, 50 mg / L of chloride ions, and 5 ml / L of additives (Top Lucina SF-M, Okuno Pharmaceutical Co., Ltd.) were used.
[0449] In this manner, a laminate (1) is obtained in which the support (D), the resin layer (C), the plating base layer (B), and the metal plating layer (E) are laminated in this order.
[0450] (Example 2)
[0451] A laminate (2) in which a support (D), a resin layer (C), a plated base layer (B), and a metal plated layer (E) were sequentially laminated was obtained by the same method except that the transfer laminate (2) prepared in Preparation Example 6 was used instead of the transfer laminate (1) used in Example 1. In addition, the surface resistance of the plated base layer (B) after the transfer laminate was thermally pressed and the temporary support (A) was peeled off was 10Ω / □ on both the front and back sides. In addition, the surface resistance of the plated base layer (B) after drying at 250°C for 5 minutes was 0.5Ω / □ on both the front and back sides.
[0452] (Example 3)
[0453] A stack (3) in which a support (D), a resin layer (C), a plated base layer (B) and a metal plated layer (E) are sequentially stacked is obtained by the same method except that the transfer stack (3) prepared in Preparation Example 7 is used instead of the transfer stack (1) used in Example 1. The metal plated layer (E) has a lattice pattern like the conductive pattern of the plated base layer (B). In addition, the surface resistance of the plated base layer (B) after the transfer stack is hot-pressed and the temporary support (A) is peeled off is 50Ω / □ on both the front and back sides. In addition, the surface resistance of the plated base layer (B) after drying at 250°C for 5 minutes is 10Ω / □ on both the front and back sides.
[0454] (Example 4)
[0455] The glossy side (non-roughened side) of the copper foil (F2-WS manufactured by Furukawa Electric Co., Ltd., thickness 18 μm) was attached to both sides of the prepreg (R-5670KG manufactured by Panasonic Co., Ltd., containing glass fiber, thickness 0.1 mm, surface roughness Sz: 20.815 μm), and hot-pressed at 195°C for 90 minutes using a hand press ("Mini testpress" manufactured by Toyo Seiki Seisaku-sho Co., Ltd.). Thereafter, the entire surface of the copper foil was etched by immersing it in a ferric chloride etching solution (content 40% by mass) at 40°C for 3 minutes, thereby obtaining a rigid substrate equivalent to the above-mentioned support (D) obtained by curing the prepreg. It was confirmed that the surface roughness Sz of the rigid substrate was 4.215 μm and was smoothed. Thereafter, both sides of the above-mentioned rigid substrate were subjected to corona treatment ("Corona Surface Modification Evaluation Device TEC-4AX" manufactured by Kasuga Electric Co., Ltd., electrode-substrate distance 0.5 mm, 100 W). Next, the surface of the transfer laminate (2) obtained in Preparation Example 6 on which the resin layer (C) was formed was attached to both surfaces of the above-mentioned rigid substrate and pressed at 175°C for 1 minute using a hand press ("Minitest press" manufactured by Toyo Seiki Seisaku-sho Co., Ltd.).
[0456] Then, a drill is used to form a through hole (through hole) with a diameter of 100 μm from the surface of the copper foil of the temporary support (A) of the transfer stack (2) to the copper foil of the temporary support on the opposite side. Then, in order to remove the dirt (smear) generated by the drill processing, the smear is removed by plasma treatment. Thereafter, the substrate with through holes obtained in the above manner is passed through the black hole process (adjustment-carbon adsorption treatment-etching) of MacDermid Company to attach carbon to the surface of the through hole and dry the film. Then, the copper foil equivalent to the temporary support (A) attached with carbon is peeled off, thereby making a stack having a resin layer (C) and a plated base layer (B) formed on the surface of the rigid substrate and carbon attached to the through hole. The front and back sides of the plated base layer (B) on the rigid substrate are inspected using a testing machine, and it is confirmed that the conductivity is ensured by electrical connection between the front and back sides. The surface resistance of the plated base layer (B) was 10Ω / □ on both the front and back surfaces.
[0457] Thereafter, the plated base layer (B) obtained above was set as the cathode side, the phosphorus-containing copper was set as the anode side, and an electrolytic plating solution containing copper sulfate was used at a current density of 2 A / dm 2Electrolytic plating was performed for 27 minutes to form a copper plating layer (film thickness 12 μm) corresponding to the metal plating layer (E) on the plated base layer (B) and the through-holes. As the electrolytic plating solution, 70 g / L of copper sulfate, 200 g / L of sulfuric acid, 50 mg / L of chloride ions, and 5 ml / L of additives (Top Lucina SF-M, Okuno Pharmaceutical Co., Ltd.) were used.
[0458] In this way, a laminate (4) is obtained in which the support (D), the resin layer (C), the plated base layer (B), and the metal plated layer (E) are laminated in this order and the through holes are subjected to a conductive treatment.
[0459] (Example 5)
[0460] The same method as in Example 4 was used except that sputtering was used instead of the black hole process (conditioning - carbon adsorption treatment - etching) of MacDermid Company used in the conductive treatment of the through-holes in Example 4. Regarding the conditions of the sputtering method, the substrate with through-holes was loaded into the sputtering device, and copper was installed as a sputtering target. Thereafter, the chamber was evacuated until the pressure in the chamber reached 1.0×10 -3 Pa or less, argon gas as a sputtering gas is supplied to the chamber at a flow rate of 200 sccm, so that the pressure in the chamber becomes 0.3 Pa. While maintaining the temperature of the substrate with through holes at 75°C, a metal layer composed of copper is stacked to a thickness of 100 nm by sputtering of a copper target. In addition, the surface resistance of the plated base layer (B) after the transfer stack is hot-pressed and the temporary support (A) is peeled off is 10Ω / □ on both the front and back sides. In this way, a stack (5) is obtained in which a support (D), a resin layer (C), a plated base layer (B) and a metal plating layer (E) are stacked in sequence, and the through holes are conductively treated.
[0461] (Example 6)
[0462] The glossy side (non-roughened side) of the copper foil (F2-WS manufactured by Furukawa Electric Co., Ltd., thickness 18 μm) was attached to both sides of the prepreg (R-5670KG manufactured by Panasonic Co., Ltd., containing glass fiber, thickness 0.1 mm, surface roughness Sz: 20.815 μm), and the prepreg was heat-pressed at 195°C for 90 minutes using a hand press ("Mini testpress" manufactured by Toyo Seiki Seisaku-sho Co., Ltd.). Thereafter, the entire surface of the copper foil was etched by immersing it in a 40°C ferric chloride etching solution (content 40% by mass) for 3 minutes to obtain a rigid substrate equivalent to the above-mentioned support (D) obtained by curing the prepreg. It was confirmed that the surface roughness of the rigid substrate was Sz 4.215 μm and was smoothed. Thereafter, both sides of the above-mentioned rigid substrate were subjected to corona treatment ("Corona Surface Modification Evaluation Device TEC-4AX" manufactured by Kasuga Electric Co., Ltd., electrode-substrate distance 0.5 mm, 100 W). Next, the surface of the transfer laminate (1) obtained in Preparation Example 5 on which the resin layer (C) was formed was attached to both surfaces of the above-mentioned rigid substrate and pressed at 175°C for 1 minute using a hand press ("Mini test press" manufactured by Toyo Seiki Seisaku-sho Co., Ltd.).
[0463] Then, a drill is used to form a through hole (through hole) with a diameter of 100 μm from the surface of the release film corresponding to the temporary support (A) of the transfer stack (1) to the release film corresponding to the temporary support (A) on the opposite side. Then, in order to remove the dirt (smear) generated by the drill hole processing, the smear is removed by plasma treatment. Thereafter, only the release film corresponding to the temporary support (A) is peeled off from the substrate with through holes obtained in the above manner, and a resin layer (C) and a plated base layer (B) are formed on the surface of the rigid substrate. The surface resistance of the plated base layer (B) is 20Ω / □ on both the front and back sides. Thereafter, it is dried at 250°C for 5 minutes, so that the surface resistance of the plated base layer (B) is 1Ω / □ on both the front and back sides.
[0464] Thereafter, the plated base layer (B) obtained above was set as the cathode side, the phosphorus-containing copper was set as the anode side, and an electrolytic plating solution containing copper sulfate was used at a current density of 2 A / dm 2 Electrolytic plating was performed for 27 minutes to form a copper plating layer (film thickness 12 μm) corresponding to the metal plating layer (E) on the plated base layer (B). As the electrolytic plating solution, 70 g / L of copper sulfate, 200 g / L of sulfuric acid, 50 mg / L of chloride ions, and 5 ml / L of additives (Top Lucina SF-M, Okuno Pharmaceutical Co., Ltd.) were used.
[0465] Next, in order to conduct electricity to the through-holes of the substrate with through-holes, a conductive paste ("LS-411MK" manufactured by Asahi Kagaku Co., Ltd.) was used and printed by screen printing to fill the through-holes, and then dried at 150° C. for 30 minutes.
[0466] In this way, a laminate (6) is obtained in which the support (D), the resin layer (C), the plated base layer (B), and the metal plated layer (E) are laminated in this order and the through holes are subjected to a conductive treatment.
[0467] (Example 7)
[0468] A core material ("CCL-HL832NB" manufactured by Mitsubishi Gas Chemical Co., Ltd., substrate thickness 0.1 mm, copper foil 12 μm) with copper foil laminated on both sides was prepared to produce an inner layer plate with a conductive pattern. Thereafter, the surface of the deposited film produced in Preparation Example 8 on the opposite side to the release PET film was set on the surface of the conductive pattern of the inner layer plate, and laminated using a batch vacuum pressurizing laminator. The pressure was reduced for 30 seconds to make the air pressure below 13 hPa, and then pressed at 100°C and 0.7 MPa for 30 seconds. Thereafter, the release PET film was peeled off by heating at 170°C for 15 minutes. The surface roughness was Sz 8.010 μm.
[0469] Then, the glossy surface (non-roughened surface) of the copper foil (F2-WS manufactured by Furukawa Electric Co., Ltd., thickness 18 μm) was attached to the surface of the deposited film and thermally pressed at 195° C. for 90 minutes using a hand press ("Mini testpress" manufactured by Toyo Seiki Seisaku-sho Co., Ltd.). Then, the copper foil was immersed in a ferric chloride etching solution (content 40% by mass) at 40° C. for 3 minutes to perform full-surface etching on the copper foil, thereby obtaining a cured deposited film corresponding to the support (D) described above. It was confirmed that the surface roughness of the deposited film was Sz2.125 μm and that it was smoothed.
[0470] Thereafter, the surface of the deposited film was subjected to corona treatment ("Corona surface modification evaluation device TEC-4AX" manufactured by Kasuga Electric Co., Ltd., electrode-substrate distance 0.5 mm, 100 W), and then, the surface of the transfer laminate (2) obtained in Preparation Example 6 on which the resin layer (C) was formed was attached to the surface of the deposited film and pressed at 175°C for 1 minute using a hand press ("Mini test press" manufactured by Toyo Seiki Seisaku-sho Co., Ltd.).
[0471] Then, in order to form a non-through hole from the surface of the copper foil equivalent to the temporary support (A) of the transfer stack (2) to the conductive pattern of the inner layer board, a non-through hole with a diameter of 100 μm is formed using a laser. Then, in order to remove the dirt (smear) generated by laser processing, the smear is removed by plasma treatment. Thereafter, the substrate with non-through holes obtained in the above manner is passed through the shadow process (adjustment-carbon adsorption treatment-etching) of MacDermid Company to attach carbon to the surface of the non-through holes, and the film is dried. Then, the copper foil equivalent to the temporary support (A) attached with carbon is peeled off, thereby making a stack having a resin layer (C) and a plated base layer (B) formed on the surface of the deposited film and carbon adsorbed in the non-through holes. The plated base layer (B) on the deposited film and the conductive pattern of the inner layer board are inspected using a testing machine to confirm that the surface and the inner layer board are electrically connected and the conductivity is ensured. The surface resistance of the plating base layer (B) was 10Ω / □.
[0472] Thereafter, the plated base layer (B) obtained above was set as the cathode side, the phosphorus-containing copper was set as the anode side, and an electrolytic plating solution containing copper sulfate was used at a current density of 2 A / dm 2 Electrolytic plating was performed for 27 minutes to form a copper plating layer (film thickness 12 μm) corresponding to the metal plating layer (E) on the plating base layer (B) and the surface of the non-through hole. As the electrolytic plating solution, 70 g / L of copper sulfate, 200 g / L of sulfuric acid, 50 mg / L of chloride ions, and 5 ml / L of additives (Top Lucina SF-M, Okuno Pharmaceutical Industry Co., Ltd.) were used.
[0473] In this way, a laminate (7) is obtained in which the support (D), the resin layer (C), the plated base layer (B) and the metal plated layer (E) are laminated in this order and the non-through holes are subjected to a conductive treatment.
[0474] (Example 8)
[0475] The same method as in Example 7 was used except that sputtering was used instead of the shadow process (conditioning - carbon adsorption treatment - etching) of MacDermid used in the conductive treatment of the non-through holes in Example 7. Regarding the conditions of the sputtering method, the substrate with the non-through holes was placed in the sputtering device, and copper was installed as a sputtering target. Thereafter, the chamber was evacuated until the pressure in the chamber reached 1.0×10 -3Pa or less, argon gas as a sputtering gas is supplied to the chamber at a flow rate of 200 sccm, so that the pressure in the chamber becomes 0.3 Pa. While maintaining the temperature of the substrate with non-through holes at 75°C, a metal layer composed of copper is stacked to a thickness of 100 nm by sputtering of a copper target. In addition, the temporary support (A) is peeled off, and the surface resistance of the plated base layer (B) before forming the metal plating layer (E) is measured, and the result is 10Ω / □. In this way, a stacked body (8) is obtained in which a support (D), a resin layer (C), a plated base layer (B) and a metal plating layer (E) are stacked in sequence, and the through holes are subjected to conductive treatment.
[0476] (Example 9)
[0477] A core material ("R-5775KH" manufactured by Panasonic Co., Ltd., base material thickness 0.1 mm, copper foil 18 μm) with copper foil laminated on both sides was prepared to produce an inner layer board with a conductive pattern formed thereon. Subsequently, a prepreg ("R-5670KG" manufactured by Panasonic Co., Ltd., containing glass fiber, thickness 0.1 mm, surface roughness Sz: 20.815 μm) and a glossy surface (non-roughened surface) of a copper foil (F2-WS manufactured by Furukawa Electric Co., Ltd., thickness 18 μm) were laminated to the surface of the inner layer board in sequence, and thermally pressed at 195°C for 90 minutes using a hand press ("Mini test press" manufactured by Toyo Seiki Seisaku-sho Co., Ltd.). Subsequently, the copper foil was fully etched by immersion in a ferric chloride etching solution (content 40 wt%) at 40°C for 3 minutes, thereby obtaining a rigid substrate equivalent to the above-mentioned support (D) obtained by curing the prepreg. It was confirmed that the surface roughness of the rigid substrate was Sz 4.215 μm and was smoothed. Thereafter, both sides of the rigid substrate were subjected to corona treatment ("Corona Surface Modification Evaluation Device TEC-4AX" manufactured by Kasuga Electric Co., Ltd., electrode-substrate distance 0.5 mm, 100 W), and then, the surface of the transfer laminate (2) obtained in Preparation Example 6 on which the resin layer (C) was formed was attached to both sides of the rigid substrate and pressed at 175° C. for 1 minute using a hand press ("Mini test press" manufactured by Toyo Seiki Seisaku-sho Co., Ltd.).
[0478] Then, a laser is used to form a non-through hole (blind via hole) with a diameter of 100 μm from the surface of the copper foil corresponding to the temporary support (A) of the transfer stack (2) to the conductive pattern of the inner layer board. Then, in order to remove the dirt (smear) generated by the laser hole processing, the smear is removed by plasma treatment. Thereafter, only the copper foil corresponding to the temporary support (A) is peeled off from the substrate with non-through holes obtained in the above manner, and a resin layer (C) and a plated base layer (B) are formed on the surface of the rigid substrate. The conductive pattern of the plated base layer (B) and the inner layer board is inspected by a testing machine, thereby confirming that the surface and the inner layer board are electrically connected and the conductivity is ensured. In addition, the surface resistance of the plated base layer (B) is 10Ω / □.
[0479] Thereafter, the plated base layer (B) obtained above was set as the cathode side, the phosphorus-containing copper was set as the anode side, and an electrolytic plating solution containing copper sulfate was used at a current density of 2 A / dm 2 Electrolytic plating was performed for 40 minutes to form a copper plating layer (film thickness 18 μm) corresponding to the metal plating layer (E) on the plated base layer (B). As the electrolytic plating solution, 70 g / L of copper sulfate, 200 g / L of sulfuric acid, 50 mg / L of chloride ions, and 5 ml / L of additives (Top Lucina SF-M, Okuno Pharmaceutical Co., Ltd.) were used.
[0480] Next, in order to conduct the non-through holes of the substrate with non-through holes, a conductive paste ("LS-411MK" manufactured by Asahi Kagaku Co., Ltd.) was printed by screen printing to fill the non-through holes, and dried at 150° C. for 30 minutes.
[0481] In this way, a laminate (9) is obtained in which the support (D), the resin layer (C), the plated base layer (B) and the metal plated layer (E) are laminated in this order and the non-through holes are subjected to a conductive treatment.
[0482] (Example 10)
[0483] The glossy side (non-roughened side) of the copper foil (F2-WS manufactured by Furukawa Electric Co., Ltd., thickness 18 μm) was attached to both sides of the prepreg (R-5670KG manufactured by Panasonic Co., Ltd., containing glass fiber, thickness 0.1 mm, surface roughness Sz: 20.815 μm), and hot-pressed at 195°C for 90 minutes using a hand press ("Mini testpress" manufactured by Toyo Seiki Seisaku-sho Co., Ltd.). Thereafter, the entire surface of the copper foil was etched by immersing it in a ferric chloride etching solution (content 40% by weight) at 40°C for 5 minutes, thereby obtaining a rigid substrate equivalent to the above-mentioned support (D) obtained by curing the prepreg. It was confirmed that the surface roughness Sz of the rigid substrate was 4.215 μm and was smoothed. Thereafter, both sides of the above-mentioned rigid substrate were subjected to corona treatment ("Corona Surface Modification Evaluation Device TEC-4AX" manufactured by Kasuga Electric Co., Ltd., electrode-substrate distance 0.5 mm, 100 W). Next, the surface of the transfer laminate (1) obtained in Preparation Example 5 on which the resin layer (C) was formed was attached to both surfaces of the rigid substrate and pressed at 175° C. for 1 minute using a hand press (“Mini testpress” manufactured by Toyo Seiki Seisaku-sho Co., Ltd.).
[0484] Then, a drill is used to form a through hole (through hole) with a diameter of 100 μm from the surface of the release film corresponding to the temporary support (A) of the transfer stack (1) to the release film corresponding to the temporary support (A) on the opposite side. Then, in order to remove the dirt (smear) generated by the drill processing, the smear is removed by plasma treatment. Thereafter, the substrate with through holes obtained in the above manner is made conductive by a palladium method. As the treatment conditions of the palladium method, it is immersed in a catalyst solution containing 1 g / l of palladium chloride, 1 ml / l of hydrochloric acid and 1 g / l of dimethylthiourea at 25°C for 3 minutes. Then, the substrate is washed with water and treated with a reducing solution containing 10 g / l of dimethylamine borane and 5 g / l of sodium hydroxide at 50°C for 2 minutes, thereby making the through hole conductive by palladium. Then, the release film equivalent to the temporary support (A) attached with palladium is peeled off to prepare a laminated body in which a resin layer (C) and a plated base layer (B) are formed on the surface of a rigid substrate and palladium is attached to the through hole. The front and back surfaces of the plated base layer (B) on the rigid substrate are inspected using a testing machine to confirm that the front and back surfaces are electrically connected and the conductivity is ensured. The surface resistance of the plated base layer (B) is 20Ω / □ on both the front and back surfaces.
[0485] Thereafter, a conductive pattern was formed by a semi-additive method. A plating resist ("RY-5125" manufactured by Showa Denko Materials Co., Ltd., thickness 25 μm) was applied to the surface of the plating base layer (B) at 110°C, 0.4 MPa, and 1 m / min, and an exposure machine ("BOX-W10" manufactured by Sunhayato Co., Ltd.) was used for 2 minutes (316 mJ / cm 2 ) and then immersed in a developer (1 mass % sodium carbonate aqueous solution) for 5 minutes for development to form a pattern resist. The through holes were made to be not blocked by the plating resist.
[0486] Thereafter, the plated base layer (B) and the through hole formed with the pattern resist obtained above were subjected to copper plating. The plated base layer (B) formed with the pattern resist was set as the cathode side, the phosphorus-containing copper was set as the anode side, and an electrolytic plating solution containing copper sulfate was used at a current density of 2A / dm 2 Electrolytic plating was performed for 40 minutes to form a copper plating layer (film thickness 18 μm) corresponding to the metal plating layer (E) on the plated base layer (B). As the electrolytic plating solution, 70 g / L of copper sulfate, 200 g / L of sulfuric acid, 50 mg / L of chloride ions, and 5 ml / L of additives (Top Lucina SF-M, Okuno Pharmaceutical Co., Ltd.) were used.
[0487] Then, the plated resist was stripped by immersion in 3% by mass sodium hydroxide for 3 minutes. Thereafter, the substrate obtained above was immersed in the silver etching solution (1) obtained in Preparation Example 9 at 25°C for 30 seconds to remove the plated base layer except for the conductive pattern of the metal plated layer, thereby obtaining a printed circuit board. The cross-sectional shape of the circuit forming portion of the produced printed circuit board shows a rectangular shape in which the wiring height and wiring width are not reduced and there is no undercut, and the surface is smooth. In this way, a laminate (10) in which a support (D), a resin layer (C), a plated base layer (B) and a metal plated layer (E) are sequentially stacked and the through holes are subjected to a conductive treatment is obtained.
[0488] (Example 11)
[0489] The same method was used except that the palladium method of Example 10 was replaced by the sputtering method. Regarding the conditions of the sputtering method, the substrate with through holes was placed in the sputtering device, and copper was installed as a sputtering target. Thereafter, the chamber was evacuated until the pressure in the chamber reached 1.0×10 -3Pa or less, argon gas as a sputtering gas is supplied to the chamber at a flow rate of 200 sccm to make the pressure in the chamber 0.3 Pa. While maintaining the temperature of the substrate with non-through holes at 75°C, a metal layer composed of copper is stacked to a thickness of 100 nm by sputtering of a copper target. In addition, after the temporary support (A) is peeled off, the surface resistance of the plated base layer (B) is 20Ω / □ on both the front and back sides.
[0490] In this way, a laminate (11) is obtained in which the support (D), the resin layer (C), the plated base layer (B) and the metal plated layer (E) are laminated in this order and the through holes are subjected to a conductive treatment.
[0491] (Example 12)
[0492] The glossy side (non-roughened side) of the copper foil (F2-WS manufactured by Furukawa Electric Co., Ltd., thickness 18 μm) was attached to both sides of the prepreg (R-5670KG manufactured by Panasonic Co., Ltd., containing glass fiber, thickness 0.1 mm, surface roughness Sz: 20.815 μm), and hot-pressed at 195°C for 90 minutes using a hand press ("Mini testpress" manufactured by Toyo Seiki Seisaku-sho Co., Ltd.). Thereafter, the entire surface of the copper foil was etched by immersing it in a ferric chloride etching solution (content 40% by mass) at 40°C for 3 minutes, thereby obtaining a rigid substrate equivalent to the above-mentioned support (D) obtained by curing the prepreg. It was confirmed that the surface roughness Sz of the rigid substrate was 4.215 μm and was smoothed. Thereafter, both sides of the above-mentioned rigid substrate were subjected to corona treatment ("Corona Surface Modification Evaluation Device TEC-4AX" manufactured by Kasuga Electric Co., Ltd., electrode-substrate distance 0.5 mm, 100 W). Next, the surface of the transfer laminate (1) obtained in Preparation Example 5 on which the resin layer (C) was formed was attached to both surfaces of the rigid substrate and pressed at 175° C. for 1 minute using a hand press (“Mini testpress” manufactured by Toyo Seiki Seisaku-sho Co., Ltd.).
[0493] Then, a through hole (through hole) with a diameter of 100 μm is formed from the surface of the release film corresponding to the temporary support (A) of the transfer stack (1) to the release film corresponding to the temporary support (A) on the opposite side using a drill. Then, in order to remove the dirt (smear) generated by the drill hole processing, the smear is removed by plasma treatment. Thereafter, the release film corresponding to the temporary support (A) is peeled off to produce a stack formed with a support (D), a resin layer (C), and a plated base layer (B). The surface resistance of the plated base layer (B) after the temporary support (A) is peeled off is 20Ω / □ on both the front and back sides.
[0494] Thereafter, a conductive pattern was formed by a semi-additive method. A plating resist ("RY-5125" manufactured by Showa Denko Materials Co., Ltd., thickness 25 μm) was applied to the surface of the plating base layer (B) at 110°C, 0.4 MPa, and 1 m / min, and an exposure machine ("BOX-W10" manufactured by Sunhayato Co., Ltd.) was used for 2 minutes (316 mJ / cm 2 ) and then immersed in a developer (1 mass % sodium carbonate aqueous solution) for 5 minutes and developed to form a pattern resist.
[0495] Thereafter, the plated base layer (B) on which the pattern resist was formed was subjected to copper plating. The plated base layer (B) on which the pattern resist was formed was set as the cathode side, the phosphorus-containing copper was set as the anode side, and an electrolytic plating solution containing copper sulfate was used at a current density of 2 A / dm 2 Electrolytic plating was performed for 40 minutes to form a copper plating layer (film thickness 18 μm) corresponding to the metal plating layer (E) on the plated base layer (B). As the electrolytic plating solution, 70 g / L of copper sulfate, 200 g / L of sulfuric acid, 50 mg / L of chloride ions, and 5 ml / L of additives (Top Lucina SF-M, Okuno Pharmaceutical Co., Ltd.) were used.
[0496] Then, the plated resist was stripped by immersion in 3% by mass sodium hydroxide for 3 minutes. Thereafter, the obtained substrate was immersed in the silver etching solution (1) obtained in Preparation Example 9 at 25° C. for 30 seconds to remove the plated base layer except for the conductive pattern of the metal plated layer, thereby obtaining a printed circuit board. The cross-sectional shape of the circuit forming portion of the produced printed circuit board showed a rectangular shape in which the wiring height and wiring width were not reduced and there was no undercut, and it was a conductive pattern with a smooth surface.
[0497] Thereafter, in order to conduct electricity to the through-holes of the substrate with through-holes, a conductive paste ("LS-411MK" manufactured by Asahi Kagaku Co., Ltd.) was printed by screen printing to fill the through-holes, and then dried at 150° C. for 30 minutes.
[0498] In this way, a laminate (12) is obtained in which the support (D), the resin layer (C), the plated base layer (B) and the metal plated layer (E) are laminated in this order and the through holes are subjected to a conductive treatment.
[0499] (Example 13)
[0500] The glossy surface (non-roughened surface) of the copper foil (F2-WS manufactured by Furukawa Electric Co., Ltd., thickness 18 μm) was attached to both sides of the prepreg (R-5670KG manufactured by Panasonic Co., Ltd., containing glass fiber, thickness 0.1 mm, surface roughness Sz: 20.815 μm), and the prepreg was heat-pressed at 195°C for 90 minutes using a hand press ("Mini testpress" manufactured by Toyo Seiki Seisaku-sho Co., Ltd.). Thereafter, the copper foil was immersed in a ferric chloride etching solution (content 40 mass %) at 40°C for 3 minutes to etch the entire surface, thereby obtaining a rigid substrate equivalent to the above-mentioned support (D) obtained by curing the prepreg. It was confirmed that the surface roughness Sz of the rigid substrate was 4.215 μm and was smoothed. Thereafter, both sides of the rigid substrate were subjected to corona treatment ("Corona Surface Modification Evaluation Device TEC-4AX" manufactured by Kasuga Electric Co., Ltd., electrode-substrate distance 0.5 mm, 100 W), and then, the surface of the transfer laminate (2) obtained in Preparation Example 6 on which the resin layer (C) was formed was attached to both sides of the rigid substrate, and pressed at 175°C for 1 minute using a hand press ("Mini testpress" manufactured by Toyo Seiki Seisaku-sho Co., Ltd.). Thereafter, the copper foil corresponding to the temporary support (A) was peeled off to prepare a laminate having a support (D), a resin layer (C), and a plated base layer (B). The surface resistance of the plated base layer (B) after the temporary support (A) was peeled off was 10Ω / □ on both the front and back sides.
[0501] Thereafter, a conductive pattern was formed by a semi-additive method. A plating resist ("RY-5125" manufactured by Showa Denko Materials Co., Ltd., thickness 25 μm) was applied to the surface of the plating base layer (B) at 110°C, 0.4 MPa, and 1 m / min, and an exposure machine ("BOX-W10" manufactured by Sunhayato Co., Ltd.) was used for 2 minutes (316 mJ / cm 2 ) and then immersed in a developer (1 mass % sodium carbonate aqueous solution) for 5 minutes and developed to form a pattern resist.
[0502] Thereafter, the plated base layer (B) on which the pattern resist was formed was subjected to copper plating. The plated base layer (B) on which the pattern resist was formed was set as the cathode side, the phosphorus-containing copper was set as the anode side, and an electrolytic plating solution containing copper sulfate was used at a current density of 2 A / dm 2Electrolytic plating was performed for 40 minutes to form a copper plating layer (film thickness 18 μm) corresponding to the metal plating layer (E) on the plated base layer (B). As the electrolytic plating solution, 70 g / L of copper sulfate, 200 g / L of sulfuric acid, 50 mg / L of chloride ions, and 5 ml / L of additives (Top Lucina SF-M, Okuno Pharmaceutical Co., Ltd.) were used.
[0503] Then, the plated resist was stripped by immersion in 3% by mass sodium hydroxide for 3 minutes. Thereafter, the obtained substrate was immersed in the silver etching solution (1) obtained in Preparation Example 9 at 25° C. for 30 seconds to remove the plated base layer except for the conductive pattern of the metal plated layer, thereby obtaining a printed circuit board. The cross-sectional shape of the circuit forming portion of the produced printed circuit board showed a rectangular shape in which the wiring height and wiring width were not reduced and there was no undercut, and it was a conductive pattern with a smooth surface.
[0504] Then, a through hole (through hole) with a diameter of 100 μm was formed from the surface of the conductive pattern of the metal plating layer (E) obtained by the above-mentioned pattern etching to the conductive pattern on the opposite side using a laser. Then, in order to remove the dirt (smear) generated by the laser processing, desmearing was performed using plasma treatment.
[0505] Thereafter, in order to conduct electricity to the through-holes of the substrate with through-holes, a conductive paste ("LS-411MK" manufactured by Asahi Kagaku Co., Ltd.) was printed by screen printing to fill the through-holes, and then dried at 160° C. for 30 minutes.
[0506] In this way, a laminate (13) is obtained in which the support (D), the resin layer (C), the plated base layer (B) and the metal plated layer (E) are laminated in this order and the through holes are subjected to a conductive treatment.
[0507] (Example 14)
[0508] A core material ("R-5775KH" manufactured by Panasonic Co., Ltd., base material thickness 0.1 mm, copper foil 18 μm) with copper foil laminated on both sides was prepared to produce an inner layer board with a conductive pattern. Subsequently, a prepreg ("R-5670KG" manufactured by Panasonic Co., Ltd., containing glass fiber, thickness 0.1 mm, surface roughness Sz: 20.815 μm) and a glossy surface (non-roughened surface) of a copper foil (F2-WS manufactured by Furukawa Electric Co., Ltd., thickness 18 μm) were laminated to the surface of the inner layer board in sequence, and thermally pressed at 195°C for 90 minutes using a hand press ("Mini test press" manufactured by Toyo Seiki Seisaku-sho Co., Ltd.). Subsequently, the entire surface of the copper foil was etched by immersion in a ferric chloride etching solution (content 40 mass%) at 40°C for 3 minutes, thereby obtaining a rigid substrate equivalent to the above-mentioned support (D) obtained by curing the prepreg. It was confirmed that the surface roughness Sz of the rigid substrate was 4.215 μm and was smoothed. Thereafter, both sides of the rigid substrate were subjected to corona treatment ("Corona Surface Modification Evaluation Device TEC-4AX" manufactured by Kasuga Electric Co., Ltd., electrode-substrate distance 0.5 mm, 100 W). Subsequently, the surface of the transfer laminate (1) obtained in Preparation Example 5 on which the resin layer (C) was formed was attached to both sides of the rigid substrate, and pressed at 175°C for 1 minute using a hand press ("Mini test press" manufactured by Toyo Seiki Seisaku-sho Co., Ltd.).
[0509] Then, in order to form a blind via hole from the surface of the release film equivalent to the temporary support (A) of the transfer stack (1) to the conductive pattern of the inner layer board, a laser is used to form a blind via hole with a diameter of 100 μm. Then, in order to remove the dirt (smear) generated by laser processing, plasma treatment is used to remove the smear. Thereafter, the substrate with non-through holes obtained as described above is passed through the shadow process (adjustment-carbon adsorption treatment-etching) of MacDermid Company, so that carbon is attached to the surface of the non-through holes and the film is dried. Then, the release film equivalent to the temporary support (A) attached with carbon is peeled off, thereby preparing a stack having a resin layer (C) and a plated base layer (B) formed on the surface of the rigid substrate and carbon attached to the non-through holes. The plated base layer (B) on the rigid substrate and the conductive pattern of the inner layer board are inspected using a testing machine, and it is confirmed that the surface and the inner layer board are electrically connected and the conductivity is ensured. Furthermore, after the temporary support (A) was peeled off, the surface resistance of the plating base layer (B) was 20Ω / □.
[0510] Thereafter, a conductive pattern was formed by a semi-additive method. A plating resist ("RY-5125" manufactured by Showa Denko Materials Co., Ltd., thickness 25 μm) was applied to the surface of the plating base layer (B) at 110°C, 0.4 MPa, and 1 m / min, and an exposure machine ("BOX-W10" manufactured by Sunhayato Co., Ltd.) was used for 2 minutes (316 mJ / cm 2 ) exposure treatment, followed by immersion in a developer (1 mass % sodium carbonate aqueous solution) for 5 minutes, and development treatment, thereby forming a pattern resist. After development, the non-through holes are made into a state that is not blocked by the plating resist.
[0511] Thereafter, the plated base layer (B) and the non-through hole formed with the pattern resist obtained above were subjected to copper plating. The plated base layer (B) formed with the pattern resist was set as the cathode side, the phosphorus-containing copper was set as the anode side, and an electrolytic plating solution containing copper sulfate was used at a current density of 2 A / dm 2 Electrolytic plating was performed for 40 minutes to form a copper plating layer (film thickness 18 μm) corresponding to the metal plating layer (E) on the plated base layer (B). As the electrolytic plating solution, 70 g / L of copper sulfate, 200 g / L of sulfuric acid, 50 mg / L of chloride ions, and 5 ml / L of additives (Top Lucina SF-M, Okuno Pharmaceutical Co., Ltd.) were used.
[0512] Then, the plated resist was stripped by immersion in 3% by mass sodium hydroxide for 3 minutes. Thereafter, the substrate obtained above was immersed in the silver etching solution (1) obtained in Preparation Example 9 at 25°C for 30 seconds to remove the plated base layer except for the conductive pattern of the metal plated layer, thereby obtaining a printed circuit board. The cross-sectional shape of the circuit forming portion of the produced printed circuit board shows a rectangular shape in which the wiring height and wiring width are not reduced and there is no undercut, and it is a conductive pattern with a smooth surface. In this way, a laminate (14) in which a support (D), a resin layer (C), a plated base layer (B) and a metal plated layer (E) are sequentially stacked and the non-through holes are subjected to a conductive treatment is obtained.
[0513] (Example 15)
[0514] The same method was used except that the shadowing process (conditioning - carbon adsorption treatment - etching) of Example 14 was replaced by sputtering. Regarding the conditions of the sputtering method, the substrate with non-through holes was loaded into the sputtering device, and copper was installed as a sputtering target. Thereafter, the chamber was evacuated until the pressure in the chamber reached 1.0×10 -3Pa or less, argon gas as a sputtering gas is supplied to the chamber at a flow rate of 200sccm to make the pressure in the chamber 0.3Pa. While maintaining the temperature of the substrate with non-through holes at 75°C, the metal layer composed of copper is stacked to a thickness of 100nm by sputtering of a copper target. The conductive pattern of the plated base layer (B) and the inner layer board on the rigid substrate is inspected by a testing machine to confirm that the surface and the inner layer board are electrically connected and the conductivity is ensured. In addition, after the temporary support (A) is peeled off, the surface resistance of the plated base layer (B) is 20Ω / □.
[0515] In this way, a laminate (15) is obtained in which the support (D), the resin layer (C), the plated base layer (B), and the metal plated layer (E) are laminated in this order and the through holes are subjected to a conductive treatment.
[0516] (Example 16)
[0517] A core material ("R-5775KH" manufactured by Panasonic Co., Ltd., base material thickness 0.1 mm, copper foil 18 μm) with copper foil laminated on both sides was prepared to produce an inner layer board with a conductive pattern. Subsequently, a prepreg ("R-5670KG" manufactured by Panasonic Co., Ltd., containing glass fiber, thickness 0.1 mm, surface roughness Sz: 20.815 μm) and a glossy surface (non-roughened surface) of a copper foil (F2-WS manufactured by Furukawa Electric Co., Ltd., thickness 18 μm) were laminated to the surface of the inner layer board in sequence, and a hand press ("Mini test press" manufactured by Toyo Seiki Seisaku-sho Co., Ltd.) was used for thermal compression bonding at 195°C for 90 minutes. Subsequently, the copper foil was immersed in a ferric chloride etching solution (content 40 mass%) at 40°C for 5 minutes to etch the entire surface, thereby obtaining a rigid substrate equivalent to the above-mentioned support (D) obtained by curing the prepreg. It was confirmed that the surface roughness Sz of the rigid substrate was 4.215 μm and was smoothed. Thereafter, both sides of the rigid substrate were subjected to corona treatment ("Corona Surface Modification Evaluation Device TEC-4AX" manufactured by Kasuga Electric Co., Ltd., electrode-substrate distance 0.5 mm, 100 W), and then, the surface of the transfer laminate (2) obtained in Preparation Example 6 on which the resin layer (C) was formed was attached to both sides of the rigid substrate, and pressed at 175° C. for 1 minute using a hand press ("Mini test press" manufactured by Toyo Seiki Seisaku-sho Co., Ltd.).
[0518] Then, in order to form a blind via hole from the surface of the copper foil of the transfer laminate (2) corresponding to the temporary support (A) to the conductive pattern of the inner layer board, a laser is used to form a blind via hole with a diameter of 100 μm. Then, in order to remove the dirt (smear) generated by laser processing, the smear is removed by plasma treatment. Then, the copper foil corresponding to the temporary support (A) is peeled off to prepare a laminate having a resin layer (C) and a plated base layer (B) formed on the surface of a rigid substrate. After the temporary support (A) is peeled off, the surface resistance of the plated base layer (B) is 10Ω / □.
[0519] Thereafter, a conductive pattern was formed by a semi-additive method. A plating resist ("RY-5125" manufactured by Showa Denko Materials Co., Ltd., thickness 25 μm) was applied to the surface of the plating base layer (B) at 110°C, 0.4 MPa, and 1 m / min, and an exposure machine ("BOX-W10" manufactured by Sunhayato Co., Ltd.) was used for 2 minutes (316 mJ / cm 2 ) exposure treatment, followed by immersion in a developer (1 mass % sodium carbonate aqueous solution) for 5 minutes, and development treatment, thereby forming a pattern resist. After development, the non-through holes are made into a state that is not blocked by the plating resist.
[0520] Thereafter, the plated base layer (B) on which the pattern resist was formed was subjected to copper plating. The plated base layer (B) on which the pattern resist was formed was set as the cathode side, the phosphorus-containing copper was set as the anode side, and an electrolytic plating solution containing copper sulfate was used at a current density of 2 A / dm 2 Electrolytic plating was performed for 40 minutes to form a copper plating layer (film thickness 18 μm) corresponding to the metal plating layer (E) on the plated base layer (B). As the electrolytic plating solution, 70 g / L of copper sulfate, 200 g / L of sulfuric acid, 50 mg / L of chloride ions, and 5 ml / L of additives (Top Lucina SF-M, Okuno Pharmaceutical Co., Ltd.) were used.
[0521] Then, the plated resist was stripped by immersion in 3% by mass sodium hydroxide for 3 minutes. Thereafter, the obtained substrate was immersed in the silver etching solution (1) obtained in Preparation Example 9 at 25°C for 30 seconds to remove the plated base layer (B) except for the conductive pattern of the metal plated layer, thereby obtaining a printed circuit board. The cross-sectional shape of the circuit forming portion of the produced printed circuit board showed a rectangular shape in which the wiring height and wiring width were not reduced and there was no undercut, and it was a conductive pattern with a smooth surface.
[0522] Thereafter, in order to conduct the non-through holes of the substrate with non-through holes, a conductive paste ("LS-411MK" manufactured by Asahi Kagaku Co., Ltd.) was printed by screen printing to fill the non-through holes, and dried at 160° C. for 30 minutes.
[0523] In this way, a laminate (16) is obtained in which the support (D), the resin layer (C), the plated base layer (B) and the metal plated layer (E) are laminated in this order and the non-through holes are subjected to a conductive treatment.
[0524] (Example 17)
[0525] A core material ("R-5775KH" manufactured by Panasonic Co., Ltd., base material thickness 0.1 mm, copper foil 18 μm) with copper foil laminated on both sides was prepared to produce an inner layer board with a conductive pattern. Subsequently, a prepreg ("R-5670KG" manufactured by Panasonic Co., Ltd., containing glass fiber, thickness 0.1 mm, surface roughness Sz: 20.815 μm) and a glossy surface (non-roughened surface) of a copper foil (F2-WS manufactured by Furukawa Electric Co., Ltd., thickness 18 μm) were laminated to the surface of the inner layer board in sequence, and thermally pressed at 195°C for 90 minutes using a hand press ("Mini test press" manufactured by Toyo Seiki Seisaku-sho Co., Ltd.). Subsequently, the entire surface of the copper foil was etched by immersion in a ferric chloride etching solution (content 40 mass%) at 40°C for 5 minutes, thereby obtaining a rigid substrate equivalent to the above-mentioned support (D) obtained by curing the prepreg. It was confirmed that the surface roughness Sz of the rigid substrate was 4.215 μm and was smoothed. Thereafter, both sides of the above-mentioned rigid substrate were subjected to corona treatment ("Corona Surface Modification Evaluation Device TEC-4AX" manufactured by Kasuga Electric Co., Ltd., electrode-substrate distance 0.5 mm, 100 W), and then, the surface of the transfer laminate (2) obtained in Preparation Example 6 on which the resin layer (C) was formed was attached to both sides of the above-mentioned rigid substrate, and pressed at 175°C for 1 minute using a hand press ("Mini test press" manufactured by Toyo Seiki Seisaku-sho Co., Ltd.). Then, the copper foil corresponding to the temporary support (A) was peeled off, thereby preparing a laminate having a resin layer (C) and a plated base layer (B) formed on the surface of the rigid substrate. In addition, after the temporary support (A) was peeled off, the surface resistance of the plated base layer (B) was 10Ω / □.
[0526] Thereafter, a conductive pattern was formed by a semi-additive method. A plating resist ("RY-5125" manufactured by Showa Denko Materials Co., Ltd., thickness 25 μm) was applied to the surface of the plating base layer (B) at 110°C, 0.4 MPa, and 1 m / min, and an exposure machine ("BOX-W10" manufactured by Sunhayato Co., Ltd.) was used for 2 minutes (316 mJ / cm 2 ) exposure treatment, followed by immersion in a developer (1 mass % sodium carbonate aqueous solution) for 5 minutes, and development treatment, thereby forming a pattern resist. After development, the non-through holes are made into a state that is not blocked by the plating resist.
[0527] Thereafter, the plated base layer (B) on which the pattern resist was formed was subjected to copper plating. The plated base layer (B) on which the pattern resist was formed was set as the cathode side, the phosphorus-containing copper was set as the anode side, and an electrolytic plating solution containing copper sulfate was used at a current density of 2 A / dm 2 Electrolytic plating was performed for 40 minutes to form a copper plating layer (film thickness 18 μm) corresponding to the metal plating layer (E) on the plated base layer (B). As the electrolytic plating solution, 70 g / L of copper sulfate, 200 g / L of sulfuric acid, 50 mg / L of chloride ions, and 5 ml / L of additives (Top Lucina SF-M, Okuno Pharmaceutical Co., Ltd.) were used.
[0528] Then, the plated resist was stripped by immersion in 3% by mass sodium hydroxide for 3 minutes. Thereafter, the obtained substrate was immersed in the silver etching solution (1) obtained in Preparation Example 9 at 25°C for 30 seconds to remove the plated base layer (B) except for the conductive pattern of the metal plated layer, thereby obtaining a printed circuit board. The cross-sectional shape of the circuit forming portion of the produced printed circuit board showed a rectangular shape in which the wiring height and wiring width were not reduced and there was no undercut, and it was a conductive pattern with a smooth surface.
[0529] Next, in order to form a blind via hole from the surface of the patterned metal plating layer (E) to the conductive pattern of the inner layer board, a blind via hole with a diameter of 100 μm was formed using a laser. Next, in order to remove the dirt (smear) generated by the laser processing, desmearing was performed using plasma treatment.
[0530] Thereafter, in order to conduct the non-through holes of the substrate with non-through holes, a conductive paste ("LS-411MK" manufactured by Asahi Kagaku Co., Ltd.) was printed by screen printing to fill the non-through holes, and dried at 150° C. for 30 minutes.
[0531] In this way, a laminate (17) is obtained in which the support (D), the resin layer (C), the plated base layer (B) and the metal plated layer (E) are laminated in this order and the non-through holes are subjected to a conductive treatment.
[0532] (Comparative Example 1)
[0533] The coating liquid (1) for forming the resin layer (C) obtained in Preparation Example 3 was applied to one side (the side coated first was designated as side A) of a polyimide film ("Kapton 150EN-A" manufactured by DuPont Toray Co., Ltd., thickness 38 μm) using a small desktop coater ("K Printing Proofer" manufactured by RK Print Coat Instruments), and dried at 180°C for 3 minutes to coat the polyimide film with a layer corresponding to the above-mentioned resin layer (C) in such a manner that the thickness after drying becomes 0.3 μm. Thereafter, the polyimide film was turned over, and the coating liquid (1) for forming the resin layer (C) obtained in Preparation Example 3 was applied to the other single side (the side to be coated later was set as the B side) using a small desktop coating machine ("K Printing Proofer" manufactured by RK Print Coat Instruments), and dried at 180°C for 3 minutes to coat a layer corresponding to the above-mentioned resin layer (C) so that the thickness after drying was 0.3 μm. When the coating liquid (1) for forming the resin layer (C) obtained in Preparation Example 3 was applied to the B side, the A side came into contact with the coating device, and thus the coating film was damaged. Thereafter, the polyimide film was turned over, and the coating solution (1) for forming the plating base layer (B) obtained in Preparation Example 1 was applied to the A surface using a small desktop coating machine ("K Printing Proofer" manufactured by RK Print Coat Instruments), and dried at 180°C for 3 minutes, and a silver layer corresponding to the above-mentioned plating base layer (B) was applied so that the thickness after drying was 0.1 μm. When the coating solution (1) for forming the plating base layer (B) obtained in Preparation Example 1 was applied to the A surface, the B surface came into contact with the coating device, and thus the coating film was damaged. Thereafter, the polyimide film was turned over, and the coating solution (1) obtained in Preparation Example 1 was applied to the B surface using a small desktop coating machine ("K Printing Proofer" manufactured by RK Print Coat Instruments), and dried at 180°C for 3 minutes, and a silver layer corresponding to the above-mentioned plating base layer (B) was applied so that the thickness after drying was 0.1 μm. When the coating liquid (1) for forming the plating base layer (B) obtained in Preparation Example 1 was applied to the B surface, the A surface came into contact with the coating device, and thus the coating film was damaged.
[0534] Thereafter, the surface resistance of the plated base layer (B) was 10000Ω / □ on the A side and 20000Ω / □ on the B side. The plated base layer (B) was dried at 250°C for 5 minutes to have a surface resistance of 30Ω / □ on the A side and 500Ω / □ on the B side.
[0535] Thereafter, the plated base layer (B) obtained above is subjected to copper plating. The plated base layer (B) is set as the cathode side, the phosphorus-containing copper is set as the anode side, and an electrolytic plating solution containing copper sulfate is used at a current density of 2 A / dm 2 Electrolytic plating was performed for 40 minutes to form a copper plating layer (film thickness 18 μm) corresponding to the metal plating layer (E) on the plated base layer (B). As the electrolytic plating solution, 70 g / L of copper sulfate, 200 g / L of sulfuric acid, 50 mg / L of chloride ions, and 5 ml / L of additives (Top Lucina SF-M, Okuno Pharmaceutical Co., Ltd.) were used.
[0536] In this manner, a laminate (R1) is obtained in which the support (D), the resin layer (C), the plated base layer (B), and the metal plated layer (E) are laminated in this order.
[0537] <Measurement method of surface resistance>
[0538] The surface resistance of the plating base layer (B) was measured using a loresta GX MCP-T700 and a PSP probe. The unit is Ω / □.
[0539] <Method for evaluating damage on the surface of the plating base layer (B) and the surface of the resin layer (C)>
[0540] The damage of the surface of the plating support layer (B) and the surface of the resin layer (C) was visually evaluated using the following criteria.
[0541] A: There is no damage to the coating surface of the plating base layer (B) and the coating surface of the resin layer (C).
[0542] B: The coating surface of the plating base layer (B) is not damaged, but the coating surface of the resin layer (C) is damaged.
[0543] C: The coating surface of the plating base layer (B) is damaged, but the coating surface of the resin layer (C) is not damaged.
[0544] D: Both the coating surface of the plating base layer (B) and the coating surface of the resin layer (C) are damaged.
[0545] [Table 1]
[0546]
[0547] The laminates (1) to (17) obtained in Examples 1 to 17 of the laminates of the present invention are bonded to a support (D) using a transfer laminate, and the surface resistance of the plated base layer (B) after only the temporary support (A) is peeled off is such that the A side is equal to the B side and is relatively low, and since the coated surface does not come into contact with the coating device as in the comparative example, the coated surface is not damaged.
[0548] On the other hand, in Comparative Example 1, the front side (A side) and the back side (B side) are coated alternately, and the thermal history of the A side and the B side is different, so the surface resistance is greatly different between the A side and the B side, and the surface resistance is relatively high. Furthermore, since the coated surface is in contact with the coating device, the coated surface is more damaged. In the case where the surface resistance is different between the A side and the B side, if electrolytic copper plating is performed on both sides at one time, the copper plating is concentrated on the side with lower surface resistance, so the plated film becomes thicker. In addition, since the coated surface is damaged, it will become a cause of disconnection when forming a conductive pattern by pattern etching, and the quality is reduced.
[0549] Explanation of symbols
[0550] 1: Temporary support
[0551] 2: Plating base layer
[0552] 3: Resin layer
[0553] 4: Support
[0554] 5: Resist
[0555] 6: Metal coating
[0556] 7: Smoothing the substrate
[0557] 8:Through hole
[0558] 9: Any one of palladium, conductive polymer, conductive paste, and carbon
[0559] 10: Metal film (dry plating method)
[0560] 11: Conductive paste
[0561] 12: Nuclear materials
[0562] 13: Copper layer (inner layer)
[0563] 14: Non-through hole
Claims
1. A transfer laminate, wherein a plated base layer (B) containing a dispersant (b1) and a conductive substance (b2), and a resin layer (C) containing a compound (c1) having a functional group [X] are sequentially laminated on at least one side of a temporary support (A), characterized in that: In the plating base layer (B), the signal intensity of carbon atoms measured by glow discharge emission spectroscopy is greater on the resin layer (C) side than on the temporary support (A) side.
2. The transfer laminate according to claim 1, wherein In the plated base layer (B), the signal intensity of the glow discharge emission spectroscopy on the temporary support (A) side is 2 / 3 or less of that on the resin layer (C) side.
3. The transfer laminate according to claim 1 or 2, wherein A chemical bond is formed by reacting the basic nitrogen atom-containing group or the phosphate ester group of the compound (b1) contained in the plating base layer (B) with the functional group [X] of the compound (c1) contained in the resin layer (C).
4. The transfer laminate according to claim 3, wherein The functional group [X] is selected from one or more functional groups selected from epoxy, carboxylic acid, carboxylic anhydride, ketone, alkyl alcohol amide, isocyanate, vinyl, halogenated alkyl, acryl, cyanamide, urea, and acyl halide, or one or more functional groups selected from epoxy and amino groups.
5. The transfer laminate according to claim 1 or 2, wherein The conductive material (b2) is silver.
6. The transfer laminate according to claim 1 or 2, wherein: The resin layer (C) is one or more layers.
7. The transfer laminate according to claim 1 or 2, wherein: The surface roughness, that is, the maximum height Sz of the temporary support (A) measured with a laser microscope is 0.001 to 20 μm.
8. The transfer laminate according to claim 1 or 2, wherein The temporary support (A) has a release layer on its surface.
9. The transfer laminate according to claim 1 or 2, wherein: The temporary support (A) is a film or a metal.
10. A laminate, characterized in that: The transfer laminate according to claim 1 or 2 is laminated to at least one surface of a support D on the surface on which the resin layer (C) is formed.
11. The laminate according to claim 10, wherein The support D is made of a thermosetting resin that has been completely cured.
12. A method for producing a transfer laminate according to claim 1 or 2, characterized in that: include: Step 1 of forming a plating base layer (B) containing a dispersant (b1) and a conductive material (b2) on at least one surface of the temporary support (A), wherein the dispersant (b1) contains a basic nitrogen atom group or a phosphate group; and Step 2: forming a resin layer (C) containing a compound (c1) having a functional group [X] thereon, and forming a chemical bond by reacting the basic nitrogen atom-containing group or phosphate group of the dispersant (b1) contained in the plating base layer (B) with the functional group [X] of the compound (c1) contained in the resin layer (C).
13. A method for producing a transfer laminate according to claim 1 or 2, characterized in that: include: Step 1 of patterning and forming a plating base layer (B) containing a dispersant (b1) and a conductive substance (b2) on at least one side of the temporary support (A), wherein the dispersant (b1) contains a basic nitrogen atom group or a phosphate group; and Step 2: forming the resin layer (C) on the patterned plated base layer (B), and forming a bond by reacting the basic nitrogen atom-containing group or phosphate ester group of the dispersant (b1) contained in the plated base layer (B) with the functional group [X] of the compound (c1) contained in the resin layer (C).
14. The method for producing a transfer laminate according to claim 12, wherein: The method comprises the step 1' of forming a layer having a releasable property on the temporary support (A).
15. A method for manufacturing a conductive pattern, characterized in that: include: Step 1 of laminating the surface of the transfer laminate obtained by the production method according to claim 12 on which the resin layer (C) is formed to at least one surface of a support (D); and Step 2 of peeling off the temporary support (A) of the laminated transfer body and forming the resin layer (C) and the plating base layer (B) on at least one surface of the support (D).
16. The method for producing a conductive pattern according to claim 15, wherein: The method comprises the step of forming a metal plating layer (E) on the plated base layer (B).
17. A method for manufacturing a conductive pattern, characterized in that: include: Step 1 of laminating the surface of the transfer laminate obtained by the production method according to claim 12, on which the resin layer (C) is formed, to at least one surface of a support (D); Step 2 of forming through holes penetrating both surfaces of the temporary support (A) of the transfer laminate; Step 3 of applying any one of palladium, conductive polymer, conductive paste, and carbon to the transfer laminate and the surface of the through hole to make the surface of the through hole conductive; and Step 4 of peeling off the temporary support (A) and forming a metal plating layer (E) on the plating base layer (B) and the through-holes.
18. A method for manufacturing a conductive pattern, characterized in that: include: Step 1 of laminating the surface of the transfer laminate obtained by the production method according to claim 12, on which the resin layer (C) is formed, to at least one surface of a support (D); Step 2 of forming through holes penetrating both surfaces of the temporary support (A) of the transfer laminate; Step 3 of forming a metal film on the surface of the transfer laminate and the through-hole by dry plating to make the surface of the through-hole conductive; as well as Step 4 of peeling off the temporary support (A) and forming a metal plating layer (E) on the plating base layer (B) and the through-holes.
19. A method for manufacturing a conductive pattern, characterized in that: include: Step 1 of laminating the surface of the transfer laminate obtained by the production method according to claim 12, on which the resin layer (C) is formed, to at least one surface of a support (D); Step 2 of forming through holes penetrating both surfaces of the temporary support (A) of the transfer laminate; Step 3 of peeling off the temporary support (A) and forming a metal plating layer (E) on the surface of the plating base layer (B); and Step 4 of filling the through hole with a conductive paste to make the through hole conductive.
20. A method for manufacturing a conductive pattern, characterized in that: include: Step 1 of bonding a support (D) to at least one surface of a substrate having a conductive pattern formed thereon; Step 2 of laminating the surface of the transfer laminate obtained by the production method according to claim 12, on which the resin layer (C) is formed, to the surface of the support (D); Step 3 of forming a non-through hole from the temporary support (A) of the transfer laminate to the conductive pattern of the inner layer; Step 4 of applying any one of palladium, a conductive polymer, a conductive paste, and carbon to the surface of the transfer laminate and the non-through hole to make the surface of the non-through hole conductive; and Step 5 of peeling off the temporary support (A) and forming a metal plating layer (E) on the plating base layer (B) and the non-through holes.
21. A method for manufacturing a conductive pattern, characterized in that: include: Step 1 of bonding a support (D) to at least one surface of a substrate having a conductive pattern formed thereon; Step 2 of laminating the surface of the transfer laminate obtained by the production method according to claim 12, on which the resin layer (C) is formed, to the surface of the support (D); Step 3 of forming a non-through hole from the temporary support (A) of the transfer laminate to the conductive pattern of the inner layer; Step 4 of forming a metal film on the surface of the transfer laminate and the non-through hole by dry plating to make the surface of the non-through hole conductive; and Step 5 of peeling off the temporary support (A) and forming a metal plating layer (E) on the plating base layer (B) and the non-through holes.
22. A method for manufacturing a conductive pattern, characterized in that: include: Step 1 of bonding a support (D) to at least one surface of a substrate having a conductive pattern formed thereon; Step 2 of laminating the surface of the transfer laminate obtained by the production method according to claim 12, on which the resin layer (C) is formed, to the surface of the support (D); Step 3 of forming a non-through hole from the temporary support (A) of the transfer laminate to the conductive pattern of the inner layer; Step 4 of peeling off the temporary support (A) and forming a metal plating layer (E) on the surface of the plating base layer (B); and Step 5 of filling the non-through hole with a conductive paste to make the non-through hole conductive.
23. A method for manufacturing a conductive pattern, characterized in that: include: Step 1 of laminating the surface of the transfer laminate obtained by the production method according to claim 12, on which the resin layer (C) is formed, to at least one surface of a support (D); Step 2 of forming through holes penetrating both surfaces of the temporary support (A) of the transfer laminate; Step 3 of applying any one of palladium, conductive polymer, conductive paste, and carbon to the surface of the transfer laminate and the through-hole to make the surface of the through-hole conductive; Step 4 of peeling off the temporary support (A) and forming a pattern resist on the surface of the plated base layer (B); Step 5 of forming a metal plating layer (E) on the plating base layer (B) and the through-hole; and Step 6 of peeling off the pattern resist and removing the plating base layer (B) except for the portion where the metal plating layer (E) serving as the conductive pattern is formed by using an etching solution.
24. A method for manufacturing a conductive pattern, characterized in that: include: Step 1 of laminating the surface of the transfer laminate obtained by the production method according to claim 12, on which the resin layer (C) is formed, to at least one surface of a support (D); Step 2 of forming through holes penetrating both surfaces of the temporary support (A) of the transfer laminate; Step 3 of forming a metal film on the surface of the transfer laminate and the through-hole by dry plating to make the surface of the through-hole conductive; Step 4 of peeling off the temporary support (A) and forming a pattern resist on the surface of the plated base layer (B); Step 5 of forming a metal plating layer (E) on the plating base layer (B) and the through-hole; and Step 6 of peeling off the pattern resist and removing the plating base layer (B) except for the portion where the metal plating layer (E) serving as the conductive pattern is formed by using an etching solution.
25. A method for manufacturing a conductive pattern, characterized in that: include: Step 1 of laminating the surface of the transfer laminate obtained by the production method according to claim 12, on which the resin layer (C) is formed, to at least one surface of a support (D); Step 2 of forming through holes penetrating both surfaces of the temporary support (A) of the transfer laminate; Step 3 of peeling off the temporary support (A) and forming a pattern resist on the surface of the plating base layer (B); Step 4 of forming a metal plating layer (E) on the plated base layer (B); Step 5 of peeling off the pattern resist and removing the plating base layer (B) except for the portion where the metal plating layer (E) to be the conductive pattern is formed by an etching solution; and Step 6 of filling the through hole with a conductive paste to make the through hole conductive.
26. A method for manufacturing a conductive pattern, characterized in that: include: Step 1 of laminating the surface of the transfer laminate obtained by the production method according to claim 12, on which the resin layer (C) is formed, to at least one surface of a support (D); Step 2 of peeling off the temporary support (A) and forming the resin (C) and the plating base layer (B) on the surface of the support (D); Step 3 of forming a pattern resist on the surface of the plating base layer (B); Step 4 of forming a metal plating layer (E) on the plated base layer (B); Step 5 of peeling off the pattern resist and removing the plated base layer (B) except for the portion where the metal plated layer (E) to be the conductive pattern is formed by an etching solution; Step 6 of forming through holes penetrating both surfaces of the temporary support (A) of the transfer laminate; and Step 7 of filling the through hole with a conductive paste to make the through hole conductive.
27. A method for manufacturing a conductive pattern, characterized in that: include: Step 1 of bonding a support (D) to at least one surface of a substrate having a conductive pattern formed thereon; Step 2 of laminating the surface of the transfer laminate obtained by the production method of claim 12, on which the resin layer (C) is formed, to the surface of the support (D); Step 3 of forming a non-through hole from the temporary support (A) of the transfer laminate to the conductive pattern of the inner layer; Step 4 of applying any one of palladium, a conductive polymer, a conductive paste, and carbon to the surface of the transfer laminate and the non-through hole to make the surface of the non-through hole conductive; Step 5 of peeling off the temporary support (A) and forming a pattern resist on the surface of the plating base layer (B); Step 6 of forming a metal plating layer (E) on the plating base layer (B) and the non-through hole; and Step 7 of peeling off the pattern resist and removing the plating base layer (B) except for the portion where the metal plating layer (E) serving as the conductive pattern is formed by using an etching solution.
28. A method for manufacturing a conductive pattern, characterized in that: include: Step 1 of bonding a support (D) to at least one surface of a substrate having a conductive pattern formed thereon; Step 2 of laminating the surface of the transfer laminate obtained by the production method according to claim 12, on which the resin layer (C) is formed, to the surface of the support (D); Step 3 of forming a non-through hole from the temporary support (A) of the transfer laminate to the conductive pattern of the inner layer; Step 4 of forming a metal film on the surface of the transfer laminate and the non-through hole by dry plating to make the surface of the non-through hole conductive; Step 5 of peeling off the temporary support (A) and forming a pattern resist on the surface of the plating base layer (B); Step 6 of forming a metal plating layer (E) on the plating base layer (B) and the non-through hole; and Step 7 of peeling off the pattern resist and removing the plating base layer (B) except for the portion where the metal plating layer (E) serving as the conductive pattern is formed by using an etching solution.
29. A method for manufacturing a conductive pattern, characterized in that: include: Step 1 of bonding a support (D) to at least one surface of a substrate having a conductive pattern formed thereon; Step 2 of laminating the surface of the transfer laminate obtained by the production method of claim 12, on which the resin layer (C) is formed, to the surface of the support (D); Step 3 of forming a non-through hole from the temporary support (A) of the transfer laminate to the conductive pattern of the inner layer; Step 4 of peeling off the temporary support (A) and forming a pattern resist on the surface of the plating base layer (B); Step 5 of forming a metal plating layer (E) on the plated base layer (B); Step 6 of peeling off the pattern resist and removing the plating base layer (B) except for the portion where the metal plating layer (E) to be the conductive pattern is formed by an etching solution; and Step 7 of filling the non-through hole with a conductive paste to make the non-through hole conductive.
30. A method for manufacturing a conductive pattern, characterized in that: include: Step 1 of bonding a support (D) to at least one surface of a substrate having a conductive pattern formed thereon; Step 2 of laminating the surface of the transfer laminate obtained by the production method according to claim 12, on which the resin layer (C) is formed, to the surface of the support (D); Step 3 of peeling off the temporary support (A) and forming the resin (C) and the plating base layer (B) on the surface of the support (D); Step 4 of forming a pattern resist on the surface of the plating base layer (B); Step 5 of forming a metal plating layer (E) on the plated base layer (B); Step 6 of peeling off the pattern resist and removing the plated base layer (B) except for the portion where the metal plated layer (E) forming the conductive pattern is formed by an etching solution; Step 7 of forming a non-through hole from the temporary support (A) of the transfer laminate to the conductive pattern of the inner layer; and Step 8 of filling the non-through hole with a conductive paste to make the non-through hole conductive.
31. The method for manufacturing a conductive pattern according to claim 15, wherein: The method comprises the step of smoothing the surface of the support (D).
32. A method for manufacturing a printed wiring board, characterized in that: The method for producing a conductive pattern according to claim 15 is used.
33. A method for manufacturing a printed wiring board or an electromagnetic wave shielding film, characterized in that: The method for producing a conductive pattern according to claim 15 is used, and the support (D) is at least one selected from the group consisting of a rigid substrate, a film, a deposited film, ceramics, glass, a silicon wafer, and a metal.
34. A method for manufacturing a molded circuit component, characterized in that: The method for producing a conductive pattern according to claim 15 is used, and the support (D) is a molded article.
Citation Information
Patent Citations
Organic rust preventive treated copper foil and its production
JP1995258870A
Production of printed wiring board
JP2000286546A
Silane coupling agent and polymer composition containing the same
JP2002363189A
Surface treatment agent for metal
JP2015214743A
Surface treatment liquid and surface treatment method for bonding resist layer to base material or metal layer, and resin composition for resist layer
JP2016134454A
Cited By
Printed circuit board golden finger coating processing method
CN119676977A
Preparation method of double-layer ceramic substrate based on AMB process
CN120261296A
